Automated methods to accelerate fungal red listing: a case study for North American macrofungi - Vida J. Svahnström; Steven Bachman; Cátia Canteiro; Eimear Nic Lughadha; A. Martyn Ainsworth; Jessica L. Allen; Scott T. Bates; Matilda J.M. Brown; Susana P. Cunha; Anders Dahlberg; Susana C. Gonçalves; Tom W. May; et al. (Fungal Ecology, 2026)

Prenatal exposure to indoor PM2.5 and children's cognitive performance at 4 years of age: an observational analysis from the UGAAR randomized controlled trial - Battsetseg Ulziikhuu; Enkhjargal Gombojav; Chimeglkham Banzrai; Sarangerel Batsukh; Enkhtuul Enkhtuya; Buyantushig Boldbaatar; David C. Bellinger; Bruce P. Lanphear; Lawrence C. McCandless; Xing Yu; Ryan W. Allen (Environmental Pollution, 2026)

How harmless are alternative bioplastics? A review of their toxicological outcomes in aquatic organisms - Rui Cereja; Ana C. Ambrosino; Pedro Santana; João Bordado; Alda Pereira; Mónica Loureiro; Sofia Lourenço; Luís Aparício; Paula Allen; António Marques; Ana L. Maulvault (Aquatic Toxicology, 2026)

Improving inferences from coyote (Canis latrans) surveys across Illinois using integrated state-space models - Lauren C. Scopel; Maximilian L. Allen; Thomas J. Benson; Craig A. Miller; Kirk W. Stodola (Mammal Research, 2026)
Anthropogenic influences on landscapes changed wildlife communities immensely over the last century. One notable example of human-derived change is the expansion of coyote ( Canis latrans ) populations following the extirpation of apex carnivores and the inception of industrial agriculture in North America. In Illinois, USA, the Department of Natural Resources estimates relative abundance of coyotes using a variety of survey types, including harvest, participatory science, and observational measures. To examine how different survey methods tracked long-term changes in the state coyote population, we used four datasets of coyote relative abundance in state-space models, deriving estimates of abundance and population growth rates from 1980 to 2023. We compared estimates from individual datasets, as well as estimates from one model that integrated all datasets concurrently. Of the four datasets, only the spotlight survey indicated long-term positive population growth of coyotes, despite the spotlight survey also having the largest observational error. The integrated model showed long-term positive population growth and had high precision compared to the individual models. Individual counties showed high variation, illustrating declines and increases during different decades – fine-scale patterns likely reflect differences in human-caused mortality, prey availability, and habitat quality over time. We support the use of integrated models to combine inferences from relative abundance data, and we encourage the examination of observational biases that may overshadow long-term population changes. Further studies of fine-scale demographic change in coyote populations are needed.

Origin of negative Δ33S anomalies and Δ36S–Δ33S trends in 3700 Ma Isua sulfides: Searching for evidence of Eoarchean life in dolomitic meta-sedimentary rocks - Janaína N. Ávila; Allen P. Nutman; Vickie C. Bennett; Clark R.L. Friend; Martin Van Kranendonk (Precambrian Research, 2026)

Zircon geochronology of the Gordonbrook Serpentinite: A fragment of mantle wedge within the New England Orogen, eastern Australia - George G.F. Murray; Solomon Buckman; Allen P. Nutman; Wanchese M. Saktura; Jonathan C. Aitchison; Vickie C. Bennett; Zhen Yan; Changlei Fu (Lithos, 2026)

Mapping the Evidence for Cumulative Adverse Effects of Offshore Wind Installations on Birds - Leon A. Green-Tkacenko; Michael C. Allen; Julie L. Lockwood (Environmental Management, 2026)
Offshore wind (OSW) energy is rapidly expanding worldwide as countries aim to decarbonize their electrical grids. However, as OSW scales up to meet increasing demand, concerns about cumulative environmental effects have mounted. Over the past decade, empirical and theoretical studies on cumulative effects, especially on birds, have increased apace. We conducted a systematic review of the empirical literature on birds stored in the energy impact repository Tethys to determine how often different categories of evidence identified as important for understanding cumulative adverse effects have been measured. We used an evidence-mapping approach, aligning measurements recorded in Tethys with a published typology of evidence for cumulative adverse effects. Although many frameworks for understanding cumulative effects exist, rigorous quantification of measured outcomes is lacking. Our findings show that most empirical studies have identified which bird species are vulnerable to OSW effects (46%) or provided baseline data for species prior to OSW construction (40%), both of which are fundamental to understanding cumulative effects. In contrast, only 1% examined the nature of effect pathways (additive, synergistic, countervailing), and less than 3% sought to identify acceptable mortality thresholds for species populations affected by OSW. Additionally, there is a strong geographic bias toward the North Atlantic Ocean. Our analysis highlights critical gaps in the evidence required to understand the cumulative adverse effects of OSW on birds, guiding future research toward key areas where evidence is lacking.

Terrestrial environmental DNA survey substantially improves detection of satellite populations for an invasive insect - Julie L. Lockwood; Michael C. Allen; Anthony R. Vastano; Mario F. Hernandez; Christopher Eddy; Mariel Vandegrift; Kathleen E. Kyle; Caleb Truscott (Biological Invasions, 2026)
Early detection of satellite populations is essential for managing invasive species, but traditional methods often fall short when populations are sparse and widespread. We assessed the effectiveness of terrestrial environmental DNA (eDNA) surveys for detecting spotted lanternfly ( Lycorma delicatula ) along major highways in New York State, USA, a region at the invasion front in North America. Over 2 years, we sampled 83 sites covering 1,650 km of high-traffic roadway using a roller-based, host-tree surface eDNA collection method and compared results with concurrent visual surveys and a government-run trap surveillance program (‘circle traps’). We detected spotted lanternfly eDNA at 77% of sampled sites, while visual surveys indicated lanternfly presence at only 5% of these sites. On average, the delay between positive spotted lanternfly detection with eDNA and an eventual iNaturalist record was 662 days. Site occupancy models estimated detection probability at 0.77 per eDNA sample (95% CI 0.66–0.86), compared with 0.25 per trap (95% CI 0.21–0.31). Detection probability was lower in 2023 than in 2022 (eDNA: 0.68 vs. 0.89; traps: 0.13 vs. 0.32), likely due to our sampling in locations with lower population densities and distances farther from the invasion core. Extrapolation from hierarchical models indicated that three eDNA samples per occupied site would achieve a 95% cumulative detection probability, whereas circle traps would require 11–23 checks. Our surveys identified previously undocumented spotted lanternfly populations beyond the known range front at the time of the survey, including in high-risk agricultural and forested areas. These results show that terrestrial eDNA surveys can outperform traditional methods in detecting low-abundance invasive insects across large areas. Incorporating eDNA into early detection and rapid response efforts for terrestrial invasive species may improve management outcomes and reduce the risk of uncontrolled spread caused by human dispersal.

Day-to-day variability and method agreement of sweat sodium concentration during pilocarpine iontophoresis and exercise - Shawn C. Wierick; Zachary J. McKenna; Rosie I. Perez; Xiujing Zhao; Ryan S. Sellner; Becca M. Allen; Brendon P. McDermott (European Journal of Applied Physiology, 2026)
Purpose Sweat sodium testing is increasingly used to estimate electrolyte losses during exercise; however, the reliability of sweat sodium assessment and the influence of methodological factors remain unclear. We evaluated the day-to-day variability and agreement between common sweat induction, collection, and analytical approaches, including pilocarpine iontophoresis and exercise-induced sweating. Methods Twenty physically active adults (10 males 33 ± 11 y, 10 females 33 ± 10 y) completed two experimental trials separated by 48 h. Local sweat was induced at rest using pilocarpine iontophoresis. Participants then performed 60 min of treadmill running or cycling in 27 °C, 50% relative humidity, during which sweat was collected. Sweat sodium concentration was then analyzed and agreement between measurements was evaluated using Bland-Altman analysis. Results Day-to-day variability was good, with coefficients of variation of 13.8% for iontophoresis, 14.9% for exercise-derived Macroduct samples, and 9.9% for patch-based collection. Iontophoresis-derived sweat sodium concentrations were higher than exercise-derived values (42.0 ± 9.3 vs. 33.5 ± 11.0 mmol·L − 1 ) with a mean bias of -8.5 mmol·L − 1 (level of agreement (LoA): -32.2 to 15.2). Conclusion Sweat sodium concentration exhibits moderate day-to-day variability under controlled laboratory conditions. Exercise-derived values were lower than those obtained via pilocarpine iontophoresis, with iontophoresis overestimating sweat sodium by ~ 8.5mmol·L − 1 (~ 195mg·L − 1 ) on average. Although differences in methodological approaches were relatively small, these methodological factors contribute additional variability. Collectively, these findings indicate that both biological and methodological factors contribute to variability in sweat sodium assessment, and iontophoresis-derived values should be interpreted cautiously when estimating sodium losses during exercise.

Use of translational fusions to express functional Klebsiella oxytoca dinitrogenase reductase in plant mitochondria - Shoko Okada; Xueqin Wang; Christina M. Gregg; Robert S. Allen; Timothy Rhodes; Vanessa Gillespie; Ingrid Venables; Anu Mathew; Jessica K. Bilyj; Keren Byrne; Robert C. DeFeyter; Trevor D. Rapson; et al. (Plant Molecular Biology, 2026)
Engineering crop plants with the biological nitrogen fixation pathway is a longstanding goal of modern agriculture. Dinitrogenase reductase (NifH) is a critical component of the biological nitrogen fixation pathway, with multiple roles in metal cofactor assembly and catalysis. This enzyme must be folded correctly as a soluble homodimer and loaded with the [4Fe-4S] metallocluster for function. Previous studies have found that Klebsiella oxytoca ( Ko ) and Azotobacter vinelandii ( Av ) NifHs were mostly insoluble when targeted to plant mitochondria. Here we found that a translational fusion of two Ko NifH or Av NifH monomers, forming Ko NifHH or Av NifHH synthetic dimers, produced a soluble protein when targeted to plant mitochondria and co-expressed with the putative peptidyl-prolyl cis–trans isomerase NifM. Ko NifHH isolated after expression in leaf mitochondria at ambient oxygen showed some acetylene reduction activity, which did not require co-expression of the nitrogenase-specific metallocluster machinery NifS and NifU. This activity increased after iron-sulfur cluster reconstitution in vitro with recombinant NifU. In a parallel study, we tested a translational fusion of a variant iron-only dinitrogenase reductase ( Av AnfHv6) monomer that was soluble but not active as-isolated from plant mitochondria ( Av AnfHHv6) (Gregg et al. 2025a). Av AnfHHv6 was abundant and fully soluble when isolated from plant mitochondria, like its monomer. Av AnfHHv6 was not active as-isolated but could be largely activated by iron-sulfur cluster reconstitution in vitro. This study demonstrates how translational fusions help improve solubility and have the potential to generate an active NifH enzyme within plant mitochondria.

Hydromechanical modelling of rock slides triggered by atmospheric rivers: insights from British Columbia and Patagonia - Nicolas Jaimes; Sergio A. Sepúlveda; Brent C. Ward; Diana M. Allen; Paul Duhart (Natural Hazards, 2026)

Boater Compliance with Speed Regulations in High-Risk Areas for Marine Turtle Watercraft Strikes - Mariana M. P. B. Fuentes; Jessica Z. D’Auria; Stephanie Viegas Gkionis; Camille Kynoch; Joshua C. Manning; Sophie Mills; Sophie Rosengarten; Julia Saltzman; Armando Barsante Santos; Allen M. Foley (Coastal Management, 2026)

Links between dissolved organic matter and hydrogen peroxide dynamics in shallow Andean Patagonian lakes with contrasting underwater light climates - Sharon Allen Dohle; María C. Diéguez; Patricia E. Garcia (Journal of Environmental Sciences, 2026)

Multi-media occurrence, bioaccumulation, and exposure assessment of PFAS across a Midwestern U.S. State - Maria S. Sepúlveda; Lisa Brown; Staci L. Capozzi; Samantha C. Cullom; Jeffrey E. Dick; Daniel J. Foti; Ronaldo H. Franjul; Nicole L. Franklin; Jennifer L. Freeman; Carolina Gonzalez-Canas; Wanyue Hui; Yuxin Jiang; et al. (Environmental Research, 2026)

Adaptation and Response in Drylands: A Dryland Research Agenda and Campaign Strategy - Andrew F. Feldman; Sasha C. Reed; Konrad Wessels; Dennis Ojima; David J. P. Moore; William K. Smith; Niall P. Hanan; Cibele Amaral; Flurin Babst; Joel A. Biederman; Marcy Litvak; Natasha MacBean; et al. (Global Change Biology, 2026)
Dryland ecosystems cover 41% of Earth's land surfaces, account for 44% of cultivated lands and 60% of food sources, and make large contributions to the global water and carbon cycles. However, these ecosystems are experiencing unprecedented extremes including heatwaves, floods, and droughts as well as hotter temperatures and often declining water resource availability. These ecosystems are some of the most challenging to monitor given their high temporal variability with rapid response to their environment as well as vast spatial variability with intermixing of different plant species and life forms amongst bare soil coverage. The Adaptation and Response in Drylands (ARID) campaign was selected by National Aeronautics and Space Administration (NASA) as a scoping study to develop a research agenda for a dryland field campaign. Here, we detail our ARID science research agenda and implementation plan that were developed based on an extensive community engagement effort in over 160 events with over a thousand scientists, land managers, and Tribal communities between 2023 and 2024. The selected science themes cover drought and climate variability, ecosystem structure, function, and biodiversity, carbon cycle interannual variability and trends, and social ecological systems (land management and adaptation). We then detail our remote sensing, modeling, and field‐based strategies to capture high temporal and high spatial resolution processes. Finally, our implementation strategy is presented which includes focus area selections in a core intensive western U.S. domain and distributed international domains. This strategy includes our overarching guiding principles of using multi‐temporal airborne acquisitions and super sites as well as enhancing land management in co‐development with end‐user partners. While originally developed for NASA, our ARID report creates a blueprint for any future dryland field campaign, at any scale, that can be implemented widely for foundational and applied science objectives.

Space radiation and microgravity as models of accelerated aging: modulation of hepatic miRNA-TGF-β networks associated with senescence and fibrosis - Natalie Hayslip; JangKeun Kim; Sarah A. Ashiqueali; Xiang Zhu; Ridwan Hussein; Md Tanjim Alam; Driele N. Garcia; Bianka M. Zanini; Angela Kubik; Noah Allen; Elizabeth A. Blaber; Sarah S. Siddiqi; et al. (GeroScience, 2026)

“Ethological non-entity” no more? The role of the male in social Hymenoptera - D. Zarate; R. Keim; C. Allen; B. Peto; B. M. Guillén; G. Chong-Echavez; J. Maccaro; J. Purcell (Insectes Sociaux, 2026)

Training the Next Generation of Researchers to Advance Cancer Health Equity: Five Years of Experience from the Florida-California Cancer Research, Education and Engagement (CaRE2) Health Equity Center - John M. Allen; Bereket Mochona; Kinfe Redda; Debra Lyon; Brooke Hensel; John D. Carpten; Mariana C. Stern; Romonia Renee Reams; Folakemi T. Odedina; Diana J. Wilkie; Ite A. Offringa (Journal of Cancer Education, 2026)
The underrepresentation of racial and ethnic minority scientists in research is a significant barrier to eliminating cancer health disparities. There is a compelling need to develop a cadre of racially and ethnically diverse, well-trained scientists to effectively meet the nation’s biomedical, behavioral, population, and clinical cancer research needs. The Florida-California Cancer Research, Education and Engagement Health Equity Center’s program focuses on training this underrepresented workforce. Our center is a tri-institutional collaboration between Florida A&M University, University of Florida, and University of Southern California. Here, we report the organizational structure and initial outcomes of our program to support 130 unique talented, underrepresented individuals in 138 cancer research training positions. Over the past 5 years, we offered the following: (1) a 12-week early and focused exposure of 35 undergraduate students; (2) training and support of 23 postbaccalaureate trainees in a 1-year mentored research and training program; and (3) academic career development, mentorship, and tailored research training opportunities to increase the competitive research capacity for 33 graduate students, 13 post-doctoral scholars, and 34 early-stage investigators. Educators, researchers, policymakers, and community leaders can use our training models to advance equity through excellence in education and research for underrepresented minority populations, ultimately fostering a more just and inclusive society.

Whole genome resequencing data provide high-resolution conservation insights into population structure and life history - Natalie M. Allen; Andrew J. Mularo; Jong Yoon Jeon; Alvaro G. Hernandez; Ethan S. Streckfuss; Wade A. Ryberg; Toby J. Hibbitts; Brandon C. Bowers; Paul Crump; J. Andrew DeWoody (Conservation Genetics, 2026)
Whole genome resequencing can be a powerful tool for uncovering biological insights and quantifying population genomic metrics relevant to conservation. These insights have the potential to be most profound in secretive or elusive species that are understudied but whose populations may be waning. The western chicken turtle ( Deirochelys reticularia miaria ) is one such example where conservationists are concerned about reported population declines. Here, we report results from analyses of genome sequence data from western chicken turtles and how the associated inferences could be used to inform management decisions. We sequenced and assembled a novel reference genome, then conducted a population genomics resequencing survey across much of Texas that represents one of the first in any freshwater turtle. We uncovered fine-scale population structure indicative of natal philopatry. Absolute values of fixation indices were relatively small (all pairwise F ST $$\:\le\:$$ 0.03), but principal component analyses of the resequencing data readily separated individuals into clusters that correspond to their geographic sampling sites (i.e., wetland mosaic) and phylogenomic analyses revealed monophyletic groupings that also correspond to wetland mosaic geography. Estimates of individual genome-wide heterozygosity ( H ) were similar to those observed for threatened or endangered turtle species. Collectively, our data suggest that western chicken turtle populations are spatially differentiated due to natal philopatry and limited gene flow. We discuss the relevance of these insights as they pertain to turtle biology, including the conservation implications of philopatry in a species of concern.

Correction: The influence of high-load and combined high- and low-load resistance training on electromyographic behavior during an absolute muscular endurance task - Alex A. Olmos; Stephanie A. Sontag; Daniel J. Lawson; Lyric D. Richardson; Brenden L. Roth; Sunggun Jeon; Jaiden C. Smith; Allen L. Redinger; Michael A. Trevino (European Journal of Applied Physiology, 2026)

Nutritional composition of forage resources consumed by Florida manatees (Trichechus manatus latirostris) vulnerable to seagrass decline in the Indian River Lagoon - Aarin Conrad Allen; Danielle C. Sattelberger; Justin E. Campbell; Jeremy J. Kiszka (Aquatic Botany, 2026)

Acoustic telemetry reveals high site fidelity of yellow‐phase American eels Anguilla rostrata in a large river - Felix Eissenhauer; Tommi Linnansaari; Thomas C. Pratt; R. Allen Curry; Philip M. Harrison (Journal of Fish Biology, 2026)
Movement patterns and habitat use of yellow‐phase American eels Anguilla rostrata in the Wolastoq/Saint John River were examined using acoustic telemetry. Tracking 72 tagged yellow‐phase eels from late summer 2021 to autumn 2023 revealed overall restricted longitudinal movements (mean linear range ± standard deviation [SD] 6.4 ± 10.9 km) and high site fidelity. However, two eels exhibited small‐scale (20–25 km) seasonal movements within freshwater habitats and one eel undertook large‐scale (~83 km) seasonal movements between estuarine habitats in winter and freshwater habitats in summer. Tracking 24 yellow‐phase eels equipped with depth sensors indicated that depth use correlated with diel period, season and fish length, with eels occupying shallower habitats at night, presumably for foraging, and deeper habitats during the day, likely for shelter. Sixteen tagged eels presumably matured to the silver phase and initiated out‐migration in late summer. These eels moved rapidly through freshwater (mean ± SD 11.9 ± 8.8 km/day) but slowed considerably on reaching estuarine habitats (1.3 ± 1.3 km/day). These findings highlight the diversity of movement strategies in yellow‐phase eels and provide new insights into the transition to the migratory silver phase.

Sector expert and public perceptions of greening of grey infrastructure: a case study in Britain’s Ocean City - Jessica R. Allen; Anaëlle J. Lemasson; Melanie J. Bishop; Katherine A. Dafforn; Kate C. Dodds; Mick E. Hanley; Antony M. Knights; Mariana Mayer-Pinto; Abigail McQuatters-Gollop; Maria L. Vozzo; Louise B. Firth (Urban Ecosystems, 2026)

Coronary CT Angiography-Based Prediction Model for Hemodynamically Significant Coronary Stenosis Integrating Morphological and Plaque Characteristics - Chenxi Wang; Shuang Leng; Ru-San Tan; Ping Chai; Jiang Ming Fam; Adrian Fatt Hoe Low; Lohendran Baskaran; Lynette Teo; Felix Yung Jih Keng; Chee Yang Chin; Ching Ching Ong; John C. Allen; et al. (Cardiovascular Engineering and Technology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Beyond size and shape: Physicochemical properties of microplastic test materials generated by cryomilling - Lucy Howarth-Forster; Robyn Barrett; Robert Clough; Lisbet Sørensen; Jack Allen; Chris Powell; Richard C. Thompson; Matthew Cole; Michael Wilde (Journal of Hazardous Materials, 2026)

Impact of brewer’s spent grain on freshwater and marine harmful algal bloom species - C. Taylor Armstrong; Michael Gonsior; Allen R. Place (Harmful Algae, 2026)

What Lies Below: A Theory of Planned Behavior Study of Septic System Owners’ Practices in the Attoyac Bayou Watershed - Emmanuel. C. Okolo; Audrey McCrary; Karissa Palmer; T. Allen Berthold; Holli R. Leggette (Environmental Management, 2026)
As populations increase, water quality is increasingly affected by failing septic systems that introduce harmful fecal bacteria (e.g., E. coli ) into watersheds. Septic system owners play a vital role in reducing the impact of such bacteria. Therefore, our study aimed to examine factors that influence septic system owners’ decisions to improve septic system maintenance and protect watershed health in the Attoyac Bayou, located in East Texas. Using the theory of planned behavior, we addressed three research questions: (1) What are the characteristics of septic systems within the Attoyac Bayou watershed?; (2) How have septic system owners in the Attoyac Bayou watershed maintained their systems?; and (3) How do attitudes, subjective norms, and perceived behavioral control predict septic system maintenance behaviors? We sent a questionnaire to septic system owners in the Attoyac Bayou watershed that included questions about septic system characteristics, maintenance histories, and owners’ perceived norms, controls, attitudes, and intentions about septic systems. We found most septic systems in Attoyac Bayou are older conventional models with many owners lacking service contracts and reporting various times since the last pump out or inspection. While septic system owners generally demonstrate positive attitudes and confidence toward maintenance, our results revealed that attitude accounts for the greatest variance in maintenance behavior, with social norms and perceived behavioral control being less influential. Therefore, we recommend targeted messaging and interventions to reinforce positive attitudes, enhance perceived behavioral control, and promote consistent maintenance behaviors.

Correction: Practical Application of Geophysical Methods for Characterisation of Waste Rock Dumps - Christopher C. Allen; Matthew J. Cracknell; Clare B. Miller; Owen P. Missen; Sebastien Meffre (Mine Water and the Environment, 2026)

Practical Application of Geophysical Methods for Characterisation of Waste Rock Dumps - Christopher C. Allen; Matthew J. Cracknell; Clare B. Miller; Owen P. Missen; Sebastien Meffre (Mine Water and the Environment, 2026)

Irrigated sugarbeet water use and water use efficiency responses to various tillage practices - J.D. Jabro; W.B. Stevens; W.M. Iversen; U.M. Sainju; B.L. Allen; S.R. Dangi; C. Chen (Soil and Tillage Research, 2026)

Integrating nutritional and environmental impacts of animal-source foods via nutrition-based life-cycle assessment (nLCA) - Ajinkya Arun Atkare; Jonathan C. Allen; Minliang Yang (Sustainable Production and Consumption, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Financial viability and carbon intensity of hydrothermal waste valorization systems for bio-based asphalt binder - Ali Ahmad; Harshal D. Kawale; Sabrina Summers; Barbara Camila Bogarin Cantero; Cody M. Allen; Ramez M. Hajj; Paul C. Davidson; Yuanhui Zhang; Yalin Li (Chemical Engineering Journal, 2026)

Bias corrections for species- and source-resolved PM2.5 chemical transport model simulations using a geographically weighted regression - Ksakousti Skyllakou; Carlos S. Hernandez; Pablo Garcia Rivera; Brian Dinkelacker; Julian D. Marshall; C. Arden Pope; Allen L. Robinson; Spyros N. Pandis; Peter J. Adams (Atmospheric Environment, 2026)

The influence of high-load and combined high- and low-load resistance training on electromyographic behavior during an absolute muscular endurance task - Alex A. Olmos; Stephanie A. Sontag; Daniel J. Lawson; Lyric D. Richardson; Brenden L. Roth; Sunggun Jeon; Jaiden C. Smith; Allen L. Redinger; Michael A. Trevino (European Journal of Applied Physiology, 2025)

Thematic Layers of Genomic Susceptibility for Conservation Monitoring - Andrew N. Black; Jong Yoon Jeon; Andrew J. Mularo; Natalie M. Allen; Erangi Heenkenda; Julia C. Buchanan‐Schwanke; John W. Bickham; Zachary E. Lowe; J. Andrew DeWoody (Molecular Ecology, 2025)
Population genomics has great potential to inform applied conservation management and associated policy. However, the bioinformatic analyses and interpretation of population genomic datasets can be daunting and difficult to convey to nonspecialists, including on‐the‐ground conservationists that work with many state, federal and international agencies. We think that individual population genomic metrics of interest can be interpolated and ultimately distilled into thematic GIS layers that represent spatiotemporal genomic potential (or conversely, susceptibility) in conservation monitoring. As examples relevant to ongoing conservation efforts, we use introgressive hybridisation and individual heterozygosity to illustrate a conceptual approach for mapping population genomic susceptibility. The general framework of thematic layers could be extended to integrate key genomic metrics (e.g., runs of homozygosity and genomic load) that are relevant to many conservation efforts.

Increased quadriceps intermuscular adipose tissue in chronic liver disease is associated with an altered muscle transcriptome compared with healthy age matched controls - J. I. Quinlan; T. Nicholson; C. Bell; A. Dhaliwal; F. R. Williams; S. L. Allen; S. Choudhary; A. V. Rowlands; A. M. Elsharkawy; M. J. Armstrong; C. A. Greig; J. M. Lord; et al. (GeroScience, 2025)
Muscle fat infiltration (i.e., myosteatosis) is an important index of muscle health and pathology in disease states, such as chronic liver disease (CLD). However, it is unknown whether myosteatosis differs due to anatomical location. Further, the mechanistic implications of divergent intermuscular adipose tissue (IMAT) deposition remain unknown in patients with CLD. Thirty-three patients with CLD (55.0 ± 10.5 years) and 17 healthy controls (HC) (49.6 ± 15.4 years) were recruited. Quadriceps IMAT was estimated between 20 and 80% of muscle length and psoas IMAT at L3 via MRI. Body composition, muscle strength, and habitual activity were assessed. Fasted vastus lateralis muscle biopsies were collected and subjected to RNA sequencing analysis. ClinicalTrials.gov identifier: NCT04734496. IMAT was greater in CLD compared with HC in both quadriceps and psoas ( P < 0.0001). Quadriceps IMAT positively correlated with BMI ( r = 0.62), body fat ( r = 0.65), age ( r = 0.36), and negatively correlated with maximal knee extensor strength ( r = −0.45) and habitual physical activity ( r = −0.50) in CLD and HC. One hundred sixty-nine differentially expressed genes (DEGs) were identified in low IMAT CLD vs. HC, and 178 DEGs were identified in high IMAT CLD vs. HC. CLD patients with high and low IMAT exhibited defined expression profiles, with only 39 DEGs (representing 12.7%) in common. Pathway analysis of DEGs revealed enrichment of atrophic and pro-inflammatory pathways in the high IMAT group. IMAT is greater in patients with CLD compared to HC, irrespective of anatomical location, and is associated with reductions in muscle function and may be exacerbated by physical inactivity. IMAT appears to alter the muscle transcriptome in COLD, potentially exacerbating muscle loss. Graphical Abstract

Pore space properties and permeability of solution surfaces in Mesozoic shallow-water carbonates, southern Apennines, Italy - C. Manniello; V. La Bruna; E. Michie; R.E.B. Araùjo; F.H.R. Bezerra; D. Faulkner; M. Allen; X.M. Morais; G. Prosser; F. Agosta (Journal of Structural Geology, 2025)

Repeated low-dose copper algaecide treatments promote beneficial phytoplankton and zooplankton communities - Michael B. McDonald; Ashley V. Hennessey; Peyton P. Johnson; Matthew F. Gladfelter; Kate L. Merrill; Suzanne E. Tenison; Sathya S. Ganegoda; Tham C. Hoang; H. Allen Torbert; Benjamin H. Beck; Alan E. Wilson (Journal of Environmental Management, 2025)

New approach methodologies for assessing developmental toxicity of pharmaceuticals: Case examples and future directions - Nicola Powles-Glover; Allen R. Kaczor; Steven Van Cruchten; Christopher J. Bowman; Kimberly C. Brannen; Claudia Demarta-Gatsi; Isabelle LeConte; Amer Jamalpoor; Fumito Mikashima; Shermaine Mitchell-Ryan; Dinesh Stanislaus; Peter Theunissen; et al. (Reproductive Toxicology, 2025)

Estimating slip distribution along the southernmost ∼80 km of the San Andreas Fault by examining tectonically offset features - William C. Buckley; Patrick L. Williams; Thomas K. Rockwell; Allen M. Gontz (Geomorphology, 2025)

Ocular Motor and Vestibular Profile in Spinocerebellar Ataxia Type 27B: Toward a Practical Bedside Diagnostic Framework - Leonardo Eleuterio Ariello; Daniel R. Gold; Weiyi Mu; Michael C. Schubert; Claire Allen; Ashley Paul; David P.W. Rastall (The Cerebellum, 2025)

P27-34 See the Future Clearly: Human-Relevant adopted OECD Defined Approaches for Eye Hazard Classification - E. Adriaens; N. Alépée; T. Abo; A. Cavarzan; K. Mewes; C. Odriscoll; D. Allen (Toxicology Letters, 2025)

OS03-09 Surveying the Landscape: A Modular Generative Artificial Intelligence Workflow to Identify NAMs for Systemic Toxicity - D. Allen; E. Martin; J. Hamm; J. Wignall; K. To; T. Feiler; C. Lemeris; P. Kukic (Toxicology Letters, 2025)

Sex-dependent latent chilling injury changes estimates of thermal tolerance in a model insect - Mahmoud I. El-Saadi; Mitchell C. Allen; Heath A. MacMillan (Journal of Insect Physiology, 2025)

Thermal treatment of hexafluoropropylene oxide dimer acid (HFPO-DA) using a pilot-scale research combustor - Nathan H. Weber; Gabrielle V. West; William R. Roberson; John C. Mackie; James M. Mattila; Preston Burnette; Matthew Allen; William Preston; William P. Linak; Jonathan D. Krug (Journal of Hazardous Materials, 2025)

Integration of crop modeling and sensing into molecular breeding for nutritional quality and stress tolerance - Jonathan Berlingeri; Abelina Fuentes; Earl Ranario; Heesup Yun; Ellen Y. Rim; Oscar Garrett; Alexander Howard; Mary-Francis LaPorte; Sassoum Lo; Duke Pauli; Jenna Hershberger; Mason Earles; et al. (Theoretical and Applied Genetics, 2025)
Integrating innovative technologies into plant breeding is critical to bolster food and nutritional security under biotic and abiotic stresses in changing climates. While breeding efforts have focused primarily on yield and stress tolerance, emerging evidence highlights the need to also prioritize nutritional quality. Advanced molecular breeding approaches have enhanced our ability to develop improved crop varieties and could be substantially informed by the routine integration of crop modeling and remote sensing technologies. This review article discusses the potential of combining crop modeling and sensing with molecular breeding to address the dual challenge of nutritional quality and stress tolerance. We provide overviews of stress response strategies, challenges in breeding for quality traits, and the use of environmental data in genomic prediction. We also describe the status of crop modeling and sensing technologies in grain legumes, rice, and leafy greens, alongside the status of -omics tools in these crops and the use of AI with directed evolution to identify novel resistance genes. We describe the pairwise and three-way integration of AI-enabled sensing and biophysically and empirically constrained crop modeling into breeding to enable prediction of phenotypic and breeding values and dissection of genotype-by-environment-by-management interactions with increasing fidelity, efficiency, and temporal/spatial resolution to inform selection decisions. This article highlights current initiatives and future trends that focus on leveraging these advancements to develop more climate-resilient and nutritionally dense crops, ultimately enhancing the effectiveness of molecular breeding.

Ecological and Anthropogenic Drivers of Red Fox ( Vulpes vulpes ) Abundance and Site Use Across the Contiguous USA - Maximilian L. Allen; Katherine C. B. Weiss; Austin M. Green (Journal of Biogeography, 2025)
Aim Understanding species abundance and distribution is fundamental for conservation, particularly for widespread animals that influence ecosystem health and processes. Red foxes ( Vulpes vulpes ) are the most widely distributed mammalian carnivore globally, and provide many ecosystem services while also being a potential source of human‐wildlife conflict. Determining drivers of red fox distributions is therefore important for human‐wildlife coexistence and management. Location We analysed data from 4587 individual camera trap sites from 254 study arrays across the contiguous USA from a coordinated, multi‐year camera trap survey (Snapshot USA). Methods We assessed the site use probability (using a Bayesian occupancy model at the 1 km scale) and local abundance (using a Bayesian N‐mixture model at the 100 m scale) of red foxes. Specifically, we assessed the effects and relative importance of nine covariates we predicted would shape the distribution and abundance of red foxes. Results Our analyses revealed that the local abundance and site use probability of red foxes were influenced by the quadratic effect of impervious surfaces (highlighting a preference for an intermediate level at both fine and coarse scales), and a positive relationship with water availability. However, the local abundance and site use probability of red foxes varied relative to the detection rate of coyotes, the proportion of agricultural cover, and urban edge habitat. The relationship between red foxes and competitively dominant coyotes was complex, showing a positive association with coyotes at the 1 km scale (suggesting shared resource use) and a moderate negative association at the 100 m scale (suggesting competitive exclusion and resource partitioning). Main Conclusions Our results highlight how a generalist species, like red foxes, seeks out resources differentially at varying scales. Our findings highlight the complex interactions between red foxes and their environment, thus emphasising the importance of habitat features, especially urban development and water availability, in shaping their distribution and abundance.

Cancer interventions with faith-based organizations: a scoping review - Karen Hye-cheon Kim Yeary; Jennifer D. Allen; Elva Arredondo; Jamia Atemnkeng; Birnur Buzcu-Guven; Kelsey R. Day; Elizabeth Dicarlo; Taynara Formagini; Simona C. Kwon; Pearl McElfish; Lorna H. McNeill; Robert L. Newton; et al. (Cancer Causes & Control, 2025)

Optimizing automated photo identification for population assessments - Philip T. Patton; Krishna Pacifici; Robin W. Baird; Erin M. Oleson; Jason B. Allen; Erin Ashe; Aline Athayde; Charla J. Basran; Elsa Cabrera; John Calambokidis; Júlio Cardoso; Emma L. Carroll; et al. (Conservation Biology, 2025)
Several legal acts mandate that management agencies regularly assess biological populations. For species with distinct markings, these assessments can be conducted noninvasively via capture‐recapture and photographic identification (photo‐ID), which involves processing considerable quantities of photographic data. To ease this burden, agencies increasingly rely on automated identification (ID) algorithms. Identification algorithms present agencies with an opportunity—reducing the cost of population assessments—and a challenge—propagating misidentifications into abundance estimates at a large scale. We explored several strategies for generating capture histories with an ID algorithm, evaluating trade‐offs between labor costs and estimation error in a hypothetical population assessment. To that end, we conducted a simulation study informed by 39 photo‐ID datasets representing 24 cetacean species. We fed the results into a custom optimization tool to discern the optimal strategy for each dataset. Our strategies included choosing between truly and partially automated photo‐ID and, in the case of the latter, choosing the number of suggested matches to inspect. True automation was optimal for datasets for which the algorithm identified individuals well. As identification performance declined, the optimization recommended that users inspect more suggested matches from the ID algorithm, particularly for small datasets. False negatives (i.e., individual was resighted but erroneously marked as a first capture) strongly predicted estimation error. A 2% increase in the false negative rate translated to a 5% increase in the relative bias in abundance estimates. Our framework can be used to estimate expected error of the abundance estimate, project labor effort, and find the optimal strategy for a dataset and algorithm. We recommend estimating a strategy's false negative rate before implementing the strategy in a population assessment. Our framework provides organizations with insights into the conservation benefits and consequences of automation as conservation enters a new era of artificial intelligence for population assessments.

The effects of light intensity and water clarity on growth rates of age-0 walleye (Sander vitreus) - Noland O. Michels; Thomas R. Hrabik; Quinnlan C. Smith; Greg G. Sass; Allen F. Mensinger (Fisheries Research, 2025)

Phycotoxins Along Two New Jersey Estuaries—Limitations of Passive Samplers in a Complex System - C. Taylor Armstrong; Gregg P. Sakowicz; Juliette L. Smith; Marta P. Sanderson; Kimberly S. Reece; Allen R. Place (Estuaries and Coasts, 2025)
As a state with high shellfish aquaculture production in the USA, it is essential that New Jersey (NJ) managers identify the phycotoxins of concern and their spatiotemporal distribution. However, to date, there are no publications on phycotoxin presence or concentrations in NJ estuaries. Passive samplers are valuable for assessing emerging threats and long-term trends in phycotoxins, but high levels of phenolic compounds from NJ Pinelands may interfere by competing for binding sites on the resin. The objectives of this study were to (1) establish a baseline of the spatiotemporal trends of phycotoxins in two NJ estuaries using passive samplers, and (2) determine the impact of high phenolic content waters on passive samplers. Seven phycotoxins were detected: azaspiracids-1 (AZA1), azaspiracids-2 (AZA2), okadaic acid, dinophysistoxin-1, pectenotoxin-2, yessotoxin (YTX), and goniodomin A (GDA). This is the first publication to identify YTX on the US East Coast and the farthest north that GDA, AZA1 and AZA2 have been quantified on the US East Coast. No microcystins were detected, but their adsorption/desorption on resin were strongly impacted by the NJ waters during a controlled experiment. The complexity of this coastal water also impacted analysis of all other phycotoxins as depicted by elevated suppression as compared to methanolic standards. Phytoxigene™ analysis of the passive samplers revealed cyanobacteria with phycotoxin-producing genes for cylindrospermopsin and saxitoxin. Results indicated the need for extended annual monitoring of phycotoxins in NJ, further research to identify causative species of these emerging phycotoxins, and caution when using passive samplers in particular environmental conditions, as their efficacy may be compromised.

Pre‐existing phytoplankton biomass concentrations shape coastal plankton response to fire‐generated ash leachate - Nicholas Baetge; Kimberly H. Halsey; Erin J. Hanan; Michael J. Behrenfeld; Allen J. Milligan; Jason R. Graff; Parker Hansen; Craig A. Carlson; Rene M. Boiteau; Eleanor C. Arrington; Jacqueline Comstock; Elisa R. Halewood; et al. (Limnology and Oceanography, 2025)
Climate‐driven warming is projected to intensify wildfires, increasing their frequency and severity globally. Wildfires are an increasingly significant source of atmospheric deposition, delivering nutrients, organic matter, and trace metals to coastal and open ocean waters. These inputs have the potential to fertilize or inhibit microbial growth, yet their ecological impacts remain poorly understood. This study examines how ash leachate, derived from the 2017 Thomas Fire in California and lab‐produced ash from Oregon vegetation, affects coastal plankton communities. Shipboard experiments off the California coast examined how pre‐existing plankton biomass concentrations mediate responses to ash leachates. We found that ash leachate contained dissolved organic matter (DOM) that significantly increased bacterioplankton specific growth rates and DOM remineralization rates but had a negligible effect on bacterioplankton growth efficiency, suggesting low DOM bioavailability. Furthermore, ash‐derived DOM had a higher potential to accumulate in high biomass water, where pre‐existing DOM substrates may better support bacterial metabolism. Ash leachate had a neutral to negative effect on phytoplankton division rates and decreased microzooplankton grazing rates, particularly in low biomass water, leading to increased phytoplankton accumulation. Nanoeukaryotes accumulated in low biomass water, whereas picoeukaryotes and Synechococcus accumulated in high biomass water. Our findings suggest that the influence of ash deposition on DOM cycling, phytoplankton accumulation, and broader marine food web dynamics depends on pre‐existing biomass levels. Understanding these interactions is critical for predicting the biogeochemical consequences of increasing wildfire activity on marine ecosystems.

Can Macroevolution Inform Contemporary Extinction Risk? - Sarah‐Sophie Weil; Sébastien Lavergne; Florian C. Boucher; William L. Allen; Laure Gallien (Ecology Letters, 2025)
Current global changes are driving many species towards extinction, making the early detection of threatened species a priority for efficient conservation actions. However, the threat status of many species remains unknown due to insufficient data on updated distributions, population sizes and population trends and using ecological indicator traits, such as range size, is not always straightforward. Recent advances suggest that macroevolutionary indicators (rates of extinction, net diversification or niche evolution) could provide novel insights into extinction risk based on the assumption that macroevolutionary rates can serve as proxies for extinction‐promoting traits (small range size, narrow niche breadth or low evolutionary potential). However, this assumption has not yet been sufficiently investigated to use this approach. Here, we assess current understanding of the assumptions underlying the relationship between macroevolutionary indices and contemporary extinction risk. We find that only past extinction rates can be reliable predictors of current extinction risk due to their correlation with inherited extinction‐promoting traits. Assumptions underlying relationships between current extinction risk and diversification and niche evolution rates vary by taxon or ecological conditions, and require further investigation through targeted studies. When underlying assumptions are validated, macroevolutionary indicators could be promising tools complementing trait‐based approaches in identifying inherent extinction risk.

The effects of light and novel enrichment on Eastern indigo snake (Drymarchon couperi) behavior and physiology - Emily C. Lynch; Elizabeth A. Roznik; Dustin Smith; Alexis Alvey; Francesca Giammona; Janine L. Brown; Nicole Boisseau; Audrey Williams; Melissa Barr; Nick Allen; Katherine Hagen (Applied Animal Behaviour Science, 2025)

Transient Lymphatic Remodeling Follows Sub-Ablative High-Frequency Irreversible Electroporation Therapy in a 4T1 Murine Model - Savieay Esparza; Edward Jacobs; Jennifer H. Hammel; Sharon K. Michelhaugh; Nastaran Alinezhadbalalami; Margaret Nagai-Singer; Khan Mohammad Imran; Rafael V. Davalos; Irving C. Allen; Scott S. Verbridge; Jennifer M. Munson (Annals of Biomedical Engineering, 2025)
High-frequency irreversible electroporation (H-FIRE) is a minimally invasive local ablation therapy known to activate the adaptive immune system and reprogram the tumor microenvironment. Its predecessor, irreversible electroporation (IRE), transiently increases microvascular density and immune cell infiltration within the surviving non-ablated and non-necrotic tumor region, also known as the viable tumor region. However, the impact of pulse electric field therapies on lymphatic vessels, crucial for T-cell fate and maturation, remains unclear. This study investigates how sub-ablative H-FIRE (SA-HFIRE) affects lymphatic and blood microvascular remodeling in the 4T1 mammary mouse model. We conducted a temporal and spatial analysis to evaluate vascular changes in the viable tumor, peritumoral fat pad, and tumor-draining lymph node post-treatment. Histological examination showed a transient increase in blood vessel density on Day 1 post-treatment, followed by a spike in lymphatic vessel density in the viable tumor region on Day 3 post-treatment, increased lymphatic vessel density in the peripheral fat pad, and minimal remodeling of the tumor-draining lymph node within 3 days following treatment. Gene expression analysis indicated elevated levels of CCL21 and CXCL2 on Day 1 post-treatment, while VEGFA and VEGFC did not appear to contribute to vascular remodeling. Likewise, CCL21 protein content in tumor-draining axillary lymph nodes correlated with gene expression data from the viable tumor region. These findings suggest a dynamic shift in lymphatic and blood microvascular structures post-SA-HFIRE, potentially enhancing the adaptive immune response through CCL21-mediated lymphatic homing and subsequent lymph node microvascular remodeling. Future work will assess the immune and transport function of the microvasculature to inform experiments aimed at the application of adjuvant therapies during scenarios of tumor partial ablation.

High‐resolution analysis of sediments from Eighteen Mile Swamp (eastern Australia) records its transition from a fluctuating coastal lagoon to stable freshwater swamp - Jonathan C. Marshall; John Tibby; Patrick Moss; Hailey Martin; Allen Gontz; Annie Lau; Geraldine E. Jacobsen; Haidee Cadd; Patricia S. Gadd; Peter Negus; GLENN B. Mcgregor; Harald Hofmann; et al. (Journal of Quaternary Science, 2025)
This research documents the paleoenvironmental evolution of Eighteen Mile Swamp on North Stradbroke Island (Minjerribah), Australia, from oscillating coastal lagoon into stable freshwater swamp over the last ca. 1600 years. We analyzed multiple sediment cores via physical description, acid sulfate soil assays, particle size analysis, diatom and pollen assemblages, photosynthetic pigment content, and Itrax XRF spectrometry, alongside ground‐penetrating radar cross‐sections. This provided a detailed ecological, geochemical and chronological framework, derived from radiocarbon, Pu and 210 Pb dating, for the wetland's evolution. Results indicate spatial complexity in the timing of a pronounced shift in sedimentary conditions between ca. 300 and 1000 years ago, from estuarine mud to freshwater peat, marked by abrupt chemical and ecological changes. Unexpectedly, there were at least three and potentially many periods of dominant freshwater influence within the primarily estuarine phase, suggesting episodic estuarine closure and freshening by groundwater influx. Results provide critical insights into the complex response of subtropical wetland systems to environmental change, emphasizing the importance of interdisciplinary approaches in understanding both sedimentologic and geomorphic responses in coastal wetlands, and their potential vulnerability to future climate change. The study of Eighteen Mile Swamp is significant as it provides a detailed paleoenvironmental reconstruction that documents the wetland's evolving nature over the past two millennia. This research highlights the importance of understanding historical responses of wetlands to environmental changes, which helps inform their current and future management, conservation and restoration efforts, particularly in the context of climate change and human impacts. This study also serves as a tribute to the late Lynda Petherick, acknowledging her contributions in this field.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Nutrient recovery from high-salinity dairy wastewater through the cultivation of acclimatized microalgae - Rui Xiao; Erika Carter; Austin Allen; Pei-Lin Tan; Yu-Hua Zheng; Qian Chen; Shun-Ni Zhu; Sudeep C. Popat; Allan Knopf; Clinton F. Williams; Howard H. Chou; Huan Chen (Journal of Water Process Engineering, 2025)

Governance of a landscape: The role of formal and informal organizations - Hannah Legatzke; Brian C. Chaffin; Theresa M. Floyd; Simanti Banerjee; Sarah Church; Sabrina Gulab; Samantha Hamlin; Gwendwr R. Meredith; Alexander L. Metcalf; Holly K. Nesbitt; Emily Sutherland-Rowen; Daniel R. Uden; et al. (Journal of Environmental Management, 2025)

Distinct N-cycling microbial communities contribute to microtopographic variation in soil N2O emissions from denitrification - Alexander H. Krichels; Robert A. Sanford; Joanne C. Chee-Sanford; Lynn Connor; Rachel Van Allen; Angela D. Kent; Wendy H. Yang (Soil Biology and Biochemistry, 2025)

Paleo-data is policy relevant: How do we better incorporate it in policy and decision making? - K.J. Allen; C. Gouramanis; D. Sauchyn (Global and Planetary Change, 2025)

Using seasonal palaeo-flow reconstructions and artificial neural networks for daily water balance modelling: A case study from Tasmania, Australia - Danielle C. Verdon-Kidd; Kathryn J. Allen; Luke J. Kidd; Carolyn Maxwell; Mark Willis; Patrick Baker (Global and Planetary Change, 2025)

Evaluating the tolerance of harmful algal bloom communities to copper - Ashley V. Hennessey; Michael B. McDonald; Peyton P. Johnson; Matthew F. Gladfelter; Kate L. Merrill; Suzanne E. Tenison; Sathya S. Ganegoda; Tham C. Hoang; H. Allen Torbert; Benjamin H. Beck; Alan E. Wilson (Environmental Pollution, 2025)

A review of 3.7 Ga stromatolites from the Isua Supracrustal Belt, West Greenland - Martin J. Van Kranendonk; Allen P. Nutman; Clark R.L. Friend; Vickie C. Bennett (Earth-Science Reviews, 2025)

Life history, reproductive, and demographic parameters for bottlenose dolphins (Tursiops truncatus) in Sarasota Bay, Florida - Randall S. Wells; Aleta A. Hohn; Michael D. Scott; Jay C. Sweeney; Forrest I. Townsend; Jason B. Allen; Aaron A. Barleycorn; Katherine A. McHugh; Kim Bassos-Hull; Gretchen N. Lovewell; Deborah A. Duffield; Cynthia R. Smith; et al. (Frontiers in Marine Science, 2025)
Studies of the resident community of bottlenose dolphins ( Tursiops truncatus ) of Sarasota Bay, Florida, have been conducted for more than 50 years. Detailed histories have been collected for resident individuals through integrated observations, systematic photographic identification surveys, tagging and tracking, catch-and-release health assessments, remote biopsy sampling, and stranding response. This has produced a unique dataset documenting life history milestones and vital rates of a small cetacean. Analyses of data from 482 resident Sarasota Bay dolphins have revealed estimated maximum life spans of 67 years for females and 52 years for males. For females, predicted age at sexual maturation is 8.5 years, with a predicted age at first reproduction of 9.6 years. Females were observed to give birth when 6-48 years of age, and have been documented with as many as 12 calves, with 45% observed post-separation. Ten percent of females were considered to be reproductively senescent, having gone >13 years without producing a calf. For males, predicted age at sexual maturation is 10 years. Males 10-43 years old sired calves, producing up to 7 calves each. The average calving interval was 3.5 years, albeit with effects due to mother’s age, birth order, and calf survival. Seasonal reproduction was evident, with 81% of births occurring during May-July. Mean annual birth rate was 0.071. Mean annual fecundity was 0.182 births/adult female (defined as females 6 yrs or older). Recruitment rate through reproduction was estimated to be 0.050 based on calves surviving their first year. Immigration was infrequent, with an estimated annual rate of 0.003-0.013. Estimated mean annual maximum loss rate, from mortality, emigration, and changed identification characteristics, was 0.072. Periods of increased loss rates were related to environmental events, and factors that may be important to long-term population resilience were suggested.

Efficacy, non-target impacts, and costs of mechanical control options against a bioturbator in bivalve aquaculture - Jennifer L. Ruesink; C. Haleh Mawson; Brian Allen; Jeffrey Barrett; David Beugli; Steven Booth; Laura Butler; Bill Dewey; Cinde R. Donoghue; Brett R. Dumbauld; Kristine Feldman; Zachary Forster; et al. (Aquaculture, 2025)

Coupling tree-ring and geomorphic analyses to reconstruct the 1950s massive Glacier Lake Outburst Flood at Grosse Glacier, Chilean Patagonia - S. Gorsic; C. Corona; A. Muñoz-Torrero Manchado; J. Lopez-Saez; S. Allen; J.A. Ballesteros-Cánovas; A. Dussaillant; M. Stoffel (Science of The Total Environment, 2025)

Visual sensitivity, foraging behavior, and success of walleye (Sander vitreus) under ecologically relevant downwelling light conditions - Noland O. Michels; Quinnlan C. Smith; Loranzie S. Rogers; Thomas R. Hrabik; Greg G. Sass; Allen F. Mensinger (Environmental Biology of Fishes, 2025)

First record of the seagrass Halophila stipulacea (Forsskal) Ascherson in the waters of the continental United States (Key Biscayne, Florida) - Justin E. Campbell; Aarin-Conrad Allen; Danielle C. Sattelberger; Matthew D. White; James W. Fourqurean (Aquatic Botany, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Percutaneous balloon angioplasty as a treatment for cor triatriatum sinister in a cat - J. Allen; K. Phipps; K. Barrett; C. Day (Journal of Veterinary Cardiology, 2024)

Mn-porphyrins in a four-helix bundle participate in photo-induced electron transfer with a bacterial reaction center - J. C. Williams; M. S. Faillace; E. J. Gonzalez; R. E. Dominguez; K. Knappenberger; D. A. Heredia; T. A. Moore; A. L. Moore; J. P. Allen (Photosynthesis Research, 2024)

Strengths and limitations of the worm development and activity test (wDAT) as a chemical screening tool for developmental hazards - Piper Reid Hunt; Bonnie Welch; Jessica Camacho; Joelle K. Salazar; Megan L. Fay; Jon Hamm; Patricia Ceger; Dave Allen; Suzanne C. Fitzpatrick; Jeffrey Yourick; Robert L. Sprando (Toxicology and Applied Pharmacology, 2024)

Smartphone-based hyperspectral imaging for ice sheet and proglacial applications in South-West Greenland - M.B. Stuart; M. Davies; C. Fisk; E. Allen; A.J. Sole; R. Ing; M.J. Hobbs; J.R. Willmott (Science of The Total Environment, 2024)

The long-chain polyfluorinated alkyl substance perfluorohexane sulfonate (PFHxS) promotes bone marrow adipogenesis - Laimar C. Garmo; Mackenzie K. Herroon; Shane Mecca; Alexis Wilson; David R. Allen; Manisha Agarwal; Seongho Kim; Michael C. Petriello; Izabela Podgorski (Toxicology and Applied Pharmacology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Optimizing feature selection with gradient boosting machines in PLS regression for predicting moisture and protein in multi-country corn kernels via NIR spectroscopy - Runyu Zheng; Yuyao Jia; Chidanand Ullagaddi; Cody Allen; Kent Rausch; Vijay Singh; James C. Schnable; Mohammed Kamruzzaman (Food Chemistry, 2024)

Microbial aromatic amino acid metabolism is modifiable in fermented food matrices to promote bioactivity - Mikaela C. Kasperek; Adriana Velasquez Galeas; Maria Elisa Caetano-Silva; Zifan Xie; Alexander Ulanov; Michael La Frano; Suzanne Devkota; Michael J. Miller; Jacob M. Allen (Food Chemistry, 2024)

Mesoscale Brain Mapping: Bridging Scales and Modalities in Neuroimaging – A Symposium Review - Joshua K. Marchant; Natalie G. Ferris; Diana Grass; Magdelena S. Allen; Vivek Gopalakrishnan; Mark Olchanyi; Devang Sehgal; Maxina Sheft; Amelia Strom; Berkin Bilgic; Brian Edlow; Elizabeth M. C. Hillman; et al. (Neuroinformatics, 2024)
Advances in the spatiotemporal resolution and field-of-view of neuroimaging tools are driving mesoscale studies for translational neuroscience. On October 10, 2023, the Center for Mesoscale Mapping (CMM) at the Massachusetts General Hospital (MGH) Athinoula A. Martinos Center for Biomedical Imaging and the Massachusetts Institute of Technology (MIT) Health Sciences Technology based Neuroimaging Training Program (NTP) hosted a symposium exploring the state-of-the-art in this rapidly growing area of research. “Mesoscale Brain Mapping: Bridging Scales and Modalities in Neuroimaging” brought together researchers who use a broad range of imaging techniques to study brain structure and function at the convergence of the microscopic and macroscopic scales. The day-long event centered on areas in which the CMM has established expertise, including the development of emerging technologies and their application to clinical translational needs and basic neuroscience questions. The in-person symposium welcomed more than 150 attendees, including 57 faculty members, 61 postdoctoral fellows, 35 students, and four industry professionals, who represented institutions at the local, regional, and international levels. The symposium also served the training goals of both the CMM and the NTP. The event content, organization, and format were planned collaboratively by the faculty and trainees. Many CMM faculty presented or participated in a panel discussion, thus contributing to the dissemination of both the technologies they have developed under the auspices of the CMM and the findings they have obtained using those technologies. NTP trainees who benefited from the symposium included those who helped to organize the symposium and/or presented posters and gave “flash” oral presentations. In addition to gaining experience from presenting their work, they had opportunities throughout the day to engage in one-on-one discussions with visiting scientists and other faculty, potentially opening the door to future collaborations. The symposium presentations provided a deep exploration of the many technological advances enabling progress in structural and functional mesoscale brain imaging. Finally, students worked closely with the presenting faculty to develop this report summarizing the content of the symposium and putting it in the broader context of the current state of the field to share with the scientific community. We note that the references cited here include conference abstracts corresponding to the symposium poster presentations.

P01-75 Between-laboratory reproducibility of the modified STE to identify UN GHS Category 1 surfactants - D. Allen; T. Abo; E. Adriaens; N. Alepee; A. Cavarzan; A. Cuciureanu; K. Mewes; C. O'Driscoll (Toxicology Letters, 2024)

Robust modeling of material flows to end‐uses under uncertainty: UK wood flows and material efficiency opportunities - R. L. Anspach; S. R. Allen; R. C. Lupton (Journal of Industrial Ecology, 2024)
In this study we quantify wood flows from raw materials to end‐uses for the United Kingdom in a robust way using a new material flow analysis (MFA) model with uncertainty. This is important to identify opportunities for efficiency given constraints on wood supply. We have developed a new “ProbPACTOT” MFA model which introduces a systematic method to handle mixed units during reconciliation and uncertainty in data observations, conversion factors, and process recipes. This makes it possible to track material flows all the way to end‐uses, which is otherwise difficult because the diverse materials, data types, and units used to quantify end‐products are hard to integrate into standard allocation‐based MFA models. We apply the model for the case of wood in the United Kingdom by defining 56 process recipes and reconciling 117 data observations from various sources. The results quantify upstream production and trade flows, through to 19 specific end‐uses of wood fibers. We use this to show the potential scale of savings by enhancing material efficiency; for example, if pallets were used 25% more intensively, 0.49 0.2 of wood fibers could be saved, corresponding to 4%–7% of the total soft sawnwood consumption of the United Kingdom. Judging the scale of opportunities for wood material efficiency in the United Kingdom is important domestically, and has global significance as the United Kingdom is the second largest net importer of wood products in the world. Moreover, this study proposes an important advancement in MFA giving a structure for modeling uncertain material flows up to end‐uses, applicable to any material. This article met the requirements for a gold‐gold JIE data openness badge described at http://jie.click/badges .

Mentoring Minority Cancer Researchers of Tomorrow: Comparison of the Face-to-Face, Virtual, and Hybrid Training Methods of the CaRE2 Summer Cancer Research Education and Training Program - Bereket Mochona; Kinfe K. Redda; Ite A. Offringa; John Allen; John D. Carpten; Mariana C. Stern; Renee R. Reams; Diana J. Wilkie (Journal of Cancer Education, 2024)

Isolation, small population size, and management influence inbreeding and reduced genetic variation in K’gari dingoes - Susan M. Miller; Linda Behrendorff; Benjamin L. Allen; Rose L. Andrew; Guy Ballard; J. William O. Ballard; Kylie M. Cairns; Gabriel C. Conroy; Peter J. S. Fleming; Catherine E. Grueber; Jane Oakey; Deane A. Smith; et al. (Conservation Genetics, 2024)
Small island populations are vulnerable to genetic decline via demographic and environmental stochasticity. In the absence of immigration, founder effects, inbreeding and genetic drift are likely to contribute to local extinction risk. Management actions may also have a greater impact on small, closed populations. The demographic and social characteristics of a species can, however, delay the impact of threats. K’gari, a ~ 1 660 km 2 island off the Australian east coast and UNESCO World Heritage Site (Fraser Island 1842–2023), supports an isolated population of approximately 70–200 dingoes that represent an ideal opportunity to explore the small island paradigm. To examine temporal and spatial patterns of genetic diversity in this population we analysed single nucleotide polymorphism (SNP) genotype data (72 454 SNPS) for 112 K’gari dingoes collected over a 25-year period (1996 to 2020). Genetic diversity was lower in K’gari dingoes than mainland dingoes at the earliest time point in our study and declined significantly following a management cull in 2001. We did not find any spatial genetic patterns on the island, suggesting high levels of genetic connectivity between socially discrete packs. This connectivity, combined with the social structure and behaviour of dingoes, may act in concert to buffer the population from the impacts of genetic drift in the short term. Nevertheless, a general decline in genetic variation via inbreeding and drift has occurred over the past 20 years which we suggest should be considered in any future management planning for the population. Monitoring patterns of genetic variation, together with a clearer understanding of the social ecology of K’gari dingoes, will aid in the development of measurable genetic targets set over ecologically meaningful timelines, and help ensure continued survival of this culturally important population.

Predicting whaler shark presence and interactions with humans in southern Queensland, Australia - S.M. Lopes; J.E. Williamson; Y. Lambreghts; A.P. Allen; C. Brown (Science of The Total Environment, 2024)

Improving forage nutritive value and livestock performance with spatially-patchy prescribed fire in grazed rangeland - Megan R. Wanchuk; Devan Allen McGranahan; Kevin K. Sedivec; Marisol Berti; Kendall C. Swanson; Torre J. Hovick (Agriculture, Ecosystems & Environment, 2024)

Differences in the anatomy and physiology of the human and rat respiratory tracts and impact on toxicological assessments - Andreas O. Stucki; Ursula G. Sauer; David G. Allen; Nicole C. Kleinstreuer; Monique M. Perron; Krystle L. Yozzo; Anna B. Lowit; Amy J. Clippinger (Regulatory Toxicology and Pharmacology, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

An impact evaluation of conservation investments targeting long‐distance migratory species - C. Josh Donlan; Diana Eusse‐González; Gloria M. Luque; Matthew E. Reiter; Viviana Ruiz‐Gutierrez; Michael C. Allen; Richard Johnston‐González; Orin J. Robinson; Guillermo Fernández; Eduardo Palacios; Jorge Valenzuela (Conservation Biology, 2024)
We evaluated the impact of a philanthropic program investing in the conservation of sites along the Pacific Americas Flyway, which spans >16,000 km of coastline and is used by millions of shorebirds. Using a quasi‐experimental, mixed methods approach, we estimated what would have happened to shorebird populations at 17 wintering sites without the sustained and additional investment they received. We modeled shorebird populations across the entire flyway and at sites with and without investment. Combining shorebird abundance estimates with a land‐cover classification model, we used the synthetic control method to create counterfactuals for shorebird trends at the treatment sites. We found no evidence of an overall effect across three outcome variables. Species‐ and site‐level treatment effects were heterogeneous, with a few cases showing evidence of a positive effect, including a site with a high level of overall investment. Results suggest six shorebirds declined across the entire flyway, including at many Latin American sites. However, the percentage of flyway populations present at the sites remained stable, and the percentage at the treatment sites was higher (i.e., investment sites) than at control sites. Multiple mechanisms behind our results are possible, including that investments have yet to mitigate impacts and negative impacts at other sites are driving declines at the treatment sites. A limitation of our evaluation is the sole focus on shorebird abundance and the lack of data that prohibits the inclusion of other outcome variables. Monitoring infrastructure is now in place to design a more robust and a priori shorebird evaluation framework across the entire flyway. With this framework, it will prove easier to prioritize limited dollars to result in the most positive conservation outcomes.

Detecting early winter open-water zones on Alaska rivers using dual-polarized C-band Sentinel-1 synthetic aperture radar (SAR) - Melanie Engram; Franz J. Meyer; Dana R.N. Brown; Sarah Clement; Allen C. Bondurant; Katie V. Spellman; Laura E. Oxtoby; Christopher D. Arp (Remote Sensing of Environment, 2024)

Evaluation of in silico model predictions for mammalian acute oral toxicity and regulatory application in pesticide hazard and risk assessment - Patricia L. Bishop; Kamel Mansouri; William P. Eckel; Michael B. Lowit; David Allen; Amy Blankinship; Anna B. Lowit; D. Ethan Harwood; Tamara Johnson; Nicole C. Kleinstreuer (Regulatory Toxicology and Pharmacology, 2024)

A review of the Pacific sleeper shark Somniosus pacificus: biology and fishery interactions - Mary Elizabeth Matta; Cindy A. Tribuzio; Lindsay N. K. Davidson; Keith R. Fuller; Garrett C. Dunne; Allen H. Andrews (Polar Biology, 2024)

Accelerating carbon neutrality in China: Sensitive intervention points for the energy and transport sectors in Beijing and Hong Kong - Sum Yue Chung; Matthew C. Ives; Myles R. Allen; Jay R.S. Doorga; Yuan Xu (Journal of Cleaner Production, 2024)

Towards reusable building blocks for agent-based modelling and theory development - Uta Berger; Andrew Bell; C. Michael Barton; Emile Chappin; Gunnar Dreßler; Tatiana Filatova; Thibault Fronville; Allen Lee; Emiel van Loon; Iris Lorscheid; Matthias Meyer; Birgit Müller; et al. (Environmental Modelling & Software, 2024)

Mesocarnivores vary in their spatiotemporal avoidance strategies at communications hubs of an apex carnivore - Maximilian L. Allen; Alexandra C. Avrin; Heiko U. Wittmer; Yiwei Wang; Christopher C. Wilmers (Oecologia, 2024)

Correction: Harnessing the Electrochemical Effects of Electroporation-Based Therapies to Enhance Anti-tumor Immune Responses - Zaid S. Salameh; Kenneth N. Aycock; Nastaran Alinezhadbalalami; Khan Mohammad Imran; Iain H. McKillop; Irving C. Allen; Rafael V. Davalos (Annals of Biomedical Engineering, 2024)

Fjord circulation permits a persistent subsurface water mass in a long, deep mid-latitude inlet - Laura Bianucci; Jennifer M. Jackson; Susan E. Allen; Maxim V. Krassovski; Ian J. W. Giesbrecht; Wendy C. Callendar (Ocean Science, 2024)
Fjords are deep nearshore zones that connect watersheds and oceans, typically behaving as an estuary. In some fjords, strong katabatic winds in winter (also known as Arctic outflow wind events) can lead to cooling and reoxygenation of subsurface waters, with effects lasting until the following autumn, as observed in 2019 in Bute Inlet, British Columbia, Canada. We used high-resolution, three-dimensional ocean model summer simulations to investigate the mechanisms allowing for the persistence of these cool, oxygen-rich subsurface conditions in Bute Inlet. The slow residual circulation underneath the brackish outflow (and consequent slow advection) in this long, deep fjord is a main reason why the cold subsurface water mass stays in place until conditions change in autumn (i.e., start of stronger wind mixing and reduced freshwater forcing). Another mechanism is a positive feedback provided by the presence of this subsurface water mass, since it further reduces the already weak residual circulation. These findings are applicable to any similar long, deep fjord that experiences katabatic winds in winter, and they could have implications not only for the preservation of water masses but other possible subsurface features (e.g., pollutant spills, planktonic larvae). Furthermore, the identification of mechanisms that permit persistent cold and oxygenated conditions is key to understanding potential areas of ecological refugia in a warming and deoxygenating ocean.

Global patterns of allochthony in stream–riparian meta‐ecosystems - Daniel C. Allen; James Larson; Christina A. Murphy; Erica A. Garcia; Kurt E. Anderson; Michelle H. Busch; Alba Argerich; Alice M. Belskis; Kierstyn T. Higgins; Brooke E. Penaluna; Veronica Saenz; Jay Jones; et al. (Ecology Letters, 2024)
Ecosystems that are coupled by reciprocal flows of energy and nutrient subsidies can be viewed as a single “meta‐ecosystem.” Despite these connections, the reciprocal flow of subsidies is greatly asymmetrical and seasonally pulsed. Here, we synthesize existing literature on stream–riparian meta‐ecosystems to quantify global patterns of the amount of subsidy consumption by organisms, known as “allochthony.” These resource flows are important since they can comprise a large portion of consumer diets, but can be disrupted by human modification of streams and riparian zones. Despite asymmetrical subsidy flows, we found stream and riparian consumer allochthony to be equivalent. Although both fish and stream invertebrates rely on seasonally pulsed allochthonous resources, we find allochthony varies seasonally only for fish, being nearly three times greater during the summer and fall than during the winter and spring. We also find that consumer allochthony varies with feeding traits for aquatic invertebrates, fish, and terrestrial arthropods, but not for terrestrial vertebrates. Finally, we find that allochthony varies by climate for aquatic invertebrates, being nearly twice as great in arid climates than in tropical climates, but not for fish. These findings are critical to understanding the consequences of global change, as ecosystem connections are being increasingly disrupted.

Population genomic structure of a widespread, urban‐dwelling mammal: The eastern grey squirrel ( Sciurus carolinensis ) - Nicole A. Fusco; Bradley J. Cosentino; James P. Gibbs; Maximilian L. Allen; Alexander J. Blumenfeld; George H. Boettner; Elizabeth J. Carlen; Merri Collins; Catherine Dennison; Devin DiGiacopo; André‐Philippe Drapeau Picard; Jonathan Edmonson; et al. (Molecular Ecology, 2024)
Urbanization is a persistent and widespread driver of global environmental change, potentially shaping evolutionary processes due to genetic drift and reduced gene flow in cities induced by habitat fragmentation and small population sizes. We tested this prediction for the eastern grey squirrel ( Sciurus carolinensis ), a common and conspicuous forest‐dwelling rodent, by obtaining 44K SNPs using reduced representation sequencing (ddRAD) for 403 individuals sampled across the species' native range in eastern North America. We observed moderate levels of genetic diversity, low levels of inbreeding, and only a modest signal of isolation‐by‐distance. Clustering and migration analyses show that estimated levels of migration and genetic connectivity were higher than expected across cities and forested areas, specifically within the eastern portion of the species' range dominated by urbanization, and genetic connectivity was less than expected within the western range where the landscape is fragmented by agriculture. Landscape genetic methods revealed greater gene flow among individual squirrels in forested regions, which likely provide abundant food and shelter for squirrels. Although gene flow appears to be higher in areas with more tree cover, only slight discontinuities in gene flow suggest eastern grey squirrels have maintained connected populations across urban areas in all but the most heavily fragmented agricultural landscapes. Our results suggest urbanization shapes biological evolution in wildlife species depending strongly on the composition and habitability of the landscape matrix surrounding urban areas.

An expert‐based system to predict population survival rate from health data - Lori H. Schwacke; Len Thomas; Randall S. Wells; Teresa K. Rowles; Gregory D. Bossart; Forrest Townsend; Marilyn Mazzoil; Jason B. Allen; Brian C. Balmer; Aaron A. Barleycorn; Ashley Barratclough; Louise Burt; et al. (Conservation Biology, 2024)
Timely detection and understanding of causes for population decline are essential for effective wildlife management and conservation. Assessing trends in population size has been the standard approach, but we propose that monitoring population health could prove more effective. We collated data from 7 bottlenose dolphin ( Tursiops trun catus) populations in the southeastern United States to develop a method for estimating survival probability based on a suite of health measures identified by experts as indices for inflammatory, metabolic, pulmonary, and neuroendocrine systems. We used logistic regression to implement the veterinary expert system for outcome prediction (VESOP) within a Bayesian analysis framework. We fitted parameters with records from 5 of the sites that had a robust network of responders to marine mammal strandings and frequent photographic identification surveys that documented definitive survival outcomes. We also conducted capture–mark–recapture (CMR) analyses of photographic identification data to obtain separate estimates of population survival rates for comparison with VESOP survival estimates. The VESOP analyses showed that multiple measures of health, particularly markers of inflammation, were predictive of 1‐ and 2‐year individual survival. The highest mortality risk 1 year following health assessment related to low alkaline phosphatase (odds ratio [OR] = 10.2 [95% CI: 3.41–26.8]), whereas 2‐year mortality was most influenced by elevated globulin (OR = 9.60 [95% CI: 3.88–22.4]); both are markers of inflammation. The VESOP model predicted population‐level survival rates that correlated with estimated survival rates from CMR analyses for the same populations (1‐year Pearson's r = 0.99, p = 1.52 × 10 –5 ; 2‐year r = 0.94, p = 0.001). Although our proposed approach will not detect acute mortality threats that are largely independent of animal health, such as harmful algal blooms, it can be used to detect chronic health conditions that increase mortality risk. Random sampling of the population is important and advancement in remote sampling methods could facilitate more random selection of subjects, obtainment of larger sample sizes, and extension of the approach to other wildlife species.

Effects of a high cholesterol diet on chill tolerance are highly context-dependent in Drosophila - Mitchell C. Allen; Marshall W. Ritchie; Mahmoud I. El-Saadi; Heath A. MacMillan (Journal of Thermal Biology, 2024)

Harnessing the Electrochemical Effects of Electroporation-Based Therapies to Enhance Anti-tumor Immune Responses - Zaid S. Salameh; Kenneth N. Aycock; Nastaran Alinezhadbalalami; Khan Mohammad Imran; Iain H. McKillop; Irving C. Allen; Rafael V. Davalos (Annals of Biomedical Engineering, 2024)
This study introduces a new method of targeting acidosis (low pH) within the tumor microenvironment (TME) through the use of cathodic electrochemical reactions (CER). Low pH is oncogenic by supporting immunosuppression. Electrochemical reactions create local pH effects when a current passes through an electrolytic substrate such as biological tissue. Electrolysis has been used with electroporation (destabilization of the lipid bilayer via an applied electric potential) to increase cell death areas. However, the regulated increase of pH through only the cathode electrode has been ignored as a possible method to alleviate TME acidosis, which could provide substantial immunotherapeutic benefits. Here, we show through ex vivo modeling that CERs can intentionally elevate pH to an anti-tumor level and that increased alkalinity promotes activation of naïve macrophages. This study shows the potential of CERs to improve acidity within the TME and that it has the potential to be paired with existing electric field-based cancer therapies or as a stand-alone therapy.

Geography, taxonomy, extinction risk and exposure of fully migratory birds to droughts and cyclones - Rhys G. G. Preston‐Allen; Henry Häkkinen; Laura Cañellas‐Dols; Eric I. Ameca y Juarez; C. David L. Orme; Nathalie Pettorelli (Global Ecology and Biogeography, 2024)
Aim Anthropogenic climate change is predicted to drive unprecedented increases in the frequency and intensity of extreme climatic events, such as drought and cyclones. The impacts of these events on fully migratory species could be particularly severe and have cascading effects on the functioning of many ecosystems. We explore the relationships between geography, taxonomy, extinction risk and the exposure of fully migratory birds to drought and cyclones. Location Global. Time Period 1985–2014. Major Taxa Studied 383 fully migratory bird species. Methods We assessed the exposure of fully migratory birds to cyclones and droughts, quantifying exposure by calculating the percentage of spatial overlap between a species' range and the extent of an extreme event within a given time series. We compared the level of cumulative exposure sustained by species among different taxonomic groups and within their breeding and wintering ranges; we also assessed whether species currently classed as ‘threatened’ are more cumulatively exposed than ‘non‐threatened’ species. Results We identified fully migratory bird species highly exposed to extreme climatic events and global geographic hotspots of species exposure. 4% of species were found to be highly exposed to cyclones and droughts in both their wintering and breeding ranges. Wintering ranges were, on average, more cumulatively exposed to cyclones than breeding ranges; there was no discernible difference in drought exposure between ranges. Species currently classed as threatened were shown to experience higher exposure to droughts than non‐threatened ones in both ranges. Main Conclusions This exposure analysis provides the first step to a full global assessment of fully migratory bird species' vulnerability to extreme climatic events. Many species are at least as exposed to extreme events within their wintering ranges as in their breeding ranges, supporting calls for ‘full cycle’ assessment of migratory species' vulnerability to climate change. Our identification of hotspots of exposure may help to guide further monitoring, research and management.

Nitrogen deposition suppresses ephemeral post‐fire plant diversity - Justin M. Valliere; Irina C. Irvine; Edith B. Allen (Global Change Biology, 2024)
Fire is a dominant force shaping patterns of plant diversity in Mediterranean‐type ecosystems. In these biodiversity hotspots, including California's endangered coastal scrub, many species remain hidden belowground as seeds and bulbs, only to emerge and flower when sufficient rainfall occurs after wildfire. The unique adaptations possessed by these species enable survival during prolonged periods of unfavorable conditions, but their continued persistence could be threatened by nonnative plant invasion and environmental change. Furthermore, their fleeting presence aboveground makes evaluating these threats in situ a challenge. For example, nitrogen (N) deposition resulting from air pollution is a well‐recognized threat to plant diversity worldwide but impacts on fire‐following species are not well understood. We experimentally evaluated the impact of N deposition on post‐fire vegetation cover and richness for three years in stands of coastal sage scrub that had recently burned in a large wildfire in southern California. We installed plots receiving four levels of N addition that corresponded to the range of N deposition rates in the region. We assessed the impact of pre‐fire invasion status on vegetation dynamics by including plots in areas that had previously been invaded by nonnative grasses, as well as adjacent uninvaded areas. We found that N addition reduced native forb cover in the second year post‐fire while increasing the abundance of nonnative forbs. As is typical in fire‐prone ecosystems, species richness declined over the three years of the study. However, N addition hastened this process, and native forb richness was severely reduced under high N availability, especially in previously invaded shrublands. An indicator species analysis also revealed that six functionally and taxonomically diverse forb species were especially sensitive to N addition. Our results highlight a new potential mechanism for the depletion of native species through the suppression of ephemeral post‐fire bloom events.

A subsurface layer on asteroid (101955) Bennu and implications for rubble pile asteroid evolution - E.B. Bierhaus; F. Rossmann; C. Johnson; R.T. Daly; D. Golish; J. Nolau; A. Allen; H. Campins; M. Pajola; B. Rizk; C. D'Aubigny; D. DellaGiustina; et al. (Icarus, 2023)

SUCCESSFUL TRANSPLANT OF KIDNEYS AFTER VITRIFICATION AND NANOWARMING - Zonghu Han; Joseph S. Rao; Lakshya Gangwar; Bat-Erdene Namsrai; Jacqueline Pasek-Allen; Michael L. Etheridge; Erik B. Finger; John C. Bischof (Cryobiology, 2023)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Density- and size-dependent mechanisms modulate the outcome of stocking in a naturally recruiting freshwater piscivore (northern pike, Esox lucius): A replicated whole-lake experiment - Daniel Hühn; Daniel C. Gwinn; Stephanie L. Shaw; Josep Alós; Micheal S. Allen; Thilo Pagel; Christian Skov; Robert Arlinghaus (Fisheries Research, 2023)

A database of human predictive patch test data for skin sensitization - Judy Strickland; Jaleh Abedini; David G. Allen; John Gordon; Victoria Hull; Nicole C. Kleinstreuer; Hon-Sum Ko; Joanna Matheson; Hermann-Josef Thierse; James Truax; Jens T. Vanselow; Matthias Herzler (Archives of Toxicology, 2023)
Critical to the evaluation of non-animal tests are reference data with which to assess their relevance. Animal data are typically used because they are generally standardized and available. However, when regulatory agencies aim to protect human health, human reference data provide the benefit of not having to account for possible interspecies variability. To support the evaluation of non-animal approaches for skin sensitization assessment, we collected data from 2277 human predictive patch tests (HPPTs), i.e., human repeat insult patch tests and human maximization tests, for skin sensitization from 1555 publications. We recorded protocol elements and positive or negative outcomes, developed a scoring system to evaluate each test for reliability, and calculated traditional and non-traditional dose metrics. We also traced each test result back to its original report to remove duplicates. The resulting database, which contains information for 1366 unique substances, was characterized for physicochemical properties, chemical structure categories, and protein binding mechanisms. This database is publicly available on the National Toxicology Program Interagency Center for the Evaluation of Alternative Toxicological Methods website and in the Integrated Chemical Environment to serve as a resource for additional evaluation of alternative methods and development of new approach methodologies for skin sensitization assessments.

Communication in the science-policy interface: Evidence from a boundary organization in Nebraska, USA - Sechindra Vallury; Brian C. Chaffin; Samantha L. Hamlin; Craig R. Allen (Environmental Science & Policy, 2023)

Titanium and iron isotopic records of granitoid crust production in diverse Archean cratons - Zhe J. Zhang; Nicolas Dauphas; Aleisha C. Johnson; Sarah M. Aarons; Vickie C. Bennett; Allen P. Nutman; Scott MacLennan; Blair Schoene (Earth and Planetary Science Letters, 2023)

Molecular complexity and diversity of persistent soil organic matter - Andrew R. Jones; Ram C. Dalal; Vadakattu V.S.R. Gupta; Susanne Schmidt; Diane E. Allen; Geraldine E. Jacobsen; Michael Bird; A. Stuart Grandy; Jonathan Sanderman (Soil Biology and Biochemistry, 2023)

Age constraints on c. 1.9 Ga volcanism, basin evolution and mineralization at the world-class Zinkgruvan Zn-Pb-Ag(-Cu) deposit, Bergslagen, Sweden - Nils F. Jansson; Filip Simán; Rodney L. Allen; Joakim Mansfeld; Tobias C. Kampmann (Precambrian Research, 2023)

Evolution of the Palaeozoic mafic-ultramafic Lizard Complex (SW England) from zircon and baddeleyite U-Pb-Hf isotopic constraints: New thoughts on the convergence of Avalonia and Armorica - Allen P. Nutman; Vickie C. Bennett; David H. Green; Clark R.L. Friend (Lithos, 2023)

Comparison of Methemoglobin, Deoxyhemoglobin, and Ferrous Nitrosyl Hemoglobin as Potential MRI Contrast Agents - Roya Ayati; Kyle C. Manwaring; Steven P. Allen; Ronald W. Day; Randy S. Lewis (Annals of Biomedical Engineering, 2023)

A Demonstration of the Capability of Low-Cost Hyperspectral Imaging for the Characterisation of Coral Reefs - Jonathan Teague; John C. C. Day; Michael J. Allen; Thomas B. Scott; Eric J. Hochberg; David Megson-Smith (Oceans, 2023)
The use of hyperspectral imaging in marine applications is limited, largely due to the cost-prohibitive nature of the technology and the risk of submerging such expensive electronics. Here, we examine the use of low-cost (<5000 GBP) hyperspectral imaging as a potential addition to the marine monitoring toolbox. Using coral reefs in Bermuda as a case study and a trial for the technology, data was collected across two reef morphologies, representing fringing reefs and patch reefs. Hyperspectral data of various coral species, Montastraea cavernosa, Diploria labyrinthiformis, Pseudodiploria strigosa, and Plexaurella sp., were successfully captured and analyzed, indicating the practicality and suitability of underwater hyperspectral imaging for use in coral reef assessment. The spectral data was also used to demonstrate simple spectral classification to provide values of the percentage coverage of benthic habitat types. Finally, the raw image data was used to generate digital elevation models to measure the physical structure of corals, providing another data type able to be used in reef assessments. Future improvements were also suggested regarding how to improve the spectral data captured by the technique to account for the accurate application of correction algorithms.

Who benefits most from a prenatal HEPA filter air cleaner intervention on childhood cognitive development? The UGAAR randomized controlled trial - Battsetseg Ulziikhuu; Enkhjargal Gombojav; Chimeglkham Banzrai; Sarangerel Batsukh; Enkhtuul Enkhtuya; Buyantushig Boldbaatar; David C. Bellinger; Bruce P. Lanphear; Lawrence C. McCandless; Pablo Nepomnaschy; Katrina Salvante; Joanne Weinberg; et al. (Environmental Research, 2023)

Topographic information improves simulated patterns of post‐fire conifer regeneration in the southwest United States - Chang Gyo Jung; Alisa R. Keyser; Cecile C. Remy; Daniel Krofcheck; Craig D. Allen; Matthew D. Hurteau (Global Change Biology, 2023)
The western United States is projected to experience more frequent and severe wildfires in the future due to drier and hotter climate conditions, exacerbating destructive wildfire impacts on forest ecosystems such as tree mortality and unsuccessful post‐fire regeneration. While empirical studies have revealed strong relationships between topographical information and plant regeneration, ecological processes in ecosystem models have either not fully addressed topography‐mediated effects on the probability of plant regeneration, or the probability is only controlled by climate‐related factors, for example, water and light stresses. In this study, we incorporated seedling survival data based on a planting experiment in the footprint of the 2011 Las Conchas Fire into the Photosynthesis and EvapoTranspiration (PnET) extension of the LANDIS‐II model by adding topographic and an additional climatic variable to the probability of regeneration. The modified algorithm included topographic parameters such as heat load index and ground slope and spring precipitation. We ran simulations on the Las Conchas Fire landscape for 2012–2099 using observed and projected climate data (i.e., Representative Concentration Pathway 4.5 and 8.5). Our modification significantly reduced the number of regeneration events of three common southwestern conifer tree species (piñon, ponderosa pine, and Douglas‐fir), leading to decreases in aboveground biomass, regardless of climate scenario. The modified algorithm decreased regeneration at higher elevations and increased regeneration at lower elevations relative to the original algorithm. Regenerations of three species also decreased in eastern aspects. Our findings suggest that ecosystem models may overestimate post‐fire regeneration events in the southwest United States. To better represent regeneration processes following wildfire, ecosystem models need refinement to better account for the range of factors that influence tree seedling establishment. This will improve model utility for projecting the combined effects of climate and wildfire on tree species distributions.

The structural components of the Azotobacter vinelandii iron-only nitrogenase, AnfDKG, form a protein complex within the plant mitochondrial matrix - E. Johnston; S. Okada; C. M. Gregg; A. C. Warden; V. Rolland; V. Gillespie; K. Byrne; M. L. Colgrave; A. L. Eamens; R. S. Allen; C. C. Wood (Plant Molecular Biology, 2023)
A long-held goal of synthetic biology has been the transfer of a bacterial nitrogen-fixation pathway into plants to reduce the use of chemical fertiliser on crops such as rice, wheat and maize. There are three classes of bacterial nitrogenase, named after their metal requirements, containing either a MoFe-, VFe- or FeFe-cofactor, that converts N 2 gas to ammonia. Relative to the Mo-nitrogenase the Fe-nitrogenase is not as efficient for catalysis but has less complex genetic and metallocluster requirements, features that may be preferable for engineering into crops. Here we report the successful targeting of bacterial Fe-nitrogenase proteins, AnfD, AnfK, AnfG and AnfH, to plant mitochondria. When expressed as a single protein AnfD was mostly insoluble in plant mitochondria, but coexpression of AnfD with AnfK improved its solubility. Using affinity-based purification of mitochondrially expressed AnfK or AnfG we were able to demonstrate a strong interaction of AnfD with AnfK and a weaker interaction of AnfG with AnfDK. This work establishes that the structural components of the Fe-nitrogenase can be engineered into plant mitochondria and form a complex, which will be a requirement for function. This report outlines the first use of Fe-nitrogenase proteins within a plant as a preliminary step towards engineering an alternative nitrogenase into crops.

Amide- and bis-amide-linked highly potent and broadly active antifungal agents for the treatment of invasive fungal infections- towards the discovery of pre-clinical development candidate FC12406 - Simon D. P. Baugh; Anna Chaly; Damian G. Weaver; David B. Whitman; Jeffrey C. Pelletier; Haiyan Bian; Katie B. Freeman; Allen B. Reitz; Richard W. Scott (Medicinal Chemistry Research, 2023)

Effect of species‐level trait variation on urban exploitation in mammals - Katherine C. B. Weiss; Austin M. Green; Daniel J. Herrera; Tru M. Hubbard; Christine C. Rega‐Brodsky; Maximilian L. Allen (Ecology, 2023)
Identifying drivers of urban association in wildlife is a central challenge in conservation biology. Traits facilitating access to novel resources and avoiding humans often correspond with urban exploitation in mammal species, but these relationships differ by taxa and trophic guild. Variation among or within traits may be a yet untested explanation for the non‐generality of species‐trait relationships in cities. Using camera trap data from 1492 sites throughout the contiguous USA in 2019, we investigated if mammal species with greater intraspecific trait variation have higher degrees of urban occupancy. We hypothesized that intraspecific trait variation would correspond with urban occupancy, but that the strength of these relationships would vary by taxonomic order due to expected phylogenetic constraints. Mean trait values (average home range size, body mass, group size, weaning age, litter size, and diet composition) varied widely across orders. The only traits that affected urban association across all species corresponded with demography (litter size), while responses across orders were more variable and informative. Mean trait values associated with home range and body size had informative relationships with urbanization for Cetartiodactyla, Rodentia, and Carnivora, while intraspecific variation in traits corresponding with diet (Carnivora), demography (Cetartiodactyla, Carnivora, Rodentia), and temporal responses to humans (Carnivora) had informative relationships to urbanization. This is the first study investigating mammalian species‐level trait variation and its relationship to urban exploitation across many traits and taxa. Since natural selection requires trait variation, the variation of demographic traits, like litter size, can have significant implications for wildlife management and conservation. Our results also provide further evidence for omnivory as a form of dietary plasticity supporting urban accessibility in higher trophic guilds (e.g., Carnivora). Using this information, we can better manage and understand which species occupy and adapt to cities, thereby promoting human‐wildlife coexistence.

Late Cenozoic history and the role of Beringia in assembling a Holarctic cestode species complex - Kurt E. Galbreath; Arseny A. Makarikov; Kayce C. Bell; Stephen E. Greiman; Julie M. Allen; Genevieve M.S. Haas; Chenhong Li; Joseph A. Cook; Eric P. Hoberg (Molecular Phylogenetics and Evolution, 2023)

The role of Dnmt1 in oocyte development - Emily A. Shelby; Elizabeth C. McKinney; Christopher B. Cunningham; Alvin M. Simmons; Allen J. Moore; Patricia J. Moore (Journal of Insect Physiology, 2023)

A snapshot of online wildlife trade: Australian e-commerce trade of native and non-native pets - Adam Toomes; Stephanie Moncayo; Oliver C. Stringham; Charlotte Lassaline; Lisa Wood; Mariah Millington; Charlotte Drake; Charlotte Jense; Ashley Allen; Katherine G.W. Hill; Pablo García-Díaz; Lewis Mitchell; et al. (Biological Conservation, 2023)

Correction: Reading the biomineralized book of life: expanding otolith biogeochemical research and applications for fisheries and ecosystem-based management - Patrick Reis-Santos; Bronwyn M. Gillanders; Anna M. Sturrock; Christopher Izzo; Dion S. Oxman; Jessica A. Lueders-Dumont; Karin Hüssy; Susanne E. Tanner; Troy Rogers; Zoë A. Doubleday; Allen H. Andrews; Clive Trueman; et al. (Reviews in Fish Biology and Fisheries, 2023)

Reading the biomineralized book of life: expanding otolith biogeochemical research and applications for fisheries and ecosystem-based management - Patrick Reis-Santos; Bronwyn M. Gillanders; Anna M. Sturrock; Christopher Izzo; Dion S. Oxman; Jessica A. Lueders-Dumont; Karin Hüssy; Susanne E. Tanner; Troy Rogers; Zoë A. Doubleday; Allen H. Andrews; Clive Trueman; et al. (Reviews in Fish Biology and Fisheries, 2023)
Chemical analysis of calcified structures continues to flourish, as analytical and technological advances enable researchers to tap into trace elements and isotopes taken up in otoliths and other archival tissues at ever greater resolution. Increasingly, these tracers are applied to refine age estimation and interpretation, and to chronicle responses to environmental stressors, linking these to ecological, physiological, and life-history processes. Here, we review emerging approaches and innovative research directions in otolith chemistry, as well as in the chemistry of other archival tissues, outlining their value for fisheries and ecosystem-based management, turning the spotlight on areas where such biomarkers can support decision making. We summarise recent milestones and the challenges that lie ahead to using otoliths and archival tissues as biomarkers, grouped into seven, rapidly expanding and application-oriented research areas that apply chemical analysis in a variety of contexts, namely: (1) supporting fish age estimation; (2) evaluating environmental stress, ecophysiology and individual performance; (3) confirming seafood provenance; (4) resolving connectivity and movement pathways; (5) characterising food webs and trophic interactions; (6) reconstructing reproductive life histories; and (7) tracing stock enhancement efforts. Emerging research directions that apply hard part chemistry to combat seafood fraud, quantify past food webs, as well as to reconcile growth, movement, thermal, metabolic, stress and reproductive life-histories provide opportunities to examine how harvesting and global change impact fish health and fisheries productivity. Ultimately, improved appreciation of the many practical benefits of archival tissue chemistry to fisheries and ecosystem-based management will support their increased implementation into routine monitoring. Graphical abstract

Determination of specific lethal heat treatment parameters for pests associated with wood products using the Humble water bath - M. K. Noseworthy; L. M. Humble; T. J. Souque; E. P. John; J. Roberts; C. R. Lloyd; E. A. Allen (Journal of Pest Science, 2023)
Heat treatment is an effective sanitization method used for over half a century to reduce the risk of transporting pests associated with wood products. The determination of precise lethal heat treatment parameters for pests is critical for the development of globally harmonized plant protection regulatory treatment policies. Separation of heat treatment dose (time and temperature) from the factors associated with the method of heat application (delivery) and variables associated with wood characteristics allows for universal agreement on lethal dose and promotes efficient development of treatment schedule guidance. The Humble water bath is an effective and carefully calibrated heat treatment apparatus designed to test the effects of heat and determine lethal temperature doses. Specifications for building this apparatus and experimental treatment parameters are described. To demonstrate the capacities of the water bath apparatus, the effect of heat on a non-indigenous wood-boring beetle, Anisandrus dispar, is reported using heat-ramp schedules similar to industrial kiln heating applications. Adult A. dispar tested in vitro, did not survive 50 °C treatment temperature for 15 min time duration.

Optimization of 4D Flow MRI Spatial and Temporal Resolution for Examining Complex Hemodynamics in the Carotid Artery Bifurcation - Retta El Sayed; Alireza Sharifi; Charlie C. Park; Diogo C. Haussen; Jason W. Allen; John N. Oshinski (Cardiovascular Engineering and Technology, 2023)

Electric dipole scattering from a finitely conducting cylinder - Allen Q. Howard; Diego C. Miranda (Journal of Applied Geophysics, 2023)

Abundance patterns of mammals across Russia explained by remotely sensed vegetation productivity and snow indices - Elena Razenkova; Maxim Dubinin; Anna M. Pidgeon; Martina L. Hobi; Likai Zhu; Eugenia V. Bragina; Andrew M. Allen; Murray K. Clayton; Leonid M. Baskin; Nicholas C. Coops; Volker C. Radeloff (Journal of Biogeography, 2023)
Aim Predicting biodiversity responses to global changes requires good models of species' distributions. Both environmental conditions and human activities determine population density patterns. However, quantifying the relationship between wildlife population densities and their underlying environmental conditions across large geographical scales has remained challenging. Our goal was to explain the abundances of mammal species based on their response to several remotely sensed indices including the Dynamic Habitat Indices (DHIs) and the novel Winter Habitat Indices (WHIs). Location Russia, the majority of regions. Taxon Eight mammal species. Methods We estimated average population densities for each species across Russia from 1981 to 2010 from winter track counts. The DHIs measure vegetative productivity, a proxy for food availability. Our WHIs included the duration of snow‐free ground, duration of snow‐covered ground and the start, end and length of frozen season. In models, we included elevation, climate conditions, human footprint index. We parameterized multiple linear regression and applied best‐subset model selection to determine the main factors influencing population density. Results The DHIs were included in some of the top‐twelve models of every species, and in the top model for moose, wild boar, red fox and wolf, so they were important for species at all trophic levels. The WHIs were included in top models for all species except roe deer, demonstrating the importance of winter conditions. The duration of frozen ground without snow and the end of frozen season were particularly important. Our top models performed well for all the species ( R 2 adj 0.43–0.87). Main Conclusions The combination of the DHIs and the WHIs with climate and human‐related variables resulted in high explanatory power. We show that vegetation productivity and winter conditions are key drivers of variation in population density of eight species across Russia.

Oyster aquaculture cages provide fish habitat similar to natural structure with minimal differences based on farm location - Renee Mercaldo-Allen; Peter J. Auster; Paul Clark; Mark S. Dixon; Erick Estela; Yuan Liu; Lisa Milke; Gillian Phillips; Dylan Redman; Barry C. Smith; Alison Verkade; Julie M. Rose (Frontiers in Marine Science, 2023)
Oyster aquaculture gear may augment natural seafloor by providing structured habitat for economically important fish species. Underwater video census was used to assess fish abundance and community composition on eastern oyster ( Crassostrea virginica ) shelf and bag style aquaculture off-bottom cages and within natural rock reef habitat. During 2018, underwater cameras were mounted on four study cages at a dense shellfish farm of 40-100 commercial cages (dense cage farm), on four single cages interspersed on low relief seafloor (sparse cage farm), and amongst four boulders on a rock reef (rock reef), within an embayment off Milford, Connecticut, which is part of Long Island Sound, in the United States. In 2019, cameras were similarly deployed on two study cages per farm at each of three shellfish farms off Milford, Norwalk and Westport, CT. Video was recorded hourly in eight-minute segments from 7 am to 7 pm. Data loggers monitored seawater temperature, light intensity, and current speed. Fish abundance (MaxN) was calculated for all videos. We compared fish abundance and community composition between May and September, on cage and boulder habitat, on cages at dense and sparse farms and on cages across farm locations. In 2018, abundance of black sea bass ( Centropristis striata ), scup ( Stenotomus chrysops ) and tautog ( Tautoga onitis ) was significantly higher on cages than boulders, regardless of cage number. Cunner ( Tautogolabrus adspersus ) abundance was significantly higher on boulders than cages when cage sites were grouped. However pairwise comparisons indicated that cunner were significantly higher at the sparse cage farm versus the rock reef but cunner abundance on the dense cage farm and rock reef sites was not significantly different. Abundance of black sea bass, scup, tautog, and cunner were not significantly different across 2019 farm locations. Young-of-the-year fish occurred episodically at all sites during both years, with black sea bass and scup most abundant. Fish abundance corresponded to seasonal changes in seawater temperature and was highest at the warmest temperatures. Light intensity and current speed explained less variation in fish abundance relative to temperature, and relationships were inconsistent across habitats and farm locations Our results suggest that multi-tiered oyster aquaculture cages contribute structure to seafloor environments that provide habitat for temperate reef fish similar to natural rock reefs.

Mammalian functional diversity and trait responses to anthropogenic and environmental factors across the contiguous USA - Christine C. Rega-Brodsky; Katherine C. B. Weiss; Austin M. Green; Fabiola Iannarilli; Jacquelyn Tleimat; Sarah Fritts; Daniel J. Herrera; M. Caitlin Fisher-Reid; Justin A. Compton; Diana J. R. Lafferty; Maximilian L. Allen (Urban Ecosystems, 2023)

Development of a Benchmark Eddy Flux Evapotranspiration Dataset for Evaluation of Satellite-Driven Evapotranspiration Models Over the CONUS - John M. Volk; Justin Huntington; Forrest S. Melton; Richard Allen; Martha C. Anderson; Joshua B. Fisher; Ayse Kilic; Gabriel Senay; Gregory Halverson; Kyle Knipper; Blake Minor; Christopher Pearson; et al. (Agricultural and Forest Meteorology, 2023)

The air quality impacts of pre-operational hydraulic fracturing activities - Shona E. Wilde; James R. Hopkins; Alastair C. Lewis; Rachel E. Dunmore; Grant Allen; Joseph R. Pitt; Robert S. Ward; Ruth M. Purvis (Science of The Total Environment, 2023)

Differential cardiopulmonary effects of isoprene-versus toluene-generated photochemically-Aged smog in rats - Samantha J. Snow; Jonathan D. Krug; John M. Turlington; Judy E. Richards; Mette C. Schladweiler; Allen D. Ledbetter; Todd Krantz; Charly King; M. Ian Gilmour; Stephen H. Gavett; Urmila P. Kodavanti; Aimen K. Farraj; et al. (Atmospheric Environment, 2023)

Late Pleistocene Glacial-Paleosol-cosmic record of the Viso Massif—France and Italy: New evidence in support of the Younger Dryas boundary (12.8 ka) - William C. Mahaney; Peeter Somelar; Christopher C. R. Allen (International Journal of Earth Sciences, 2023)

Understanding heterogeneity of responses to, and optimizing clinical efficacy of, exercise training in older adults: NIH NIA Workshop summary - Melissa L. Erickson; Jacob M. Allen; Daniel P. Beavers; Linda M. Collins; Karina W. Davidson; Kirk I. Erickson; Karyn A. Esser; Matthijs K. C. Hesselink; Kerrie L. Moreau; Eric B. Laber; Charlotte A. Peterson; Courtney M. Peterson; et al. (GeroScience, 2023)
Exercise is a cornerstone of preventive medicine and a promising strategy to intervene on the biology of aging. Variation in the response to exercise is a widely accepted concept that dates back to the 1980s with classic genetic studies identifying sequence variations as modifiers of the VO 2 max response to training. Since that time, the literature of exercise response variance has been populated with retrospective analyses of existing datasets that are limited by a lack of statistical power from technical error of the measurements and small sample sizes, as well as diffuse outcomes, very few of which have included older adults. Prospective studies that are appropriately designed to interrogate exercise response variation in key outcomes identified a priori and inclusive of individuals over the age of 70 are long overdue. Understanding the underlying intrinsic (e.g., genetics and epigenetics) and extrinsic (e.g., medication use, diet, chronic disease) factors that determine robust versus poor responses to various exercise factors will be used to improve exercise prescription to target the pillars of aging and optimize the clinical efficacy of exercise training in older adults. This review summarizes the proceedings of the NIA-sponsored workshop entitled, “Understanding Heterogeneity of Responses to, and Optimizing Clinical Efficacy of, Exercise Training in Older Adults” and highlights the importance and current state of exercise response variation research, particularly in older adults, prevailing challenges, and future directions.

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Heterogeneity in diagnostic characters across ecoregions: A case study with Botrynema (Hydrozoa: Trachylina: Halicreatidae) - Javier Montenegro; Allen G. Collins; Russell R. Hopcroft; Jennifer M. Questel; Erik V. Thuesen; Tiffany S. Bachtel; Leah A. Bergman; Mehul N. Sangekar; Jeffrey C. Drazen; Dhugal J. Lindsay (Frontiers in Marine Science, 2023)
Introduction Botrynema, a genus of medusozoans in the trachyline family Halicreatidae, currently contains two species: B. brucei and B. ellinorae , distinguished by the presence or absence, respectively, of an apical knob as a diagnostic character. However, no study has corroborated if these taxonomic diagnoses have a biological and evolutionary basis. Therefore, in this study we attempted to address the question “do the two nominal species in the genus Botrynema represent independent phylogenetic lineages, or two phenotypic variants of a single species? Methods In this study we took advantage of legacy collections from different research expeditions across the globe from 2000 to 2021 to study the phylogenetics and taxonomy of the genus Botrynema. Results B. brucei and B. ellinorae present partially overlapping vertical distributions in the Arctic and as a whole in the Arctic the genus seems to be limited to the Atlantic water masses. The phylogenetic reconstruction based on the concatenated alignment corroborates the validity of the family Halicreatidae and of genus Botrynema as monophyletic groups. However no clear differentiation was found between the two presently accepted species, B. ellinorae and B. brucei . Discussion Based on the evidence we gathered, we conclude that while the genus Botrynema does contain at least two species lineages, these lineages are not concordant with current species definitions. The species B. ellinorae is reassigned as a subspecies of B. brucei and diagnostic characters are provided.

Identifying the midline thalamus in humans in vivo - Puck C. Reeders; M. Vanessa Rivera Núñez; Robert P. Vertes; Aaron T. Mattfeld; Timothy A. Allen (Brain Structure and Function, 2023)

Toxicity comparison of atrazine on Eisenia fetida in artificial soil and three natural soils - Xiaoying Li; Yue Yang; Ruolin Wu; Kaixuan Hou; Samuel C. Allen; Lusheng Zhu; Zhongkun Du; Bing Li; Jinhua Wang; Jun Wang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Identification of amino acid residues in a proton release pathway near the bacteriochlorophyll dimer in reaction centers from Rhodobacter sphaeroides - J. P. Allen; K. D. Chamberlain; J. C. Williams (Photosynthesis Research, 2023)

Cover Image - Rachel N. Hofer; Allen Lin; Benjamin C. House; Christopher N. Purvis; Bradley J. Harris; Steven J. K. Symes; David K. Giles (Journal of Fish Diseases, 2023)

Exogenous polyunsaturated fatty acids ( PUFAs ) influence permeability, antimicrobial peptide resistance, biofilm formation and membrane phospholipid structure in an A‐layer and non‐A ‐layer strain of Aeromonas salmonicida - Rachel N. Hofer; Allen Lin; Benjamin C. House; Christopher N. Purvis; Bradley J. Harris; Steven J. K. Symes; David K. Giles (Journal of Fish Diseases, 2023)
Aeromonas salmonicida is a Gram‐negative bacterium that can infect a wide host range of fish populations, including salmonids and non‐salmonids as well as freshwater and marine life. Some strains of A. salmonicida cause the disease furunculosis, which can cause lethargy, intestinal inflammation, ulcers, haemorrhaging and death. The infection is spread through fish‐to‐fish contact, and the presence of infection can have devastating effects on cultivated fish populations. The purpose of this study was to explore the ability of non‐A‐layer and A‐layer A. salmonicida strains to incorporate polyunsaturated fatty acids (PUFAs) into their lipid profile and test the phenotypic effects thereof. Lipids were extracted from PUFA‐exposed cultures and analysed for lipid modification by thin‐layer chromatography and ultraperformance liquid chromatography‐mass spectrometry, showing A. salmonicida , regardless of A‐layer, capable of incorporating all seven of the PUFAs studied. Phenotypic effects were determined through the use of assays that tested for biofilm formation, membrane permeability and cyclic peptide susceptibility. Temperature‐dependent effects on biofilm formation were observed, and PUFA exposure showed significant ( p

Demographic reporting across a decade of neuroimaging: a systematic review - Elijah Sterling; Hannah Pearl; Zexuan Liu; Jason W. Allen; Candace C. Fleischer (Brain Imaging and Behavior, 2022)
Diversity of participants in biomedical research with respect to race, ethnicity, and biological sex is crucial, particularly given differences in disease prevalence, recovery, and survival rates between demographic groups. The objective of this systematic review was to report on the demographics of neuroimaging studies using magnetic resonance imaging (MRI). The Web of Science database was used and data collection was performed between June 2021 to November 2021; all articles were reviewed independently by at least two researchers. Articles utilizing MR data acquired in the United States, with n ≥ 10 human subjects, and published between 2010–2020 were included. Non-primary research articles and those published in journals that did not meet a quality control check were excluded. Of the 408 studies meeting inclusion criteria, approximately 77% report sex, 10% report race, and 4% report ethnicity. Demographic reporting also varied as function of disease studied, participant age range, funding, and publisher. We anticipate quantitative data on the extent, or lack, of reporting will be necessary to ensure inclusion of diverse populations in biomedical research.

Combining surface and soil environmental DNA with artificial cover objects to improve terrestrial reptile survey detection - Kathleen E. Kyle; Michael C. Allen; Jeffrey Dragon; John F. Bunnell; Howard K. Reinert; Robert Zappalorti; Benjamin D. Jaffe; Jordan C. Angle; Julie L. Lockwood (Conservation Biology, 2022)
Reptiles are increasingly of conservation concern due to their susceptibility to habitat loss, emerging disease, and harvest in the wildlife trade. However, reptile populations are often difficult to monitor given the frequency of crypsis in their life history. This difficulty has left uncertain the conservation status of many species and the efficacy of conservation actions unknown. Environmental DNA (eDNA) surveys consistently elevate the detection rate of species they are designed to monitor, and while their use is promising for terrestrial reptile conservation, successes in developing such surveys have been sparse. We tested the degree to which inclusion of surface and soil eDNA sampling into conventional artificial‐cover methods elevates the detection probability of a small, cryptic terrestrial lizard, Scincella lateralis . The eDNA sampling of cover object surfaces with paint rollers elevated per sample detection probabilities for this species 4–16 times compared with visual surveys alone. We readily detected S. lateralis eDNA under cover objects up to 2 weeks after the last visual detection, and at some cover objects where no S. lateralis were visually observed in prior months. With sufficient sampling intensity, eDNA testing of soil under cover objects produced comparable per sample detection probabilities as roller surface methods. Our results suggest that combining eDNA and cover object methods can considerably increase the detection power of reptile monitoring programs, allowing more accurate estimates of population size, detection of temporal and spatial changes in habitat use, and tracking success of restoration efforts. Further research into the deposition and decay rates of reptile eDNA under cover objects, as well as tailored protocols for different species and habitats, is needed to bring the technique into widespread use.

Using Colour as a Marker for Coral ‘Health’: A Study on Hyperspectral Reflectance and Fluorescence Imaging of Thermally Induced Coral Bleaching - Jonathan Teague; Jack Willans; David A. Megson-Smith; John C. C. Day; Michael J. Allen; Thomas B. Scott (Oceans, 2022)
Rising oceanic temperatures create more frequent coral bleaching events worldwide and as such there exists a need for rapid, non-destructive survey techniques to gather greater and higher definition information than that offered by traditional spectral based monitoring systems. Here, we examine thermally induced laboratory bleaching of Montipora capricornis and Montipora confusa samples, utilising hyperspectral data to gain an understanding of coral bleaching from a spectral standpoint. The data revealed several characteristic spectral peaks that can be used to make health determinations. The fluorescence peaks are attributed to fluorescent proteins (FPs) and Chlorophyll-a fluorescence. The reflectance peaks can be attributed to Chlorophyll absorption and accessory pigments such as Peridinin and Diadinoxanthin. Each characteristic spectral peak or ‘marker’ allows for observation of each aspect of coral health and hence, simultaneous monitoring of these markers using hyperspectral imaging techniques provides an opportunity to better understand the processes occurring during bleaching and the rates at which they occur relative to one another.

Novelty-induced locomotor behavior predicts heroin addiction vulnerability in male, but not female, rats - Brittany N. Kuhn; Nazzareno Cannella; Ayteria D. Crow; Analyse T. Roberts; Veronica Lunerti; Carter Allen; Rusty W. Nall; Gary Hardiman; Leah C. Solberg Woods; Dongjun Chung; Roberto Ciccocioppo; Peter W. Kalivas (Psychopharmacology, 2022)

A novel method for identifying coded tags recorded on aquatic acoustic monitoring systems - Christopher D. Lowe; Nicolas J. C. Tregenza; Claudia J. Allen; Georgina E. Blow; Hanna Nuuttila; Chiara M. Bertelli; Anouska F. Mendzil; Thomas Stamp; Emma V. Sheehan; Peter Davies; Jonathan C. D. Gordon; Jonathan D. Bolland; et al. (Environmental Monitoring and Assessment, 2022)
Aquatic biotelemetry increasingly relies on using acoustic transmitters (‘tags’) that enable passive detection of tagged animals using fixed or mobile receivers. Both tracking methods are resource-limited, restricting the spatial area in which movements of highly mobile animals can be measured using proprietary detection systems. Transmissions from tags are recorded by underwater noise monitoring systems designed for other purposes, such as cetacean monitoring devices, which have been widely deployed in the marine environment; however, no tools currently exist to decode these detections, and thus valuable additional information on animal movements may be missed. Here, we describe simple hybrid methods, with potentially wide application, for obtaining information from otherwise unused data sources. The methods were developed using data from moored, acoustic cetacean detectors (C-PODs) and towed passive receiver arrays, often deployed to monitor the vocalisations of cetaceans, but any similarly formatted data source could be used. The method was applied to decode tag detections that were found to have come from two highly mobile fish species, bass ( Dicentrarchus labrax ) and Twaite shad ( Alosa fallax ), that had been tagged in other studies. Decoding results were validated using test tags; range testing data were used to demonstrate the relative efficiency of these receiver methods in detecting tags. This approach broadens the range of equipment from which acoustic tag detections can be decoded. Novel detections derived from the method could add significant value to past and present tracking studies at little additional cost, by providing new insights into the movement of mobile animals at sea.

Illuminating the dark metabolome of Pseudo‐nitzschia –microbiome associations - Irina Koester; Zachary A. Quinlan; Louis‐Félix Nothias; Margot E. White; Ariel Rabines; Daniel Petras; John K. Brunson; Kai Dührkop; Marcus Ludwig; Sebastian Böcker; Farooq Azam; Andrew E. Allen; et al. (Environmental Microbiology, 2022)
The exchange of metabolites mediates algal and bacterial interactions that maintain ecosystem function. Yet, while thousands of metabolites are produced, only a few molecules have been identified in these associations. Using the ubiquitous microalgae Pseudo‐nitzschia sp., as a model, we employed an untargeted metabolomics strategy to assign structural characteristics to the metabolites that distinguished specific diatom‐microbiome associations. We cultured five species of Pseudo‐nitzschia , including two species that produced the toxin domoic acid, and examined their microbiomes and metabolomes. A total of 4826 molecular features were detected by tandem mass spectrometry. Only 229 of these could be annotated using available mass spectral libraries, but by applying new in silico annotation tools, characterization was expanded to 2710 features. The metabolomes of the Pseudo‐nitzschia ‐microbiome associations were distinct and distinguished by structurally diverse nitrogen compounds, ranging from simple amines and amides to cyclic compounds such as imidazoles, pyrrolidines and lactams. By illuminating the dark metabolomes, this study expands our capacity to discover new chemical targets that facilitate microbial partnerships and uncovers the chemical diversity that underpins algae‐bacteria interactions.

Biochemical and clinical studies of putative allergens to assess what distinguishes them from other non-allergenic proteins in the same family - Kevin C. Glenn; Andre Silvanovich; Soon Goo Lee; Aron Allen; Stephanie Park; S. Eliza Dunn; Colton Kessenich; Chen Meng; John L. Vicini; Joseph M. Jez (Transgenic Research, 2022)
Many protein families have numerous members listed in databases as allergens; however, some allergen database entries, herein called “orphan allergens”, are members of large families of which all other members are not allergens. These orphan allergens provide an opportunity to assess whether specific structural features render a protein allergenic. Three orphan allergens [ Cladosporium herbarum aldehyde dehydrogenase (ChALDH), Alternaria alternata ALDH (AaALDH), and C. herbarum mannitol dehydrogenase (ChMDH)] were recombinantly produced and purified for structure characterization and for clinical skin prick testing (SPT) in mold allergic participants. Examination of the X-ray crystal structures of ChALDH and ChMDH and a homology structure model of AaALDH did not identify any discernable epitopes that distinguish these putative orphan allergens from their non-allergenic protein relatives. SPT results were aligned with ChMDH being an allergen, 53% of the participants were SPT (+). AaALDH did not elicit SPT reactivity above control proteins not in allergen databases (i.e., Psedomonas syringae indole-3-acetaldehyde dehydrogenase and Zea mays ALDH). Although published results showed consequential human IgE reactivity with ChALDH, no SPT reactivity was observed in this study. With only one of these three orphan allergens, ChMDH, eliciting SPT(+) reactions consistent with the protein being included in allergen databases, this underscores the complicated nature of how bioinformatics is used to assess the potential allergenicity of food proteins that could be newly added to human diets and, when needed, the subsequent clinical testing of that bioinformatic assessment. Trial registration number and date of registration AAC-2017-0467, approved as WIRB protocol #20172536 on 07DEC2017 by WIRB-Copernicus (OHRP/FDA Registration #: IRB00000533, organization #: IORG0000432).

Gene expression underlying parenting and being parented shows limited plasticity in response to different ambient temperatures - Jeanette B. Moss; Christopher B. Cunningham; Elizabeth C. McKinney; Allen J. Moore (Molecular Ecology, 2022)
Flexible interactions between parents and offspring are essential for buffering families against variable, unpredictable, and challenging environmental conditions. In the subsocial carrion beetle, Nicrophorus orbicollis , mid‐summer temperatures impose steep fitness costs on parents and offspring but do not elicit behavioural plasticity in parents. Here, we ask if plasticity of gene expression underpins this behavioural stability or facilitates independent compensation by larvae. To test this, we characterized gene expression of parents and offspring before and during active parenting under benign (20°C) and stressful (24°C) temperatures to identify genes of parents and offspring associated with thermal response, parenting/being parented, and gene expression plasticity associated with behavioural stability of parental care. The main effects of thermal and social condition each shaped patterns of gene expression in females, males, and larvae. In addition, we implicated 79 genes in females as “buffering” parental behaviour across environments. The majority of these underwent significant changes in expression in actively parenting mothers at the benign temperature, but not at the stressful temperature. Our results suggest that neither genetic programmes for parenting nor their effects on offspring gene expression are fundamentally different under stressful conditions, and that behavioural stability is associated primarily with the maintenance of existing genetic programmes rather than replacement or supplementation. Thus, while selection for compensatory gene expression could expand the range of thermal conditions parents will tolerate, without expanding the toolkit of genes involved selection is unlikely to lead to adaptive changes of function.

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Association patterns and community structure among female bottlenose dolphins: environmental, genetic and cultural factors - Svenja M. Marfurt; Simon J. Allen; Manuela R. Bizzozzero; Erik P. Willems; Stephanie L. King; Richard C. Connor; Anna M. Kopps; Sonja Wild; Livia Gerber; Samuel Wittwer; Michael Krützen (Mammalian Biology, 2022)
Social structuring from assortative associations may affect individual fitness, as well as population-level processes. Gaining a broader understanding of social structure can improve our knowledge of social evolution and inform wildlife conservation. We investigated association patterns and community structure of female Indo-Pacific bottlenose dolphins ( Tursiops aduncus ) in Shark Bay, Western Australia, assessing the role of kinship, shared culturally transmitted foraging techniques, and habitat similarity based on water depth. Our results indicated that associations are influenced by a combination of uni- and biparental relatedness, cultural behaviour and habitat similarity, as these were positively correlated with a measure of dyadic association. These findings were matched in a community level analysis. Members of the same communities overwhelmingly shared the same habitat and foraging techniques, demonstrating a strong homophilic tendency. Both uni- and biparental relatedness between dyads were higher within than between communities. Our results illustrate that intraspecific variation in sociality in bottlenose dolphins is influenced by a complex combination of genetic, cultural, and environmental aspects.

The physiological basis underlying functional connectivity differences in older adults: A multi-modal analysis of resting-state fMRI - Allen A. Champagne; Nicole S. Coverdale; Matti D. Allen; Joshua C. Tremblay; Rebecca E. K. MacPherson; Kyra E. Pyke; T. Dylan Olver; Douglas J. Cook (Brain Imaging and Behavior, 2022)

A global synthesis of human impacts on the multifunctionality of streams and rivers - Mario Brauns; Daniel C. Allen; Iola G. Boëchat; Wyatt F. Cross; Verónica Ferreira; Daniel Graeber; Christopher J. Patrick; Marc Peipoch; Daniel von Schiller; Björn Gücker (Global Change Biology, 2022)
Human impacts, particularly nutrient pollution and land‐use change, have caused significant declines in the quality and quantity of freshwater resources. Most global assessments have concentrated on species diversity and composition, but effects on the multifunctionality of streams and rivers remain unclear. Here, we analyse the most comprehensive compilation of stream ecosystem functions to date to provide an overview of the responses of nutrient uptake, leaf litter decomposition, ecosystem productivity, and food web complexity to six globally pervasive human stressors. We show that human stressors inhibited ecosystem functioning for most stressor‐function pairs. Nitrate uptake efficiency was most affected and was inhibited by 347% due to agriculture. However, concomitant negative and positive effects were common even within a given stressor‐function pair. Some part of this variability in effect direction could be explained by the structural heterogeneity of the landscape and latitudinal position of the streams. Ranking human stressors by their absolute effects on ecosystem multifunctionality revealed significant effects for all studied stressors, with wastewater effluents (194%), agriculture (148%), and urban land use (137%) having the strongest effects. Our results demonstrate that we are at risk of losing the functional backbone of streams and rivers if human stressors persist in contemporary intensity, and that freshwaters are losing critical ecosystem services that humans rely on. We advocate for more studies on the effects of multiple stressors on ecosystem multifunctionality to improve the functional understanding of human impacts. Finally, freshwater management must shift its focus toward an ecological function‐based approach and needs to develop strategies for maintaining or restoring ecosystem functioning of streams and rivers.

Competitive release during fire succession influences ecological turnover in a small mammal community - Addison G. Allen; Zachary P. Roehrs; R. Scott Seville; Hayley C. Lanier (Ecology, 2022)
Ecologists have long debated the relative importance of biotic interactions versus species‐specific habitat preferences in shaping patterns of ecological dominance. In western North America, cycles of fire disturbance are marked by transitions between North American deermice ( Peromyscus maniculatus ), which predominate after wildfires, and southern red‐backed voles ( Myodes gapperi ), which gradually replace deermice 3–4 years postfire and maintain dominance as forests mature. While this shift has been frequently documented, the processes that mediate this turnover are debated. One possibility is competitive release, which predicts a reduction in vole competition may contribute to niche expansion and population growth in deermice. Alternatively, turnover in both species may be shaped by differences in their preferred habitat and resource base, as predicted by optimum foraging theory. We evaluate these hypotheses using stable isotopes and spatial mark–recapture of deermouse and vole populations sampled prior to and following a fire as part of a longitudinal study in the Greater Yellowstone Ecosystem. Fire disturbance was associated with a 94% decrease in vole abundance but a 102% increase in deermice. Even after accounting for microhabitat, vole and deermouse populations were negatively correlated spatially and temporally ( R = −0.45), and competitor abundance was more important prefire than postfire. When vole abundance was high (prefire), vole dietary niche space was seven times broader than that of deermice. Postfire, deermouse dietary niche nearly tripled and was enriched in 13 C (i.e., more C 4 plants), while voles occupied a slightly reduced dietary niche (79% of prefire breadth). Our results suggest deermice are experiencing ecological release due to a reduction in vole competition but vole shifts are largely driven by habitat preferences.

A stochastic model for estimating sustainable limits to wildlife mortality in a changing world - Oliver Manlik; Robert C. Lacy; William B. Sherwin; Hugh Finn; Neil R. Loneragan; Simon J. Allen (Conservation Biology, 2022)
Human‐caused mortality of wildlife is a pervasive threat to biodiversity. Assessing the population‐level impact of fisheries bycatch and other human‐caused mortality of wildlife has typically relied upon deterministic methods. However, population declines are often accelerated by stochastic factors that are not accounted for in such conventional methods. Building on the widely applied potential biological removal (PBR) equation, we devised a new population modeling approach for estimating sustainable limits to human‐caused mortality and applied it in a case study of bottlenose dolphins affected by capture in an Australian demersal otter trawl fishery. Our approach, termed sustainable anthropogenic mortality in stochastic environments (SAMSE), incorporates environmental and demographic stochasticity, including the dependency of offspring on their mothers. The SAMSE limit is the maximum number of individuals that can be removed without causing negative stochastic population growth. We calculated a PBR of 16.2 dolphins per year based on the best abundance estimate available. In contrast, the SAMSE model indicated that only 2.3–8.0 dolphins could be removed annually without causing a population decline in a stochastic environment. These results suggest that reported bycatch rates are unsustainable in the long term, unless reproductive rates are consistently higher than average. The difference between the deterministic PBR calculation and the SAMSE limits showed that deterministic approaches may underestimate the true impact of human‐caused mortality of wildlife. This highlights the importance of integrating stochasticity when evaluating the impact of bycatch or other human‐caused mortality on wildlife, such as hunting, lethal control measures, and wind turbine collisions. Although population viability analysis (PVA) has been used to evaluate the impact of human‐caused mortality, SAMSE represents a novel PVA framework that incorporates stochasticity for estimating acceptable levels of human‐caused mortality. It offers a broadly applicable, stochastic addition to the demographic toolbox to evaluate the impact of human‐caused mortality on wildlife.

Predicting Seabird Foraging Habitat for Conservation Planning in Atlantic Canada: Integrating Telemetry and Survey Data Across Thousands of Colonies - Robert A. Ronconi; David J. Lieske; Laura A. McFarlane Tranquilla; Sue Abbott; Karel A. Allard; Brad Allen; Amie L. Black; François Bolduc; Gail K. Davoren; Antony W. Diamond; David A. Fifield; Stefan Garthe; et al. (Frontiers in Marine Science, 2022)
Conservation of mobile organisms is difficult in the absence of detailed information about movement and habitat use. While the miniaturization of tracking devices has eased the collection of such information, it remains logistically and financially difficult to track a wide range of species across a large geographic scale. Predictive distribution models can be used to fill this gap by integrating both telemetry and census data to construct distribution maps and inform conservation goals and planning. We used tracking data from 520 individuals of 14 seabird species in Atlantic Canada to first compare foraging range and distance to shorelines among species across colonies, and then developed tree-based machine-learning models to predict foraging distributions for more than 5000 breeding sites distributed along more than 5000 km of shoreline. Despite large variability in foraging ranges among species, tracking data revealed clusters of species using similar foraging habitats (e.g., nearshore vs. offshore foragers), and within species, foraging range was highly colony-specific. Even with this variability, distance from the nesting colony was an important predictor of distribution for nearly all species, while distance from coastlines and bathymetry (slope and ruggedness) were additional important predictors for some species. Overall, we demonstrated the utility of tree-based machine-learning approach when modeling tracking data to predict distributions at un-sampled colonies. Although tracking and colony data have some shortcomings (e.g., fewer data for some species), where results need to be interpreted with care in some cases, applying methods for modeling breeding season distributions of seabirds allows for broader-scale conservation assessment. The modeled distributions can be used in decisions about planning for offshore recreation and commercial activities and to inform conservation planning at regional scales.

Functional and transcriptional profiling of microglial activation during the chronic phase of TBI identifies an age-related driver of poor outcome in old mice - Rodney M. Ritzel; Yun Li; Zhuofan Lei; Jordan Carter; Junyun He; Harry M. C. Choi; Niaz Khan; Hui Li; Samantha Allen; Marta M. Lipinski; Alan I. Faden; Junfang Wu (GeroScience, 2022)
Elderly patients with traumatic brain injury (TBI) have greater mortality and poorer outcomes than younger individuals. The extent to which old age alters long-term recovery and chronic microglial activation after TBI is unknown, and evidence for therapeutic efficacy in aged mice is sorely lacking. The present study sought to identify potential inflammatory mechanisms underlying age-related outcomes late after TBI. Controlled cortical impact was used to induce moderate TBI in young and old male C57BL/6 mice. At 12 weeks post-injury, aged mice exhibited higher mortality, poorer functional outcomes, larger lesion volumes, and increased microglial activation. Transcriptomic analysis identified age- and TBI-specific gene changes consistent with a disease-associated microglial signature in the chronically injured brain, including those involved with complement, phagocytosis, and autophagy pathways. Dysregulation of phagocytic and autophagic function in microglia was accompanied by increased neuroinflammation in old mice. As proof-of-principle that these pathways have functional importance, we administered an autophagic enhancer, trehalose, in drinking water continuously for 8 weeks after TBI. Old mice treated with trehalose showed enhanced functional recovery and reduced microglial activation late after TBI compared to the sucrose control group. Our data indicate that microglia undergo chronic changes in autophagic regulation with both normal aging and TBI that are associated with poorer functional outcome. Enhancing autophagy may therefore be a promising clinical therapeutic strategy for TBI, especially in older patients.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Mapping the Shoreface of Coastal Sediment Compartments to Improve Shoreline Change Forecasts in New South Wales, Australia - M. A. Kinsela; D. J. Hanslow; R. C. Carvalho; M. Linklater; T. C. Ingleton; B. D. Morris; K. M. Allen; M. D. Sutherland; C. D. Woodroffe (Estuaries and Coasts, 2022)
The potential response of shoreface depositional environments to sea level rise over the present century and beyond remains poorly understood. The shoreface is shaped by wave action across a sedimentary seabed and may aggrade or deflate depending on the balance between time-averaged wave energy and the availability and character of sediment, within the context of the inherited geological control. For embayed and accommodation-dominated coastal settings, where shoreline change is particularly sensitive to cross-shore sediment transport, whether the shoreface is a source or sink for coastal sediment during rising sea level may be a crucial determinant of future shoreline change. While simple equilibrium-based models (e.g. the Bruun Rule) are widely used in coastal risk planning practice to predict shoreline change due to sea level rise, the relevance of fundamental model assumptions to the shoreface depositional setting is often overlooked due to limited knowledge about the geomorphology of the nearshore seabed. We present high-resolution mapping of the shoreface-inner shelf in southeastern Australia from airborne lidar and vessel-based multibeam echosounder surveys, which reveals a more complex seabed than was previously known. The mapping data are used to interpret the extent, depositional character and morphodynamic state of the shoreface, by comparing the observed geomorphology to theoretical predictions from wave-driven sediment transport theory. The benefits of high-resolution seabed mapping for improving shoreline change predictions in practice are explored by comparing idealised shoreline change modelling based on our understanding of shoreface geomorphology and morphodynamics before and after the mapping exercise.

Salinity legacy: Foliar microbiome's history affects mutualist‐conferred salinity tolerance - Suresh C. Subedi; Preston Allen; Rosario Vidales; Leonel Sternberg; Michael Ross; Michelle E. Afkhami (Ecology, 2022)
The rapid human‐driven changes in the environment during the Anthropocene have placed extreme stress on many plants and animals. Beneficial interactions with microorganisms may be crucial for ameliorating these stressors and facilitating the ecosystem services host organisms provide. Foliar endophytes, microorganisms that reside within leaves, are found in essentially all plants and can provide important benefits (e.g., enhanced drought tolerance or resistance to herbivory). However, it remains unclear how important the legacy effects of the abiotic stressors that select on these microbiomes are for affecting the degree of stress amelioration provided to their hosts. To elucidate foliar endophytes' role in host‐plant salt tolerance, especially if salinity experienced in the field selects for endophytes that are better suited to improve the salt tolerance of their hosts, we combined field collections of 90 endophyte communities from 30 sites across the coastal Everglades with a manipulative growth experiment assessing endophyte inoculation effects on host‐plant performance. Specifically, we grew >350 red mangrove ( Rhizophora mangle ) seedlings in a factorial design that manipulated the salinity environment the seedlings experienced (freshwater vs. saltwater), the introduction of field‐collected endophytes (live vs. sterilized inoculum), and the legacy of salinity stress experienced by these introduced endophytes, ranging from no salt stress (0 parts per thousand [ppt] salinity) to high salt stress (40 ppt) environments. We found that inoculation with field‐collected endophytes significantly increased mangrove performance across almost all metrics examined (15%–20% increase on average), and these beneficial effects typically occurred when the endophytes were grown in saltwater. Importantly, our study revealed the novel result that endophyte‐conferred salinity tolerance depended on microbiome salinity legacy in a key coastal foundation species. Salt‐stressed mangroves inoculated with endophyte microbiomes from high‐salinity environments performed, on average, as well as plants grown in low‐stress freshwater, while endophytes from freshwater environments did not relieve host salinity stress. Given the increasing salinity stress imposed by sea level rise and the importance of foundation species like mangroves for ecosystem services, our results indicate that consideration of endophytic associations and their salinity legacy may be critical for the successful restoration and management of coastal habitats.

Can Stomach Content and Microbiomes of Tuna Provide Near Real-Time Detection of Ecosystem Composition in the Pacific Ocean? - Alejandro Trujillo-González; Teng Li; Joanne Potts; Simon Nicol; Valerie Allain; Sam C. Godwin; Elodie Vourey; Annie Portal; Brian Kumasi; Thomas Usu; Allen Rodrigo; Dianne Gleeson (Frontiers in Marine Science, 2022)
This preliminary study used DNA metabarcoding to test whether the stomach content and gut microbiome of tuna could be a viable near real-time monitoring tool for detecting composition and change in oceanic ecosystems. The gut content of skipjack ( Katsuwonus pelamis , n=55) and yellowfin tuna ( Thunnus albacares , n=46) captured in the Pacific Ocean during El Niño Southern Oscillation events (ENSO) between 2015-2017 were examined by high throughput sequencing and complemented by morphological assessments to identify fishes, crustaceans and cephalopods in the stomach content. Gut microbiome was examined solely by high throughput sequencing. Stomach content and gut microbiome were compared between tuna species, ENSO events and capture location using generalised linear models. The full model (tuna species, capture location and interaction with ENSO) best explained fish prey composition, while capture location and ENSO weakly explained the composition of crustaceans and cephalopods. Skipjack and yellowfin tuna captured near coastal areas (Longitude<170°W) showed a greater diversity of prey compared to fish captured in oceanic regions of the Pacific, while Thunnus albacares showed a much more diverse stomach content than K. pelamis (21 fish, eight cephalopods and six crustaceans). Fish captured during La Niña events showed higher prey diversity compared to fish captured during El Niño. Tuna species best explained differences in gut microbiome to the Phylum level, while no model explained gut microbiome differences to the Order or Family level. This preliminary study shows that capture location and ENSO events explained differences in stomach content of K. pelamis and T. albacares, while tuna species best explained gut microbiome assemblages to the Phylum level.

The impacts of mangrove range expansion on wetland ecosystem services in the southeastern United States: Current understanding, knowledge gaps, and emerging research needs - Michael J. Osland; A. Randall Hughes; Anna R. Armitage; Steven B. Scyphers; Just Cebrian; Savannah H. Swinea; Christine C. Shepard; Micheal S. Allen; Laura C. Feher; James A. Nelson; Cherie L. O’Brien; Colt R. Sanspree; et al. (Global Change Biology, 2022)
Climate change is transforming ecosystems and affecting ecosystem goods and services. Along the Gulf of Mexico and Atlantic coasts of the southeastern United States, the frequency and intensity of extreme freeze events greatly influence whether coastal wetlands are dominated by freeze‐sensitive woody plants (mangrove forests) or freeze‐tolerant grass‐like plants (salt marshes). In response to warming winters, mangroves have been expanding and displacing salt marshes at varying degrees of severity in parts of north Florida, Louisiana, and Texas. As winter warming accelerates, mangrove range expansion is expected to increasingly modify wetland ecosystem structure and function. Because there are differences in the ecological and societal benefits that salt marshes and mangroves provide, coastal environmental managers are challenged to anticipate the effects of mangrove expansion on critical wetland ecosystem services, including those related to carbon sequestration, wildlife habitat, storm protection, erosion reduction, water purification, fisheries support, and recreation. Mangrove range expansion may also affect wetland stability in the face of extreme climatic events and rising sea levels. Here, we review the current understanding of the effects of mangrove range expansion and displacement of salt marshes on wetland ecosystem services in the southeastern United States. We also identify critical knowledge gaps and emerging research needs regarding the ecological and societal implications of salt marsh displacement by expanding mangrove forests. One consistent theme throughout our review is that there are ecological trade‐offs for consideration by coastal managers. Mangrove expansion and marsh displacement can produce beneficial changes in some ecosystem services, while simultaneously producing detrimental changes in other services. Thus, there can be local‐scale differences in perceptions of the impacts of mangrove expansion into salt marshes. For very specific local reasons, some individuals may see mangrove expansion as a positive change to be embraced, while others may see mangrove expansion as a negative change to be constrained.

Plasma Kallikrein Contributes to Intracerebral Hemorrhage and Hypertension in Stroke-Prone Spontaneously Hypertensive Rats - Jian Guan; Allen C. Clermont; Loc-Duyen Pham; Tuna Ustunkaya; Alexey S. Revenko; A. Robert MacLeod; Edward P. Feener; Fabrício Simão (Translational Stroke Research, 2022)

Adaptation and early implementation of the PREdiction model for gene mutations (PREMM5™) for lynch syndrome risk assessment in a diverse population - Kathleen F. Mittendorf; Chinedu Ukaegbu; Marian J. Gilmore; Nangel M. Lindberg; Tia L. Kauffman; Donna J. Eubanks; Elizabeth Shuster; Jake Allen; Carmit McMullen; Heather Spencer Feigelson; Katherine P. Anderson; Michael C. Leo; et al. (Familial Cancer, 2022)
Lynch syndrome (LS) is the most common inherited cause of colorectal and endometrial cancers. Identifying individuals at risk for LS without personal cancer history requires detailed collection and assessment of family health history. However, barriers exist to family health history collection, especially in historically underserved populations. To improve LS risk assessment in historically underserved populations, we adapted the provider-facing PREdiction Model for gene Mutations (PREMM 5 ™ model), a validated LS risk assessment model, into a patient-facing electronic application through an iterative development process involving expert and patient stakeholders. We report on preliminary findings based on the first 500 individuals exposed to the adapted application in a primary care population enriched for low-literacy and low-resource patients. Major adaptations to the PREMM 5 ™ provider module included reduction in reading level, addition of interactive literacy aids, incorporation of family history assessment for both maternal and paternal sides of the family, and inclusion of questions about individual relatives or small groups of relatives to reduce cognitive burden. In the first 500 individuals, 90% completed the PREMM 5 ™ independently; of those, 94% did so in 5 min or less (ranged from 0.2 to 48.8 min). The patient-facing application was able to accurately classify 84% of patients as having clinically significant or not clinically significant LS risk. Our preliminary results suggest that in this diverse study population, most participants were able to rapidly, accurately, and independently complete an interactive application collecting family health history assessment that accurately assessed for Lynch syndrome risk.

Durable siloxane-polyurethane coatings for mitigating freshwater mussel fouling - Teluka Pasan Galhenage; Shane J. Stafslien; Allen Skaja; Dean C. Webster (Biofouling, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

A National Status Report on United States Coral Reefs Based on 2012–2018 Data From National Oceanic and Atmospheric Administration’s National Coral Reef Monitoring Program - Erica K. Towle; E. Caroline Donovan; Heath Kelsey; Mary E. Allen; Hannah Barkley; Jeremiah Blondeau; Russell E. Brainard; Annie Carew; Courtney S. Couch; Maria K. Dillard; C. Mark Eakin; Kimberly Edwards; et al. (Frontiers in Marine Science, 2022)
National Oceanic and Atmospheric Administration’s Coral Reef Conservation Program supports the National Coral Reef Monitoring Program (NCRMP) in the United States Pacific, Atlantic, Caribbean, and Gulf of Mexico. NCRMP conducts standardized observations of biological, climatic, and socioeconomic indicators across American Samoa, Guam, the Main Hawaiian Islands, the Northwestern Hawaiian Islands, the Northern Mariana Islands, the Pacific Remote Islands, Florida, the Flower Garden Banks, Puerto Rico, and the United States Virgin Islands. NCRMP provides periodic, national-level assessments of the status of United States coral reef ecosystems and communities connected to them. In 2014, NCRMP partnered with the University of Maryland Center for Environmental Science on an unprecedented collaboration between federal and jurisdictional/state agencies, academia, and non-governmental organizations to synthesize NCRMP data into a reporting format designed to be accessible and relevant to the public and policy makers. The process involved multi-year data analyses of key benthic, fish, and climate indicators. In populated jurisdictions, socioeconomic data were integrated to assess public support for management actions, participation in pro-environmental behaviors, and awareness of threats to coral reefs. Jurisdictions were scored using a report-card scale (0–100%) by establishing references for each indicator using best-available historical data or expert opinion where historical data did not exist or were not statistically comparable. Despite overall ecosystem scores of Fair for all combined Atlantic (70%) and Pacific (74%) jurisdictions, the current trend is downward with a majority of United States coral reefs declining and vulnerable to further degradation. Remote, uninhabited reefs had an advantage with respect to reef fish population scores, i.e., Flower Garden Banks (85%) and Pacific Remote Islands (93%), when compared to populated location scores, i.e., Puerto Rico (63%) and Main Hawaiian Islands (66%). All coral reefs are highly impacted by climate change, and climate impacts were more pronounced than expected on remote reefs, i.e., the Northwestern Hawaiian Islands (58%). Presenting results in a report-card style facilitates communication to the public and policy makers, and provides a useful mechanism to garner support for management actions such as expanding protected areas; enforcing existing regulations; increasing climate change education; reducing land-based sources of pollution; and other actions to improve the trajectory of coral reef ecosystem conditions.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Climate change research and action must look beyond 2100 - Christopher Lyon; Erin E. Saupe; Christopher J. Smith; Daniel J. Hill; Andrew P. Beckerman; Lindsay C. Stringer; Robert Marchant; James McKay; Ariane Burke; Paul O’Higgins; Alexander M. Dunhill; Bethany J. Allen; et al. (Global Change Biology, 2022)
Anthropogenic activity is changing Earth's climate and ecosystems in ways that are potentially dangerous and disruptive to humans. Greenhouse gas concentrations in the atmosphere continue to rise, ensuring that these changes will be felt for centuries beyond 2100, the current benchmark for projection. Estimating the effects of past, current, and potential future emissions to only 2100 is therefore short‐sighted. Critical problems for food production and climate‐forced human migration are projected to arise well before 2100, raising questions regarding the habitability of some regions of the Earth after the turn of the century. To highlight the need for more distant horizon scanning, we model climate change to 2500 under a suite of emission scenarios and quantify associated projections of crop viability and heat stress. Together, our projections show global climate impacts increase significantly after 2100 without rapid mitigation. As a result, we argue that projections of climate and its effects on human well‐being and associated governance and policy must be framed beyond 2100.

Assessing the Viability of the Sarasota Bay Community of Bottlenose Dolphins - Robert C. Lacy; Randall S. Wells; Michael D. Scott; Jason B. Allen; Aaron A. Barleycorn; Kim W. Urian; Suzanne Hofmann (Frontiers in Marine Science, 2021)
Population models, such as those used for Population Viability Analysis (PVA), are valuable for projecting trends, assessing threats, guiding environmental resource management, and planning species conservation measures. However, rarely are the needed data on all aspects of the life history available for cetacean species, because they are long-lived and difficult to study in their aquatic habitats. We present a detailed assessment of population dynamics for the long-term resident Sarasota Bay common bottlenose dolphin ( Tursiops truncatus ) community. Model parameters were estimated from 27 years of nearly complete monitoring, allowing calculation of age-specific and sex-specific mortality and reproductive rates, uncertainty in parameter values, fluctuation in demographic rates over time, and intrinsic uncertainty in the population trajectory resulting from stochastic processes. Using the Vortex PVA model, we projected mean population growth and quantified causes of variation and uncertainty in growth. The ability of the model to simulate the dynamics of the population was confirmed by comparing model projections to observed census trends from 1993 to 2020. When the simulation treated all losses as deaths and included observed immigration, the model projects a long-term mean annual population growth of 2.1%. Variance in annual growth across years of the simulation ( SD = 3.1%) was due more to environmental variation and intrinsic demographic stochasticity than to uncertainty in estimates of mean demographic rates. Population growth was most sensitive to uncertainty and annual variation in reproduction of peak breeding age females and in calf and juvenile mortality, while adult survival varied little over time. We examined potential threats to the population, including increased anthropogenic mortality and impacts of red tides, and tested resilience to catastrophic events. Due to its life history characteristics, the population was projected to be demographically stable at smaller sizes than commonly assumed for Minimum Viable Population of mammals, but it is expected to recover only slowly from any catastrophic events, such as disease outbreaks and spills of oil or other toxins. The analyses indicate that well-studied populations of small cetaceans might typically experience slower growth rates (about 2%) than has been assumed in calculations of Potential Biological Removal used by management agencies to determine limits to incidental take of marine mammals. The loss of an additional one dolphin per year was found to cause significant harm to this population of about 150 to 175 animals. Beyond the significance for the specific population, demographic analyses of the Sarasota Bay dolphins provide a template for examining viability of other populations of small cetaceans.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

The role of CDHR3 in susceptibility to otitis media - Scott D. Hirsch; Christina L. Elling; Tori C. Bootpetch; Melissa A. Scholes; Lena Hafrén; Sven-Olrik Streubel; Harold S. Pine; Todd M. Wine; Wasyl Szeremeta; Jeremy D. Prager; Elisabet Einarsdottir; Ayesha Yousaf; et al. (Journal of Molecular Medicine, 2021)

Homogeneity of cognitive and behavioural processes underlying the relationship between insomnia and body image disturbance - Umair Akram; Sarah F. Allen; Jodie C. Stevenson; Lambros Lazuras; Millicent Ackroyd; Jessica Chester; Jessica Longden; Chloe Peters; Kamila R. Irvine (Cognitive Processing, 2021)
Specific cognitive behavioural mechanisms related to selective attention, situational avoidance and physical appearance are implicated in the development and maintenance of insomnia and negative reinforcement of body image disturbances. Therefore, we examined whether these processes potentially mediate the relationship between insomnia and body image perception. N = 728 participants completed self-reported measures of sleep-associated monitoring, insomnia symptoms, body image disturbance and coping with body image challenges. Symptoms of insomnia and sleep-associated monitoring behaviour were independently related to increased reports of body image disturbance, cognitive distortions of body image, appearance fixing (i.e. altering appearance by covering, camouflaging or correcting the perceived defect), avoidance (i.e. attempt to escape or avert stressful body image situations) and reduced levels of positive rationale acceptance (i.e. acceptance of the challenging event and positive self-care or rationale self-talk about one’s appearance). More crucially, sleep-related monitoring on awakening, cognitive distortion of body image and negative coping strategies related to body image (i.e. appearance fixing, avoidance, rationale acceptance) mediated the relationship between reports of body image disturbance and insomnia symptoms. The current findings expand upon previous research demonstrating consistent relationships between poor sleep and increased dissatisfaction with cutaneous features, by providing novel evidence that body image disturbances are associated with symptoms of insomnia. More crucially, we highlight the role of particular cognitive and behavioural mechanisms pertaining to sleep (i.e. selective attention for physical signs of poor sleep) and body image (i.e. avoidance and rationale acceptance) which may be targeted as part of cognitive behavioural treatments.

Physical activity in relation to circulating hormone concentrations in 117,100 men in UK Biobank - Eleanor L. Watts; Aurora Perez-Cornago; Aiden Doherty; Naomi E. Allen; Georgina K. Fensom; Sandar Tin Tin; Timothy J. Key; Ruth C. Travis (Cancer Causes & Control, 2021)
Purpose Physical activity may reduce the risk of some types of cancer in men. Biological mechanisms may involve changes in hormone concentrations; however, this relationship is not well established. Therefore, we aimed to investigate the associations of physical activity with circulating insulin-like growth factor-I (IGF-I), sex hormone-binding globulin (SHBG, which modifies sex hormone activity), and total and free testosterone concentrations, and the extent these associations might be mediated by body mass index (BMI). Methods Circulating concentrations of these hormones and anthropometric measurements and self-reported physical activity data were available for 117,100 healthy male UK Biobank participants at recruitment. Objectively measured accelerometer physical activity levels were also collected on average 5.7 years after recruitment in 28,000 men. Geometric means of hormone concentrations were estimated using multivariable-adjusted analysis of variance, with and without adjustment for BMI. Results The associations between physical activity and hormones were modest and similar for objectively measured (accelerometer) and self-reported physical activity. Compared to men with the lowest objectively measured physical activity, men with high physical activity levels had 14% and 8% higher concentrations of SHBG and total testosterone, respectively, and these differences were attenuated to 6% and 3% following adjustment for BMI. Conclusion Our results suggest that the associations of physical activity with the hormones investigated are, at most, modest; and following adjustment for BMI, the small associations with SHBG and total testosterone were largely attenuated. Therefore, it is unlikely that changes in these circulating hormones explain the associations of physical activity with risk of cancer either independently or via BMI.

Anticipating and Adapting to the Future Impacts of Climate Change on the Health, Security and Welfare of Low Elevation Coastal Zone (LECZ) Communities in Southeastern USA - Thomas Allen; Joshua Behr; Anamaria Bukvic; Ryan S. D. Calder; Kiki Caruson; Charles Connor; Christopher D’Elia; David Dismukes; Robin Ersing; Rima Franklin; Jesse Goldstein; Jonathon Goodall; et al. (Journal of Marine Science and Engineering, 2021)
Low elevation coastal zones (LECZ) are extensive throughout the southeastern United States. LECZ communities are threatened by inundation from sea level rise, storm surge, wetland degradation, land subsidence, and hydrological flooding. Communication among scientists, stakeholders, policy makers and minority and poor residents must improve. We must predict processes spanning the ecological, physical, social, and health sciences. Communities need to address linkages of (1) human and socioeconomic vulnerabilities; (2) public health and safety; (3) economic concerns; (4) land loss; (5) wetland threats; and (6) coastal inundation. Essential capabilities must include a network to assemble and distribute data and model code to assess risk and its causes, support adaptive management, and improve the resiliency of communities. Better communication of information and understanding among residents and officials is essential. Here we review recent background literature on these matters and offer recommendations for integrating natural and social sciences. We advocate for a cyber-network of scientists, modelers, engineers, educators, and stakeholders from academia, federal state and local agencies, non-governmental organizations, residents, and the private sector. Our vision is to enhance future resilience of LECZ communities by offering approaches to mitigate hazards to human health, safety and welfare and reduce impacts to coastal residents and industries.

Effect of salinity on growth, survival, and serum osmolality of red snapper, Lutjanus campechanus - Harsha S. C. Galkanda-Arachchige; Robert P. Davis; Sidra Nazeer; Leonardo Ibarra-Castro; D. Allen Davis (Fish Physiology and Biochemistry, 2021)

Robotic Assessment of Upper Limb Function in a Nonhuman Primate Model of Chronic Stroke - Yining Chen; Meredith C. Poole; Shelby V. Olesovsky; Allen A. Champagne; Kathleen A. Harrison; Joseph Y. Nashed; Nicole S. Coverdale; Stephen H. Scott; Douglas J. Cook (Translational Stroke Research, 2021)

Biodiversity and biogeography of hydroids across marine ecoregions and provinces of southern South America and Antarctica - Thaís P. Miranda; Marina O. Fernandez; Gabriel N. Genzano; Álvaro L. Peña Cantero; Allen G. Collins; Antonio C. Marques (Polar Biology, 2021)

Disturbance type and species life history predict mammal responses to humans - Justin P. Suraci; Kaitlyn M. Gaynor; Maximilian L. Allen; Peter Alexander; Justin S. Brashares; Sara Cendejas‐Zarelli; Kevin Crooks; L. Mark Elbroch; Tavis Forrester; Austin M. Green; Jeffrey Haight; Nyeema C. Harris; et al. (Global Change Biology, 2021)
Human activity and land use change impact every landscape on Earth, driving declines in many animal species while benefiting others. Species ecological and life history traits may predict success in human‐dominated landscapes such that only species with “winning” combinations of traits will persist in disturbed environments. However, this link between species traits and successful coexistence with humans remains obscured by the complexity of anthropogenic disturbances and variability among study systems. We compiled detection data for 24 mammal species from 61 populations across North America to quantify the effects of (1) the direct presence of people and (2) the human footprint (landscape modification) on mammal occurrence and activity levels. Thirty‐three percent of mammal species exhibited a net negative response (i.e., reduced occurrence or activity) to increasing human presence and/or footprint across populations, whereas 58% of species were positively associated with increasing disturbance. However, apparent benefits of human presence and footprint tended to decrease or disappear at higher disturbance levels, indicative of thresholds in mammal species’ capacity to tolerate disturbance or exploit human‐dominated landscapes. Species ecological and life history traits were strong predictors of their responses to human footprint, with increasing footprint favoring smaller, less carnivorous, faster‐reproducing species. The positive and negative effects of human presence were distributed more randomly with respect to species trait values, with apparent winners and losers across a range of body sizes and dietary guilds. Differential responses by some species to human presence and human footprint highlight the importance of considering these two forms of human disturbance separately when estimating anthropogenic impacts on wildlife. Our approach provides insights into the complex mechanisms through which human activities shape mammal communities globally, revealing the drivers of the loss of larger predators in human‐modified landscapes.

Contributions of Organic and Mineral Matter to Vertical Accretion in Tidal Wetlands across a Chesapeake Bay Subestuary - Jenny R. Allen; Jeffrey C. Cornwell; Andrew H. Baldwin (Journal of Marine Science and Engineering, 2021)
Persistence of tidal wetlands under conditions of sea level rise depends on vertical accretion of organic and inorganic matter, which vary in their relative abundance across estuarine gradients. We examined the relative contribution of organic and inorganic matter to vertical soil accretion using lead-210 (210Pb) dating of soil cores collected in tidal wetlands spanning a tidal freshwater to brackish gradient across a Chesapeake Bay subestuary. Only 8 out of the 15 subsites had accretion rates higher than relative sea level rise for the area, with the lowest rates of accretion found in oligohaline marshes in the middle of the subestuary. The mass accumulation of organic and inorganic matter was similar and related (R2 = 0.37). However, owing to its lower density, organic matter contributed 1.5–3 times more toward vertical accretion than inorganic matter. Furthermore, water/porespace associated with organic matter accounted for 82%–94% of the total vertical accretion. These findings demonstrate the key role of organic matter in the persistence of coastal wetlands with low mineral sediment supply, particularly mid-estuary oligohaline marshes.

High Throughput Argon-37 Field System - James C. Hayes; Craig Aalseth; Thomas Alexander; Henning Back; Eric Church; Michael Foxe; Todd Hossbach; Paul Humble; Lance Lidey; Emily Mace; Kerry Meinhardt; Jennifer Mendez; et al. (Pure and Applied Geophysics, 2021)

The conservation status of the world’s freshwater molluscs - Monika Böhm; Nadia I. Dewhurst-Richman; Mary Seddon; Sophie E. H. Ledger; Christian Albrecht; David Allen; Arthur E. Bogan; Jay Cordeiro; Kevin S. Cummings; Annabelle Cuttelod; Gustavo Darrigran; Will Darwall; et al. (Hydrobiologia, 2021)

Modelling potential Pleistocene habitat corridors between Afromontane forest regions - Kaitlin E. Allen; Walter P. Tapondjou; Benedictus Freeman; Jacob C. Cooper; Rafe M. Brown; A. Townsend Peterson (Biodiversity and Conservation, 2021)

Neuropsychological Assessment and Screening in Heart Failure: a Meta-Analysis and Systematic Review - Eric J. Connors; Alexander O. Hauson; Brianna D. Barlet; Sharis Sarkissians; Nicholas P. Stelmach; Alyssa D. Walker; Natasha M. Nemanim; Kristina L. Greenwood; Nicholas J. Chesher; Scott C. Wollman; Kenneth E. Allen; Matthew G. Hall; et al. (Neuropsychology Review, 2021)

Skeletal muscle mitochondrial DNA copy number and mitochondrial DNA deletion mutation frequency as predictors of physical performance in older men and women - Allen Herbst; Steven J. Prior; Cathy C. Lee; Judd M. Aiken; Debbie McKenzie; Austin Hoang; Nianjun Liu; Xiwei Chen; Pengcheng Xun; David B. Allison; Jonathan Wanagat (GeroScience, 2021)

Neighboring colonies influence uptake of thermotolerant endosymbionts in threatened Caribbean coral recruits - Olivia M. Williamson; Corinne E. Allen; Dana E. Williams; Matthew W. Johnson; Margaret W. Miller; Andrew C. Baker (Coral Reefs, 2021)

A Model for Studying the Biomechanical Effects of Varying Ratios of Collagen Types I and III on Cardiomyocytes - Brian Roman; Shweta Anil Kumar; Shane C. Allen; Monica Delgado; Sabastian Moncayo; Andres M. Reyes; Laura J. Suggs; Ramana Chintalapalle; Chunqiang Li; Binata Joddar (Cardiovascular Engineering and Technology, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Mapping shifts in spatial synchrony in grassland birds to inform conservation planning - Michael C. Allen; Julie L. Lockwood (Conservation Biology, 2021)
Resumen La sincronía espacial, definida como las fluctuaciones correlacionadas de la abundancia de poblaciones separadas espacialmente, puede deberse a las fluctuaciones regionales de los conductores ambientales naturales y antropogénicos de las poblaciones. Los análisis de la geografía de las sincronías pueden proporcionar conocimiento útil para guiar los esfuerzos de planeación de la conservación al revelar regiones de conductores comunes de población y la vulnerabilidad de extinción de las metapoblaciones. Examinamos la geografía de la sincronía espacial y los cambios por década en estos patrones para las aves de pastizal en los Estados Unidos y Canadá, las cuales están experimentando declinaciones poblacionales extensas y persistentes. Usamos modelos bayesianos jerárquicos y más de 50 años de datos de abundancia tomados del Censo Norteamericano de Aves Reproductoras para generar índices poblacionales dentro una cuadrícula de 2° de latitud por 2° de longitud. Calculamos y mapeamos la sincronía espacial local media para cada celda (la correlación con deducción de tendencia de la media del índice entre las celdas vecinas), además de la incertidumbre asociada, para 19 especies en dos períodos de 26 años: 1968 ‐ 1993 y 1994 ‐ 2019. Se predijo que las aves de pastizal aumentarían su sincronía espacial en donde aumentarán la intensificación agrícola, el cambio climático o las interacciones entre ambos. No encontramos evidencia de un aumento generalizado de la sincronía entre las especies de aves de pastizal. Sin embargo, con base en la geografía de estos cambios, hubo una heterogeneidad espacial considerable entre las especies. Como promedio entre las especies, identificamos módulos de sincronía espacial en aumento en las regiones de Prairie Pothole y Shortgrass Prairie así como una región de sincronía espacial en declive al este de los Estados Unidos. Nuestra estrategia tiene el potencial para guiar a la planeación de la conservación a escala continental al añadir una capa adicional de información relevante a los análisis del estado de las especies y a la priorización espacial de las acciones de manejo y de políticas. Nuestro trabajo contribuye a una creciente literatura que sugiere que el cambio mundial podría derivar en patrones cambiantes de sincronía espacial en las dinámicas poblacionales de muchos taxones con implicaciones amplias para la conservación de la biodiversidad. Mapeo de los Cambios en la Sincronía Espacial de las Aves de Pastizal para Guiar la Planeación de la Conservación

Variability in periphyton community and biomass over 37 years in Lake Tahoe (CA-NV) - Karen S. Atkins; Scott H. Hackley; Brant C. Allen; Shohei Watanabe; John E. Reuter; S. Geoffrey Schladow (Hydrobiologia, 2021)
Nuisance periphyton blooms are occurring in oligotrophic lakes worldwide, but few lakes have documented changes in biomass through periphyton monitoring. For decades periphyton has caused concern about oligotrophic Lake Tahoe’s nearshore water quality. To determine whether eulittoral periphyton increased in Lake Tahoe, measures of biomass and dominant communities at 0.5 m below lake level have been monitored regularly at nine shoreline sites starting in 1982, with up to 54 additional sites monitored annually at peak biomass. Lake-wide, this metric of periphyton biomass has not increased since monitoring began. Biomass decreased at many sites and increased at one. Periphyton biomass peaked in March and was low in the summer lake-wide. The northern and western shores had higher biomass than the eastern and southern shores. Biomass varied with lake level. High biomass occurred at sites regardless of urban development levels. As increasing periphyton at Lake Tahoe was first cited in scientific literature in the 1960s, it is possible that periphyton increased prior to our monitoring program. A dearth of published long-term monitoring data from oligotrophic lakes with reported periphyton blooms makes it difficult to determine the extent of this issue worldwide. Long-term nearshore monitoring is crucial for tracking and understanding periphyton blooms.

Fieldable Environmental DNA Sequencing to Assess Jellyfish Biodiversity in Nearshore Waters of the Florida Keys, United States - Cheryl Lewis Ames; Aki H. Ohdera; Sophie M. Colston; Allen G. Collins; William K. Fitt; André C. Morandini; Jeffrey S. Erickson; Gary J. Vora (Frontiers in Marine Science, 2021)
Recent advances in molecular sequencing technology and the increased availability of fieldable laboratory equipment have provided researchers with the opportunity to conduct real-time or near real-time gene-based biodiversity assessments of aquatic ecosystems. In this study, we developed a workflow and portable kit for fieldable environmental DNA sequencing (FeDS) and tested its efficacy by characterizing the breadth of jellyfish (Medusozoa) taxa in the coastal waters of the Upper and Lower Florida Keys. Environmental DNA was isolated from seawater collection events at eight sites and samples were subjected to medusozoan 16S rRNA gene and metazoan mitochondrial cytochrome oxidase 1 gene profiling via metabarcoding onsite. In total, FeDS yielded 175,326 processed sequence reads providing evidence for 53 medusozoan taxa. Our most salient findings revealed eDNA from: (1) two venomous box jellyfish (Cubozoa) species, including taxa whose stings cause the notorious Irukandji envenomation syndrome; (2) two species of potentially introduced stalked jellyfish (Staurozoa); and (3) a likely cryptic species of upside-down jellyfish (Scyphozoa). Taken together, the results of this study highlight the merits of FeDS in conducting biodiversity surveys of endemic and introduced species, and as a potential tool for assessing envenomation and/or conservation-related threats.

First documentation of scent-marking behaviors in striped skunks (Mephitis mephitis) - Kathrina Jackson; Christopher C. Wilmers; Heiko U. Wittmer; Maximilian L. Allen (Mammal Research, 2021)

An inventory and typology of permanent floodplain lakes in the Mississippi Alluvial Valley: a first step to conservation planning - L. E. Miranda; M. C. Rhodes; Y. Allen; K. J. Killgore (Aquatic Sciences, 2021)

A Convolutional Neural Network for Automated Detection of Humpback Whale Song in a Diverse, Long-Term Passive Acoustic Dataset - Ann N. Allen; Matt Harvey; Lauren Harrell; Aren Jansen; Karlina P. Merkens; Carrie C. Wall; Julie Cattiau; Erin M. Oleson (Frontiers in Marine Science, 2021)
Passive acoustic monitoring is a well-established tool for researching the occurrence, movements, and ecology of a wide variety of marine mammal species. Advances in hardware and data collection have exponentially increased the volumes of passive acoustic data collected, such that discoveries are now limited by the time required to analyze rather than collect the data. In order to address this limitation, we trained a deep convolutional neural network (CNN) to identify humpback whale song in over 187,000 h of acoustic data collected at 13 different monitoring sites in the North Pacific over a 14-year period. The model successfully detected 75 s audio segments containing humpback song with an average precision of 0.97 and average area under the receiver operating characteristic curve (AUC-ROC) of 0.992. The model output was used to analyze spatial and temporal patterns of humpback song, corroborating known seasonal patterns in the Hawaiian and Mariana Islands, including occurrence at remote monitoring sites beyond well-studied aggregations, as well as novel discovery of humpback whale song at Kingman Reef, at 5 ∘ North latitude. This study demonstrates the ability of a CNN trained on a small dataset to generalize well to a highly variable signal type across a diverse range of recording and noise conditions. We demonstrate the utility of active learning approaches for creating high-quality models in specialized domains where annotations are rare. These results validate the feasibility of applying deep learning models to identify highly variable signals across broad spatial and temporal scales, enabling new discoveries through combining large datasets with cutting edge tools.

Flexible Manufacturing: The Future State of Drug Product Development and Commercialization in the Pharmaceutical Industry - Yash Kapoor; Robert F. Meyer; Brian K. Meyer; James C. DiNunzio; Akhilesh Bhambhani; Justin Stanbro; Kristin J. M. Ploeger; Erin N. Guidry; Gregory M. Troup; Adam T. Procopio; Allen C. Templeton (Journal of Pharmaceutical Innovation, 2021)

Persistent COVID-19-associated neurocognitive symptoms in non-hospitalized patients - Joanna Hellmuth; T. Allen Barnett; Breton M. Asken; J. Daniel Kelly; Leonel Torres; Melanie L. Stephens; Bryan Greenhouse; Jeffrey N. Martin; Felicia C. Chow; Steven G. Deeks; Meredith Greene; Bruce L. Miller; et al. (Journal of NeuroVirology, 2021)
As cases of coronavirus disease 2019 (COVID-19) mount worldwide, attention is needed on potential long-term neurologic impacts for the majority of patients who experience mild to moderate illness managed as outpatients. To date, there has not been discussion of persistent neurocognitive deficits in patients with milder COVID-19. We present two cases of non-hospitalized patients recovering from COVID-19 with persistent neurocognitive symptoms. Commonly used cognitive screens were normal, while more detailed testing revealed working memory and executive functioning deficits. An observational cohort study of individuals recovering from COVID-19 (14 or more days following symptom onset) identified that among the first 100 individuals enrolled, 14 were non-hospitalized patients reporting persistent cognitive issues. These 14 participants had a median age of 39 years (interquartile range: 35–56), and cognitive symptoms were present for at least a median of 98 days (interquartile range: 71–120 following acute COVID-19 symptoms); no participants with follow-up evaluation reported symptom resolution. We discuss potential mechanisms to be explored in future studies, including direct viral effects, indirect consequences of immune activation, and immune dysregulation causing auto-antibody production.

Growth performance and acoustic feeding behavior of two size classes of Litopenaeus vannamei fed pelleted and extruded diets - Roberta Soares; Silvio Peixoto; Harsha S. C. Galkanda-Arachchige; D. Allen Davis (Aquaculture International, 2021)

Staying Alive: Long-Term Success of Bottlenose Dolphin Interventions in Southwest Florida - Katherine A. McHugh; Aaron A. Barleycorn; Jason B. Allen; Kim Bassos-Hull; Gretchen Lovewell; Denise Boyd; Anna Panike; Carolyn Cush; Deborah Fauquier; Blair Mase; Robert C. Lacy; Michelle R. Greenfield; et al. (Frontiers in Marine Science, 2021)
Small cetaceans face persistent threats from fisheries interactions, making effective mitigation a priority for conservation. In southwest Florida, interactions come primarily from small-scale recreational hook and line and trap/pot fisheries, with regional stranding network partners working with federal agency managers to assess and intervene as possible in cases of live animal entanglement. Evaluating success of intervention cases is difficult due to financial and logistical constraints which may preclude detailed follow-up monitoring. Survival over the initial 6 weeks post-release has been used as a marker of short-term success for small-cetacean rescue and/or rehabilitation cases. Early intervention prior to stranding, especially via remote disentanglement or rescue and immediate re-release onsite, can save entangled free-ranging dolphins facing life-threatening anthropogenic injuries. However, given the costs associated with interventions, it is important to understand the benefits of these endeavors not only to save individuals, but also to establish if and how saved individuals contribute to social functioning, survival and reproduction within small, resident populations facing multiple concurrent threats. Here we provide evidence from 27 well-documented common bottlenose dolphin ( Tursiops truncatus ) intervention cases during 1985–2019 where follow-up monitoring over multiple years sheds light on the longer-term success of these efforts and potential benefits to local populations. Nearly all rescued individuals (92%) survived longer than 6 weeks post-release (mean minimum survival period = 5 years, range 0–35 years), with 13 still observed frequently within their prior resident communities, in good physical health, and engaging in normal behavior. Survivorship rates did not decline substantially between 1 and 5 years post-rescue, meaning survival beyond 1 year may be a useful benchmark of long-term success. Rescued females that reached reproductive maturity ( n = 4) have produced 12 post-intervention offspring to date. Social network analysis and demographic modeling applied to cases from the long-term resident community in Sarasota Bay confirmed that animals maintain social connections post-intervention and that interventions result in higher population growth rates. While not every intervention succeeds, this study demonstrates the conservation value of pre-stranding interventions which allow individuals that otherwise would be lost to remain viable and productive members of local populations when prevention of anthropogenic injury is not possible.

A 50-Year Retrospective of the Forest Productivity Cooperative in the Southeastern United States: Regionwide Trials - David R Carter; H Lee Allen; Thomas R Fox; Timothy J Albaugh; Rafael A Rubilar; Otávio C Campoe; Rachel L Cook (Journal of Forestry, 2021)
In 2019, the Forest Productivity Cooperative (FPC) celebrated its 50th anniversary. The mission of the FPC is and has been creating innovative solutions to enhance forest productivity and value through the sustainable management of site resources. This industry-government-university partnership has generated seminal research with sweeping implications for increasing productivity throughout the southeastern United States and Latin America. To commemorate this semicentennial, we highlighted some of the pivotal findings in the southeastern United States from the past 50 years derived from our large, regional experiments: regionwide trials.

Acute rewarding and disinhibiting effects of alcohol as indicators of drinking habits - Holley C. Allen; Jessica Weafer; Michael J. Wesley; Mark T. Fillmore (Psychopharmacology, 2021)

Simulated Increases in Fire Activity Reinforce Shrub Conversion in a Southwestern US Forest - Alisa R. Keyser; Dan J. Krofcheck; Cécile C. Remy; Craig D. Allen; Matthew D. Hurteau (Ecosystems, 2020)

Homogeneous environmental selection dominates microbial community assembly in the oligotrophic South Pacific Gyre - Ro Allen; Linn J. Hoffmann; Matthew J. Larcombe; Ziva Louisson; Tina C. Summerfield (Molecular Ecology, 2020)
Oligotrophic subtropical gyres are the largest continuous biomes on Earth and play a key role in global biogeochemical cycles. Microbial communities govern primary production and carbon cycling in the oligotrophic South Pacific Gyre, yet the ecological processes which underpin microbial biogeography in the region remain understudied. We investigated microbial biogeography and community assembly processes at three depths over a ~2,000‐km the transect was longitudinal, so ran from 32°S, 170°W to 32°S, 152°W). Thus the latitude (32°S) was constant. Microbial communities in the surface waters (15 and 50 m) were remarkably similar across the transect, whilst communities at the deep chlorophyll maximum were distinct from the surface waters and displayed greater compositional heterogeneity. An ecological null model approach indicated that homogeneous selection was the dominant community assembly process in both the surface waters (100%) and at the deep chlorophyll maximum (91.81%), although variable selection (2.34%) and stochastic processes (5.85%) had a minor influence at the deep chlorophyll maximum. Homogeneous selection (76.69%77.90%), dispersal limitation (15.00%–20.05%) and variable selection (3.01%–7.11%) influenced community assembly between the surface waters and the deep chlorophyll maximum. Seawater density and temperature, which were correlated, were the most important environmental modulators of the balance between stochastic and deterministic assembly processes. Our findings demonstrate remarkable similarity in microbial community composition across longitudinal scales in the oligotrophic South Pacific Gyre, underpinned by strong environmental selection which overwhelms the influence of ecological drift. These data significantly advance our understanding of microbial community dynamics in the oligotrophic subtropical gyres which dominate the Earth's surface.

A Case Study of Eukaryogenesis: The Evolution of Photoreception by Photolyase/Cryptochrome Proteins - Jennifer A. Miles; Thomas A. Davies; Robert D. Hayman; Georgia Lorenzen; Jamie Taylor; Mubeena Anjarwalla; Sammie J. R. Allen; John W. D. Graham; Paul C. Taylor (Journal of Molecular Evolution, 2020)
Eukaryogenesis, the origin of the eukaryotes, is still poorly understood. Herein, we show how a detailed all-kingdom phylogenetic analysis overlaid with a map of key biochemical features can provide valuable clues. The photolyase/cryptochrome family of proteins are well known to repair DNA in response to potentially harmful effects of sunlight and to entrain circadian rhythms. Phylogenetic analysis of photolyase/cryptochrome protein sequences from a wide range of prokaryotes and eukaryotes points to a number of horizontal gene transfer events between ancestral bacteria and ancestral eukaryotes. Previous experimental research has characterised patterns of tryptophan residues in these proteins that are important for photoreception, specifically a tryptophan dyad, a canonical tryptophan triad, an alternative tryptophan triad, a tryptophan tetrad and an alternative tetrad. Our results suggest that the spread of the different triad and tetrad motifs across the kingdoms of life accompanied the putative horizontal gene transfers and is consistent with multiple bacterial contributions to eukaryogenesis.

Convergence, continuity, and community: a framework for enabling emerging leaders to build climate solutions in agriculture, forestry, and aquaculture - S. K. Birthisel; B. A. Eastman; A. R. Soucy; M. Paul; R. S. Clements; A. White; M. P. Acquafredda; W. Errickson; L-H. Zhu; M. C. Allen; S. A. Mills; G. Dimmig; et al. (Climatic Change, 2020)

Animal aggregations promote emergent aquatic plant production at the aquatic–terrestrial interface - Jonathan W. Lopez; Thomas B. Parr; Daniel C. Allen; Caryn C. Vaughn (Ecology, 2020)
The roles mobile animals and abiotic processes play as vectors for resource transfers between ecosystems (“subsidies”) are well studied, but the idea that resources from animals with limited mobility may be transported across boundaries through intermediate taxa remains unexplored. Aquatic plants (“macrophytes”) are globally distributed and may mediate transfers of aquatic‐derived nutrients from aggregations of aquatic animals to terrestrial ecosystems when consumed by terrestrial herbivores. We used mesocosms (94 × 44 cm) to test whether aquatic animal‐generated biogeochemical hotspots increase growth and nutrient content in macrophytes using the macrophyte Justicia americana and freshwater mussels. Justicia americana biomass production increased and belowground biomass allocation changed with increasing mussel density. At high mussel density, water‐column phosphorus increased and carbon:phosphorus ratios in J. americana tissues decreased. We deployed motion‐sensing cameras to explore herbivory on J. americana growing along the margins of the Kiamichi River, Oklahoma, and documented feeding by large mammals ( Odocoileus virginianus , Sus scrofa , and Bos taurus ). Thus, biogeochemical hotspots generated by aquatic animal aggregations can promote macrophyte production that subsequently is transferred to terrestrial animals. More broadly, this suggests that reductions in aquatic animal biomass may have bottom‐up impacts that indirectly affect terrestrial ecosystems via plant–animal interactions bridging ecosystem boundaries.

Co-limitation by N and P Characterizes Phytoplankton Communities Across Nutrient Availability and Land Use - A. R. Bratt; J. C. Finlay; J. R. Welter; B. A. Vculek; R. E. Van Allen (Ecosystems, 2020)

Precipitation‐drainage cycles lead to hot moments in soil carbon dioxide dynamics in a Neotropical wet forest - Angel Santiago Fernandez‐Bou; Diego Dierick; Michael F. Allen; Thomas C. Harmon (Global Change Biology, 2020)
Soil CO 2 concentrations and emissions from tropical forests are modulated seasonally by precipitation. However, subseasonal responses to meteorological events (e.g., storms, drought) are less well known. Here, we present the effects of meteorological variability on short‐term (hours to months) dynamics of soil CO 2 concentrations and emissions in a Neotropical wet forest. We continuously monitored soil temperature, moisture, and CO 2 for a three‐year period (2015–2017), encompassing normal conditions, floods, a dry El Niño period, and a hurricane. We used a coupled model (Hydrus‐1D) for soil water propagation, heat transfer, and diffusive gas transport to explain observed soil moisture, soil temperature, and soil CO 2 concentration responses to meteorology, and we estimated soil CO 2 efflux with a gradient‐flux model. Then, we predicted changes in soil CO 2 concentrations and emissions under different warming climate change scenarios. Observed short‐term (hourly to daily) soil CO 2 concentration responded more to precipitation than to other meteorological variables (including lower pressure during the hurricane). Observed soil CO 2 failed to exhibit diel patterns (associated with diel temperature fluctuations in drier climates), except during the drier El Niño period. Climate change scenarios showed enhanced soil CO 2 due to warmer conditions, while precipitation played a critical role in moderating the balance between concentrations and emissions. The scenario with increased precipitation (based on a regional model projection) led to increases of +11% in soil CO 2 concentrations and +4% in soil CO 2 emissions. The scenario with decreased precipitation (based on global circulation model projections) resulted in increases of +4% in soil CO 2 concentrations and +18% in soil CO 2 emissions, and presented more prominent hot moments in soil CO 2 outgassing. These findings suggest that soil CO 2 will increase under warmer climate in tropical wet forests, and precipitation patterns will define the intensity of CO 2 outgassing hot moments.

Cancer mortality risk, fine particulate air pollution, and smoking in a large, representative cohort of US adults - Nathan C. Coleman; Richard T. Burnett; Joshua D. Higbee; Jacob S. Lefler; Ray M. Merrill; Majid Ezzati; Julian D. Marshall; Sun-Young Kim; Matthew Bechle; Allen L. Robinson; C. Arden Pope (Cancer Causes & Control, 2020)

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Using spatial characteristics of apex carnivore communication and reproductive behaviors to predict responses to future human development - Veronica Yovovich; Maximilian L. Allen; Luke T. Macaulay; Christopher C. Wilmers (Biodiversity and Conservation, 2020)

Gradual and rapid shifts in the composition of assemblages of hydroids (Cnidaria) along depth and latitude in the deep Atlantic Ocean - Marina O. Fernandez; Allen G. Collins; Antonio C. Marques (Journal of Biogeography, 2020)
Aim Despite growing knowledge on deep‐sea benthic fauna, patterns of changes in species composition combining both bathymetric and latitudinal variation are still poorly known. In the first synthesis on the beta diversity patterns of assemblages of hydroids across an entire ocean basin, our aim was to infer limits and gradients of species distribution along depth and latitude. Location Atlantic Ocean and adjacent polar seas. Taxon Hydrozoa. Methods Hydroids from 50 to 5,330 m deep were studied primarily based on museum collections. Identifications were made by the authors, improving uniformity within the dataset by avoiding variations in taxonomic interpretation. Data totalled 3,699 records belonging to 432 species, at 1,444 unique sites. Records were assigned to three depth strata (50–200, 201–1,000 and 1,001–5,330 m) and eight latitudinal bands of 20° each, totalling 24 sample areas. We conducted non‐metric multidimensional scaling (NMDS) ordination, clustering and PERMANOVA analyses of species compositions and abundances per area to examine differences and relationships in hydroid assemblages among areas. Results Assemblages primarily differentiate between those to the north and south of 40°S, regardless of depth, with southern ones separated between Patagonian and Antarctic. Northwards of 40°S, assemblages differentiate gradually along both depth and latitude, although a faunal turnover occurs at 1,000 m deep. Also, assemblages at 1,001–5,330 m deep tend to be more similar to each other than assemblages at shallower strata, suggesting significant connectivity over great distances in the deep sea. We note the problem of largely unequal hydroid sampling in the Atlantic Ocean across depths and latitudes, especially in the southern hemisphere and below 1,000 m deep. Main Conclusions Assemblages of hydroids differentiate gradually along latitude and depth, with more rapid shifts in species composition occurring at 40°S, 60°S and at 1,000 m deep. Greater similarity was found among deeper water assemblages.

Associations between sensitivity to antibiotics, disinfectants and heavy metals in natural, clinical and laboratory isolates of Escherichia coli - Anna M. Bischofberger; Michael Baumgartner; Katia R. Pfrunder‐Cardozo; Richard C. Allen; Alex R. Hall (Environmental Microbiology, 2020)
Summary Bacteria in nature often encounter non‐antibiotic antibacterials (NAAs), such as disinfectants and heavy metals, and they can evolve resistance via mechanisms that are also involved in antibiotic resistance. Understanding whether susceptibility to different types of antibacterials is non‐randomly associated across natural and clinical bacteria is therefore important for predicting the spread of resistance, yet there is no consensus about the extent of such associations or underlying mechanisms. We tested for associations between susceptibility phenotypes of 93 natural and clinical Escherichia coli isolates to various NAAs and antibiotics. Across all compound combinations, we detected a small number of non‐random associations, including a trio of positive associations among chloramphenicol, triclosan and benzalkonium chloride. We investigated genetic mechanisms that can explain such associations using genomic information, genetic knockouts and experimental evolution. This revealed some mutations that are selected for by experimental exposure to one compound and confer cross‐resistance to other compounds. Surprisingly, these interactions were asymmetric: selection for chloramphenicol resistance conferred cross‐resistance to triclosan and benzalkonium chloride, but selection for triclosan resistance did not confer cross‐resistance to other compounds. These results identify genetic changes involved in variable cross‐resistance across antibiotics and NAAs, potentially contributing to associations in natural and clinical bacteria.

The Ryanodine Receptor Contributes to the Lysophosphatidylcholine-Induced Mineralization in Valvular Interstitial Cells - Reid L. Wilson; Christopher B. Sylvester; Dena C. Wiltz; Aditya Kumar; Tahir H. Malik; Joel D. Morrisett; K. Jane Grande-Allen (Cardiovascular Engineering and Technology, 2020)

Sierra Nevada mountain lake microbial communities are structured by temperature, resources and geographic location - Marika A. Schulhof; Andrew E. Allen; Eric E. Allen; Natalie Mladenov; John P. McCrow; Natalie T. Jones; Jessica Blanton; Hamanda B. Cavalheri; Drishti Kaul; Celia C. Symons; Jonathan B. Shurin (Molecular Ecology, 2020)
Warming, eutrophication (nutrient fertilization) and brownification (increased loading of allochthonous organic matter) are three global trends impacting lake ecosystems. However, the independent and synergistic effects of resource addition and warming on autotrophic and heterotrophic microorganisms are largely unknown. In this study, we investigate the independent and interactive effects of temperature, dissolved organic carbon (DOC, both allochthonous and autochthonous) and nitrogen (N) supply, in addition to the effect of spatial variables, on the composition, richness, and evenness of prokaryotic and eukaryotic microbial communities in lakes across elevation and N deposition gradients in the Sierra Nevada mountains of California, USA. We found that both prokaryotic and eukaryotic communities are structured by temperature, terrestrial (allochthonous) DOC and latitude. Prokaryotic communities are also influenced by total and aquatic (autochthonous) DOC, while eukaryotic communities are also structured by nitrate. Additionally, increasing N availability was associated with reduced richness of prokaryotic communities, and both lower richness and evenness of eukaryotes. We did not detect any synergistic or antagonistic effects as there were no interactions among temperature and resource variables. Together, our results suggest that (a) organic and inorganic resources, temperature, and geographic location (based on latitude and longitude) independently influence lake microbial communities; and (b) increasing N supply due to atmospheric N deposition may reduce richness of both prokaryotic and eukaryotic microbes, probably by reducing niche dimensionality. Our study provides insight into abiotic processes structuring microbial communities across environmental gradients and their potential roles in material and energy fluxes within and between ecosystems.

Contrasting bacteriome of the hornwort Leiosporoceros dussii in two nearby sites with emphasis on the hornwort-cyanobacterial symbiosis - R. Bouchard; G. Peñaloza-Bojacá; S. Toupin; Y. Guadalupe; J. Gudiño; N. Salazar Allen; F. W. Li; J. C. Villarreal A. (Symbiosis, 2020)

Evaluation of Australian Tsunami Warning Thresholds Using Inundation Modelling - Diana J. M. Greenslade; Burak Uslu; Stewart C. R. Allen; Claire L. Kain; Kaya M. Wilson; Hannah E. Power (Pure and Applied Geophysics, 2020)

Dual-Targeted Delivery of Nanoparticles Encapsulating Paclitaxel and Everolimus: a Novel Strategy to Overcome Breast Cancer Receptor Heterogeneity - Loujin Houdaihed; James C. Evans; Christine Allen (Pharmaceutical Research, 2020)

The use of adverse outcome pathways in the safety evaluation of food additives - Mathieu Vinken; Nynke Kramer; Timothy E. H. Allen; Yvette Hoffmans; Natalie Thatcher; Sara Levorato; Heinz Traussnig; Stefan Schulte; Alan Boobis; Anette Thiel; Ivonne M. C. M. Rietjens (Archives of Toxicology, 2020)
In the last decade, adverse outcome pathways have been introduced in the fields of toxicology and risk assessment of chemicals as pragmatic tools with broad application potential. While their use in the pharmaceutical and cosmetics sectors has been well documented, their application in the food area remains largely unexplored. In this respect, an expert group of the International Life Sciences Institute Europe has recently explored the use of adverse outcome pathways in the safety evaluation of food additives. A key activity was the organization of a workshop, gathering delegates from the regulatory, industrial and academic areas, to discuss the potentials and challenges related to the application of adverse outcome pathways in the safety assessment of food additives. The present paper describes the outcome of this workshop followed by a number of critical considerations and perspectives defined by the International Life Sciences Institute Europe expert group.

Lessons learned from public participation in hydrologic engineering projects - J. R. Etheridge; A. K. Manda; C. Grace-McCaskey; T. Allen; H. Hao (Hydrological Sciences Journal, 2020)

Bound manganese oxides capable of reducing the bacteriochlorophyll dimer of modified reaction centers from Rhodobacter sphaeroides - Eduardo Espiritu; Kori D. Chamberlain; JoAnn C. Williams; James P. Allen (Photosynthesis Research, 2020)

Host testing of Eadya daenerys, a potential biological control agent for the invasive chrysomelid pest Paropsis charybdis, predicts host specificity to eucalypt-leaf feeding Paropsina - T. M. Withers; C. L. Todoroki; G. R. Allen; A. R. Pugh; B. A. Gresham (BioControl, 2020)

A likely increase in fine particulate matter and premature mortality under future climate change - S. Park; R. J. Allen; C. H. Lim (Air Quality, Atmosphere & Health, 2020)
Climate change modulates the concentration of fine particulate matter (PM 2.5 ) via modifying atmospheric circulation, temperature, and the hydrological cycle. Furthermore, PM 2.5 is associated with cardiopulmonary diseases and premature mortality. Here, we use seven models to assess the response of PM 2.5 to end of the twenty-first century climate change under Representative Concentration Pathway 8.5, and the corresponding impact on premature mortality. The majority of models yield an increase in both PM 2.5 and premature mortality associated with lung cancer and cardiopulmonary disease in all world regions except Africa. These results are robust across five different future population projections, although the magnitude of premature deaths can vary by up to a factor of two. Much larger uncertainty is related to uncertainty in model physics and the representation of aerosol processes. Although our analysis requires several assumptions related to future population estimates, as well as the concentration-response function, results suggest that future emission reductions are necessary to avoid the likely health risks associated with increasing PM 2.5 in a warmer world.

Compositional turnover and variation in Eemian pollen sequences in Europe - Vivian A. Felde; Suzette G. A. Flantua; Cathy R. Jenks; Blas M. Benito; Jacques-Louis de Beaulieu; Petr Kuneš; Donatella Magri; Dorota Nalepka; Bjørg Risebrobakken; Cajo J. F. ter Braak; Judy R. M. Allen; Wojciech Granoszewski; et al. (Vegetation History and Archaeobotany, 2020)

Saving the Manx Shearwater Flea Ceratophyllus (Emmareus) fionnus (Insecta: Siphonaptera): The Road to Developing a Recovery Plan for a Threatened Ectoparasite - Mackenzie L. Kwak; Allen C. G. Heath; Ricardo L. Palma (Acta Parasitologica, 2019)

Correction to: Saving the Manx Shearwater Flea Ceratophyllus (Emmareus) fionnus (Insecta: Siphonaptera): The Road to Developing a Recovery Plan for a Threatened Ectoparasite - Mackenzie L. Kwak; Allen C. G. Heath; Ricardo L. Palma (Acta Parasitologica, 2019)

Impacts of broadband sound on silver (Hypophthalmichthys molitrix) and bighead (H. nobilis) carp hearing thresholds determined using auditory evoked potential audiometry - Andrew C. Nissen; Brooke J. Vetter; Loranzie S. Rogers; Allen F. Mensinger (Fish Physiology and Biochemistry, 2019)

Slow-Release Doxorubicin Pellets Generate Myocardial Cardiotoxic Changes in Mice Without Significant Systemic Toxicity - Bradley D. Allen; Zhuoli Zhang; Nivedita K. Naresh; Sol Misener; Daniele Procissi; James C. Carr (Cardiovascular Toxicology, 2019)

Lichen conservation in North America: a review of current practices and research in Canada and the United States - Jessica L. Allen; R. Troy McMullin; Erin A. Tripp; James C. Lendemer (Biodiversity and Conservation, 2019)

Male aggression varies with consortship rate and habitat in a dolphin social network - Rebecca A. Hamilton; Teresa Borcuch; Simon J. Allen; William R. Cioffi; Vanni Bucci; Michael Krützen; Richard C. Connor (Behavioral Ecology and Sociobiology, 2019)

Association between vitamin content, plant morphology and geographical origin in a worldwide collection of the orphan crop Gynandropsis gynandra (Cleomaceae) - E. O. Dêêdi Sogbohossou; Dieke Kortekaas; Enoch G. Achigan-Dako; Patrick Maundu; Tsvetelina Stoilova; Allen Van Deynze; Ric C. H. de Vos; M. Eric Schranz (Planta, 2019)

Preface—evaluating the response of critical zone processes to human impacts with sediment source fingerprinting - J. Patrick Laceby; Allen C. Gellis; Alexander J. Koiter; Will H. Blake; Olivier Evrard (Journal of Soils and Sediments, 2019)

Combining sediment fingerprinting with age-dating sediment using fallout radionuclides for an agricultural stream, Walnut Creek, Iowa, USA - Allen C. Gellis; Christopher C. Fuller; Peter Van Metre; Christopher T. Filstrup; Mark D. Tomer; Kevin J. Cole; Timur Y. Sabitov (Journal of Soils and Sediments, 2019)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Early transthoracic echocardiography has useful prognostic value in left-sided native valve endocarditis despite limited diagnostic performance - George S. Heriot; Andrew Newcomb; Jonathan Darby; Andrew Wilson; Steven Y. C. Tong; Allen C. Cheng; Danny Liew (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Characterizing the coverage of critical effects relevant in the safety evaluation of food additives by AOPs - Nynke I. Kramer; Yvette Hoffmans; Siyao Wu; Anette Thiel; Natalie Thatcher; Timothy E. H. Allen; Sara Levorato; Heinz Traussnig; Stefan Schulte; Alan Boobis; Ivonne M. C. M. Rietjens; Mathieu Vinken (Archives of Toxicology, 2019)

Multiscale patterns of rarity in fungi, inferred from fruiting records - Alan C. Gange; Lewis P. Allen; Aline Nussbaumer; Edward G. Gange; Carrie Andrew; Simon Egli; Beatrice Senn‐Irlet; Lynne Boddy (Global Ecology and Biogeography, 2019)
Aim It is unknown whether fungi show similar trends to other organisms in their macroecological patterns of abundance and spatial distribution. Here, we investigated fungal abundance–occupancy relationships to determine whether fungi that are common at a local scale tend to be more widely distributed. Location UK and Switzerland. Time period 1950–2014. Major taxa studied Fungi. Methods We used a local data set of fruiting records of 2,319 species in the UK, accumulated over 65 years, and one from Switzerland of 319 species, spanning 32 years. Using the number of records and occurrence as proxies for abundance, in each case we examined the form of species and rank abundance distributions and compared these with distributions of records in the national databases over the same time. We plotted relationships of the local number of records and regional occupancy and calculated multiscale indices of rarity for all fungal species. Results There was a remarkable congruence in the patterns found in the UK and Switzerland. Regional assemblages are characterized by many rare species, whereas few are common (fitting the lognormal distribution). However, at local scales, distributions best fitted a power law, suggesting that habitat availability or dispersal processes might play important roles. Fungi with a high number of local records are densely distributed nationally, but unlike other organisms, locally rare fungi may also be densely distributed at a wider scale. Main conclusions Fungal fruiting records can be used to infer patterns in fungal distributions. Abundances in local assemblages may be determined by the position of the assemblage in the overall geographical range of each species, dispersal ability and environmental filtering. We advocate the use of multiscale approaches to rarity in future fungal sampling programmes, to provide more reliable information for future conservation policy decisions and fungal biogeography.

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

An Evaluation of Modelled Tsunami Arrival Times - Diana J. M. Greenslade; Robert I. Greenwood; Stewart C. R. Allen (Pure and Applied Geophysics, 2019)

Long-term changes in the primary productivity of migratory caribou (Rangifer tarandus) calving grounds and summer pasture on the Quebec-Labrador Peninsula (Northeastern Canada): the mixed influences of climate change and caribou herbivory - Allen Brett Campeau; Gregory J. M. Rickbeil; Nicholas C. Coops; Steeve D. Côté (Polar Biology, 2019)

Feather mercury concentrations in North American raptors sampled at migration monitoring stations - Ryan P. Bourbour; Breanna L. Martinico; Joshua T. Ackerman; Mark P. Herzog; Angus C. Hull; Allen M. Fish; Joshua M. Hull (Ecotoxicology, 2019)

Non-Destructive Reflectance Mapping of Collagen Fiber Alignment in Heart Valve Leaflets - Will Goth; Sam Potter; Alicia C. B. Allen; Janet Zoldan; Michael S. Sacks; James W. Tunnell (Annals of Biomedical Engineering, 2019)

Neuronal nitric oxide synthase activity mediates Lycium barbarum polysaccharides-enhanced sexual performance without stimulating noncontact erection in rats - Andy C. Huang; Jia-Min Wu; Ya-Han Chang; Navneet Kumar Dubey; Allen W. Chiu; Chien-Yu Yeh; Tung-Hu Tsai; Kuei-Ying Yeh (Psychopharmacology, 2019)

Enhancement of gasworks groundwater remediation by coupling a bio-electrochemical and activated carbon system - Panagiotis Kirmizakis; Rory Doherty; Carlos A. Mendonça; Ricardo Costeira; Chris C. R. Allen; Ulrich S. Ofterdinger; Leonid Kulakov (Environmental Science and Pollution Research, 2019)

Global patterns of body size evolution in squamate reptiles are not driven by climate - Alex Slavenko; Anat Feldman; Allen Allison; Aaron M. Bauer; Monika Böhm; Laurent Chirio; Guarino R. Colli; Indraneil Das; Tiffany M. Doan; Matthew LeBreton; Marcio Martins; Danny Meirte; et al. (Global Ecology and Biogeography, 2019)
Aim Variation in body size across animal species underlies most ecological and evolutionary processes shaping local‐ and large‐scale patterns of biodiversity. For well over a century, climatic factors have been regarded as primary sources of natural selection on animal body size, and hypotheses such as Bergmann's rule (the increase of body size with decreasing temperature) have dominated discussions. However, evidence for consistent climatic effects, especially among ectotherms, remains equivocal. Here, we test a range of key hypotheses on climate‐driven size evolution in squamate reptiles across several spatial and phylogenetic scales. Location Global. Time period Extant. Major taxa studied Squamates (lizards and snakes). Methods We quantified the role of temperature, precipitation, seasonality and net primary productivity as drivers of body mass across ca. 95% of extant squamate species (9,733 spp.). We ran spatial autoregressive models of phylogenetically corrected median mass per equal‐area grid cell. We ran models globally, across separate continents and for major squamate clades independently. We also performed species‐level analyses using phylogenetic generalized least square models and linear regressions of independent contrasts of sister species. Results Our analyses failed to identify consistent spatial patterns in body size as a function of our climatic predictors. Nearly all continent‐ and family‐level models differed from one another, and species‐level models had low explanatory power. Main conclusions The global distribution of body mass among living squamates varies independently from the variation in multiple components of climate. Our study, the largest in spatial and taxonomic scale conducted to date, reveals that there is little support for a universal, consistent mechanism of climate‐driven size evolution within squamates.

Using IUCN criteria to perform rapid assessments of at-risk taxa - Tom D. Le Breton; Heidi C. Zimmer; Rachael V. Gallagher; Michelle Cox; Stuart Allen; Tony D. Auld (Biodiversity and Conservation, 2019)

How commercial fishing effort is managed - Christopher M. Anderson; Melissa J. Krigbaum; Martin C. Arostegui; Megan L. Feddern; John Zachary Koehn; Peter T. Kuriyama; Christina Morrisett; Caitlin I. Allen Akselrud; Melanie J. Davis; Courtney Fiamengo; Ava Fuller; Qi Lee; et al. (Fish and Fisheries, 2019)
Wild capture fisheries produce 90 million tonnes of food each year and have the potential to provide sustainable livelihoods for nearly 40 million people around the world ( http://www.fao.org/3/a-i5555e.pdf ). After decades of overfishing since industrialization, many global fish stocks have recovered, a change brought about through effective management. We provide a synthetic overview of three approaches that managers use to sustain stocks: regulating catch and fishing mortality, regulating effort and regulating spatial access. Within each of these approaches, we describe common restrictions, how they alter incentives to change fishing behaviour, and the resultant ecological, economic and community‐level outcomes. For each approach, we present prominent case‐studies that illustrate behaviour and the corresponding performance. These case‐studies show that sustaining target stocks requires a hard limit on fishing mortality under most conditions, but that additional measures are required to generate economic benefits. Different systems for allocation allow stakeholder communities to strike a locally acceptable balance between profitability and employment.

The Journey to AAPS 2020: a Reflection from Strategic Planning to PharmSci 360 - Joseph W. Polli; Christopher R. McCurdy; Dale Eric Wurster; Binodh S. DeSilva; Annette Bak; Reina Bendayan; Bernd Meibohm; Allen C. Templeton; William Weiser (The AAPS Journal, 2019)

Thioredoxin overexpression in both the cytosol and mitochondria accelerates age-related disease and shortens lifespan in male C57BL/6 mice - Geneva M. Cunningham; Lisa C. Flores; Madeline G. Roman; Christie Cheng; Sara Dube; Colton Allen; Joseph M. Valentine; Gene B. Hubbard; Yidong Bai; Thomas L. Saunders; Yuji Ikeno (GeroScience, 2018)

A review of the global diversity and natural history of stalked jellyfishes (Cnidaria, Staurozoa) - Lucília S. Miranda; Claudia E. Mills; Yayoi M. Hirano; Allen G. Collins; Antonio C. Marques (Marine Biodiversity, 2018)

Geochronology and geochemistry of the Devonian Gumbardo Formation (Adavale Basin): evidence for cratonisation of the Central Thomson Orogen by the Early Devonian - P. Asmussen; S. E. Bryan; C. M. Allen; D. J. Purdy (Australian Journal of Earth Sciences, 2018)

Crustal and thermal structure of the Thomson Orogen: constraints from the geochemistry, zircon U–Pb age, and Hf and O isotopes of subsurface granitic rocks - C. Siégel; S. E. Bryan; C. M. Allen; D. J. Purdy; A. J. Cross; I. T. Uysal; D. A. Gust (Australian Journal of Earth Sciences, 2018)

The Journey to AAPS 2020: a Reflection from Strategic Planning to PharmSci 360 - Joseph W. Polli; Christopher R. McCurdy; Dale Eric Wurster; Binodh S. DeSilva; Annette Bak; Reina Bendayan; Bernd Meibohm; Allen C. Templeton; William Weiser (AAPS PharmSciTech, 2018)

Bacteria and viruses in the nasopharynx immediately prior to onset of acute lower respiratory infections in Indigenous Australian children - Heidi C. Smith-Vaughan; Michael J. Binks; Jemima Beissbarth; Anne B. Chang; Gabrielle B. McCallum; Ian M. Mackay; Peter S. Morris; Robyn L. Marsh; Paul J. Torzillo; Danielle F. Wurzel; Keith Grimwood; Elizabeth Nosworthy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Discovery of a novel iflavirus sequence in the eastern paralysis tick Ixodes holocyclus - Caitlin A. O’Brien; Sonja Hall-Mendelin; Jody Hobson-Peters; Georgia Deliyannis; Andy Allen; Ala Lew-Tabor; Manuel Rodriguez-Valle; Dayana Barker; Stephen C. Barker; Roy A. Hall (Archives of Virology, 2018)

Phylogeny and morphological evolution of the so‐called bougainvilliids (Hydrozoa, Hydroidolina) - María A. Mendoza‐Becerril; Adrian José Jaimes‐Becerra; Allen G. Collins; Antonio C. Marques (Zoologica Scripta, 2018)
We present phylogenetic analyses (parsimony, maximum likelihood and Bayesian inference) for 69 lineages of anthoathecate hydroids based on 18 morphological characters (12 proposed for the first time) plus mitochondrial (16S and COI ) and nuclear (18S and 28S) molecular markers. This study aims to test the monophyly of the present concept of the family Bougainvilliidae, assessing its phylogenetic position within Hydroidolina. Our working hypothesis is used as a context for inferring the evolution of certain morphological characters, focusing on the exoskeleton. Our results shed light on some phylogenetic uncertainties within Hydroidolina, delimiting eight well‐supported linages, viz. Hydroidolina, Siphonophorae, Leptothecata, Aplanulata, Filifera II , Filifera III , Capitata and Pseudothecata taxon novum , the latter supported by four morphological synapomorphies. The monophyly of several families was not supported, viz. Bougainvilliidae, Cordylophoridae, Oceaniidae, Rathkeidae and Pandeidae. Some of the genera typically considered in Bougainvilliidae, including Bougainvillia , fell into the clade Pseudothecata, which is consistently reconstructed as the sister group of Leptothecata. We formally suggest that Dicoryne be removed from Bougainvilliidae and placed in the resurrected family Dicorynidae. The exoskeleton was a key feature in the diversification of Hydroidolina, especially with the transition from the bare hydranth to one completely enveloped within the exoskeleton. In this context, bougainvilliids exhibit several intermediate states in the development of the exosarc. Although the concatenated analysis unravels some interesting hypotheses, taxon sampling is still deficient and therefore more data are necessary for achieving a more complete understanding of the evolution and ecology of bougainvilliids and their allies.

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

Intermittent convection-enhanced delivery of GDNF into rhesus monkey putamen: absence of local or cerebellar toxicity - Matthias Luz; Philip C. Allen; John Bringas; Chris Boiko; Diane E. Stockinger; Kristen J. Nikula; Owen Lewis; Max Woolley; H. Christian Fibiger; Krystof Bankiewicz; Erich Mohr (Archives of Toxicology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Detrital zircon U–Pb geochronology of Permian strata in the Galilee Basin, Queensland, Australia - L. J. Phillips; C. Verdel; C. M. Allen; J. S. Esterle (Australian Journal of Earth Sciences, 2018)

Mortality risk and PM2.5 air pollution in the USA: an analysis of a national prospective cohort - C. Arden Pope; Majid Ezzati; John B. Cannon; Ryan T. Allen; Michael Jerrett; Richard T. Burnett (Air Quality, Atmosphere & Health, 2018)

Diel habitat selection of largemouth bass following woody structure installation in Table Rock Lake, Missouri - J. M. Harris; C. P. Paukert; S. C. Bush; M. J. Allen; M. J. Siepker (Fisheries Management and Ecology, 2018)
Largemouth bass Micropterus salmoides (Lacepède) use of installed habitat structure was evaluated in a large Midwestern USA reservoir to determine whether or not these structures were used in similar proportion to natural habitats. Seventy largemouth bass (>380 mm total length) were surgically implanted with radio transmitters and a subset was relocated monthly during day and night for one year. The top habitat selection models (based on Akaike's information criterion) suggest largemouth bass select 2–4 m depths during night and 4–7 m during day, whereas littoral structure selection was similar across diel periods. Largemouth bass selected boat docks at twice the rate of other structures. Installed woody structure was selected at similar rates to naturally occurring complex woody structure, whereas both were selected at a higher rate than simple woody structure. The results suggest the addition of woody structure may concentrate largemouth bass and mitigate the loss of woody habitat in a large reservoir.

Clinical variation in the use of echocardiography in Staphylococcus aureus bacteraemia: a multi-centre cohort study - George S. Heriot; Steven Y. C. Tong; Allen C. Cheng; Irani Thevarajan; Michele R. Levinson; Kumar Visvanathan; Danny Liew (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Advances in Silviculture of Intensively Managed Plantations - Rafael A. Rubilar; H. Lee Allen; Thomas R. Fox; Rachel L. Cook; Timothy J. Albaugh; Otávio C. Campoe (Current Forestry Reports, 2018)

Redescription of the kiwi tick Ixodes anatis (Acari: Ixodidae) from New Zealand, with notes on its biology - Mackenzie L. Kwak; Allen C. G. Heath (Experimental and Applied Acarology, 2018)

A review of the associations between single nucleotide polymorphisms in taste receptors, eating behaviors, and health - Elie Chamoun; David M. Mutch; Emma Allen-Vercoe; Andrea C. Buchholz; Alison M. Duncan; Lawrence L. Spriet; Jess Haines; David W. L. Ma (Critical Reviews in Food Science and Nutrition, 2018)

Effect of repeated abstinence on chronic ethanol self-administration in the rhesus monkey - Daicia C. Allen; Steven W. Gonzales; Kathleen A. Grant (Psychopharmacology, 2018)

Mortality risks during extreme temperature events (ETEs) using a distributed lag non-linear model - Michael J. Allen; Scott C. Sheridan (International Journal of Biometeorology, 2018)

Fear affects parental care, which predicts juvenile survival and exacerbates the total cost of fear on demography - Blair P. Dudeck; Michael Clinchy; Marek C. Allen; Liana Y. Zanette (Ecology, 2018)
Fear itself (perceived predation risk) can affect wildlife demography, but the cumulative impact of fear on population dynamics is not well understood. Parental care is arguably what most distinguishes birds and mammals from other taxa, yet only one experiment on wildlife has tested fear effects on parental food provisioning and the repercussions this has for the survival of dependent offspring, and only during early‐stage care. We tested the effect of fear on late‐stage parental care of mobile dependent offspring, by locating radio‐tagged Song Sparrow fledglings and broadcasting predator or non‐predator playbacks in their vicinity, measuring their parent's behavior and their own, and tracking the offspring's survival to independence. Fear significantly reduced late‐stage parental care, and parental fearfulness (as indexed by their reduction in provisioning when hearing predators) significantly predicted their offspring's condition and survival. Combining results from this experiment with that on early‐stage care, we project that fear itself is powerful enough to reduce late‐stage survival by 24%, and cumulatively reduce the number of young reaching independence by more than half, 53%. Experiments in invertebrate and aquatic systems demonstrate that fear is commonly as important as direct killing in affecting prey demography, and we suggest focusing more on fear effects and on offspring survival will reveal the same for wildlife.

Evolution of the claustrum in Cnidaria: comparative anatomy reveals that it is exclusive to some species of Staurozoa and absent in Cubozoa - Lucília S. Miranda; Jimena García-Rodríguez; Allen G. Collins; André C. Morandini; Antonio C. Marques (Organisms Diversity & Evolution, 2017)

Regulatory experience of TOPS: an internet-based system to prevent healthy subjects from over-volunteering for UK clinical trials - C. Allen; G. Francis; J. Martin; M. Boyce (European Journal of Clinical Pharmacology, 2017)

Erratum to: A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)

Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic - Karen A. Bjorndal; Alan B. Bolten; Milani Chaloupka; Vincent S. Saba; Cláudio Bellini; Maria A. G. Marcovaldi; Armando J. B. Santos; Luis Felipe Wurdig Bortolon; Anne B. Meylan; Peter A. Meylan; Jennifer Gray; Robert Hardy; et al. (Global Change Biology, 2017)
Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio‐indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas , which are long‐lived, highly migratory, primarily herbivorous mega‐consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled for sea turtles, has 9690 growth increments from 30 sites from Bermuda to Uruguay from 1973 to 2015. Using generalized additive mixed models, we evaluated covariates that could affect growth rates; body size, diet, and year have significant effects on growth. Growth increases in early years until 1999, then declines by 26% to 2015. The temporal (year) effect is of particular interest because two carnivorous species of sea turtles—hawksbills, Eretmochelys imbricata, and loggerheads, Caretta caretta —exhibited similar significant declines in growth rates starting in 1997 in the West Atlantic, based on previous studies. These synchronous declines in productivity among three sea turtle species across a trophic spectrum provide strong evidence that an ecological regime shift ( ERS ) in the Atlantic is driving growth dynamics. The ERS resulted from a synergy of the 1997/1998 El Niño Southern Oscillation ( ENSO )—the strongest on record—combined with an unprecedented warming rate over the last two to three decades. Further support is provided by the strong correlations between annualized mean growth rates of green turtles and both sea surface temperatures ( SST ) in the West Atlantic for years of declining growth rates ( r = −.94) and the Multivariate ENSO Index ( MEI ) for all years ( r = .74). Granger‐causality analysis also supports the latter finding. We discuss multiple stressors that could reinforce and prolong the effect of the ERS . This study demonstrates the importance of region‐wide collaborations.

A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)
Uterine fibroids are benign tumors of the uterus affecting up to 77% of women by menopause. They are the leading indication for hysterectomy, and account for $34 billion annually in the United States. Race/ethnicity and age are the strongest known risk factors. African American (AA) women have higher prevalence, earlier onset, and larger and more numerous fibroids than European American women. We conducted a multi-stage genome-wide association study (GWAS) of fibroid risk among AA women followed by in silico genetically predicted gene expression profiling of top hits. In Stage 1, cases and controls were confirmed by pelvic imaging, genotyped and imputed to 1000 Genomes. Stage 2 used self-reported fibroid and GWAS data from 23andMe, Inc. and the Black Women’s Health Study. Associations with fibroid risk were modeled using logistic regression adjusted for principal components, followed by meta-analysis of results. We observed a significant association among 3399 AA cases and 4764 AA controls at rs739187 (risk-allele frequency = 0.27) in CYTH4 (OR (95% confidence interval) = 1.23 (1.16–1.30), p value = 7.82 × 10 −9 ). Evaluation of the genetic association results with MetaXcan identified lower predicted gene expression of CYTH4 in thyroid tissue as significantly associated with fibroid risk ( p value = 5.86 × 10 −8 ). In this first multi-stage GWAS for fibroids among AA women, we identified a novel risk locus for fibroids within CYTH4 that impacts gene expression in thyroid and has potential biological relevance for fibroids.

The rise in global atmospheric CO2, surface temperature, and sea level from emissions traced to major carbon producers - B. Ekwurzel; J. Boneham; M. W. Dalton; R. Heede; R. J. Mera; M. R. Allen; P. C. Frumhoff (Climatic Change, 2017)

High N, dry: Experimental nitrogen deposition exacerbates native shrub loss and nonnative plant invasion during extreme drought - Justin M. Valliere; Irina C. Irvine; Louis Santiago; Edith B. Allen (Global Change Biology, 2017)
Hotter, longer, and more frequent global change‐type drought events may profoundly impact terrestrial ecosystems by triggering widespread vegetation mortality. However, severe drought is only one component of global change, and ecological effects of drought may be compounded by other drivers, such as anthropogenic nitrogen (N) deposition and nonnative plant invasion. Elevated N deposition, for example, may reduce drought tolerance through increased plant productivity, thereby contributing to drought‐induced mortality. High N availability also often favors invasive, nonnative plant species, and the loss of woody vegetation due to drought may create a window of opportunity for these invaders. We investigated the effects of multiple levels of simulated N deposition on a Mediterranean‐type shrubland plant community in southern California from 2011 to 2016, a period coinciding with an extreme, multiyear drought in the region. We hypothesized that N addition would increase native shrub productivity, but that this would increase susceptibility to drought and result in increased shrub loss over time. We also predicted that N addition would favor nonnatives, especially annual grasses, leading to higher biomass and cover of these species. Consistent with these hypotheses, we found that high N availability increased native shrub canopy loss and mortality, likely due to the higher productivity and leaf area and reduced water‐use efficiency we observed in shrubs subject to N addition. As native shrub cover declined, we also observed a concomitant increase in cover and biomass of nonnative annuals, particularly under high levels of experimental N deposition. Together, these results suggest that the impacts of extended drought on shrubland ecosystems may be more severe under elevated N deposition, potentially contributing to the widespread loss of native woody species and vegetation‐type conversion.

Supporting sustainability initiatives through biometeorology education and training - Michael J. Allen; Jennifer Vanos; David M. Hondula; Daniel J. Vecellio; David Knight; Hamed Mehdipoor; Rebekah Lucas; Chris Fuhrmann; Hanna Lokys; Angela Lees; Sheila Tavares Nascimento; Andrew C. W. Leung; et al. (International Journal of Biometeorology, 2017)

Sixty years of the International Journal of Biometeorology - Scott C. Sheridan; Michael J. Allen (International Journal of Biometeorology, 2017)

The oral microbiota in patients with pancreatic cancer, patients with IPMNs, and controls: a pilot study - Sara H. Olson; Jaya Satagopan; Youming Xu; Lilan Ling; Siok Leong; Irene Orlow; Amethyst Saldia; Peter Li; Pamela Nunes; Vincent Madonia; Peter J. Allen; Eileen O’Reilly; et al. (Cancer Causes & Control, 2017)

Revealing the global importance of isoprene metabolism by marine bacteria - Christopher C. R. Allen (Environmental Microbiology, 2017)

Papua New Guinea terrestrial‐vertebrate richness: elevation matters most for all except reptiles - Oliver Tallowin; Allen Allison; Adam C. Algar; Fred Kraus; Shai Meiri (Journal of Biogeography, 2017)
Aims To examine species richness patterns in Papua New Guinea's terrestrial vertebrates and test for geographical congruence between the four classes, and between lizard and snake subgroups. To assess the environmental correlates of Papua New Guinean terrestrial‐vertebrate richness, and contrast effects of varying analytical resolution and correction for spatial autocorrelation. We predict congruence in the bird, mammal and to a lesser extent amphibian richness, with weak congruence or incongruence between reptiles and the other taxonomic groups. We further predict these patterns will stem from relative or in the case of reptiles dissimilar, correlative trends with environmental predictors such as elevation and temperature. Location Papua New Guinea. Methods Having created and updated distribution maps for reptiles, we compare them with known ranges of amphibians, birds and mammals and generate species richness grids at quarter‐, half‐ and one‐ degree spatial resolutions. We examine congruence in species richness between vertebrate groups and between reptile subgroups. We employed spreading‐dye models to simulate species richness according to eight environmental predictors and one random model. We accounted for spatial autocorrelation in all analyses. Results Papua New Guinean amphibian, bird and mammal species richness are spatially congruent, a trend which strengthens with decreasing spatial resolution. Reptiles and the lizard and snake subgroups reveal remarkably different spatial‐richness trends. Elevational predictors, particularly elevational range at coarse resolutions, provide the strongest correlates of species richness. Terrestrial‐vertebrate richness increases with elevation, whereas reptile richness decreases. Main conclusions Congruent species richness gradients in Papua New Guinea are observed in most terrestrial vertebrates, except reptiles. Topographic heterogeneity and associated climatic clines promote diversity in most terrestrial vertebrates but appear to strongly constrain reptile diversity. The topographical complexity and climatic stratification of tropical mountains clearly present a wealth of opportunities for diversification in most terrestrial vertebrate groups. As reptiles are strongly constrained by temperature, tropical mountains present more of a diversification barrier for them.

Evaluating the impact of adjusting surface temperature derived from Landsat 7 ETM+ in crop evapotranspiration assessment using high-resolution airborne data - J. M. Ramírez-Cuesta; A. Kilic; R. Allen; C. Santos; I. J. Lorite (International Journal of Remote Sensing, 2017)

Social setting, social rank and HPA axis response in cynomolgus monkeys - Vanessa A. Jimenez; Daicia C. Allen; Megan N. McClintick; Kathleen A. Grant (Psychopharmacology, 2017)

Cognitive Effects of Air Pollution Exposures and Potential Mechanistic Underpinnings - J. L. Allen; C. Klocke; K. Morris-Schaffer; K. Conrad; M. Sobolewski; D. A. Cory-Slechta (Current Environmental Health Reports, 2017)

High pCO2 and elevated temperature reduce survival and alter development in early life stages of the tropical sea hare Stylocheilus striatus - Eric J. Armstrong; Trevor R. Allen; Maeva Beltrand; Vaimiti Dubousquet; Jonathon H. Stillman; Suzanne C. Mills (Marine Biology, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Seasonal spatial patterns of projected anthropogenic warming in complex terrain: a modeling study of the western US - David E. Rupp; Sihan Li; Philip W. Mote; Karen M. Shell; Neil Massey; Sarah N. Sparrow; David C. H. Wallom; Myles R. Allen (Climate Dynamics, 2017)

Acrolein Inhalation Alters Myocardial Synchrony and Performance at and Below Exposure Concentrations that Cause Ventilatory Responses - Leslie C. Thompson; Allen D. Ledbetter; Najwa Haykal-Coates; Wayne E. Cascio; Mehdi S. Hazari; Aimen K. Farraj (Cardiovascular Toxicology, 2017)

Tree mortality across biomes is promoted by drought intensity, lower wood density and higher specific leaf area - Sarah Greenwood; Paloma Ruiz‐Benito; Jordi Martínez‐Vilalta; Francisco Lloret; Thomas Kitzberger; Craig D. Allen; Rod Fensham; Daniel C. Laughlin; Jens Kattge; Gerhard Bönisch; Nathan J. B. Kraft; Alistair S. Jump (Ecology Letters, 2017)
Drought events are increasing globally, and reports of consequent forest mortality are widespread. However, due to a lack of a quantitative global synthesis, it is still not clear whether drought‐induced mortality rates differ among global biomes and whether functional traits influence the risk of drought‐induced mortality. To address these uncertainties, we performed a global meta‐analysis of 58 studies of drought‐induced forest mortality. Mortality rates were modelled as a function of drought, temperature, biomes, phylogenetic and functional groups and functional traits. We identified a consistent global‐scale response, where mortality increased with drought severity [log mortality (trees trees −1 year −1 ) increased 0.46 (95% CI = 0.2–0.7) with one SPEI unit drought intensity]. We found no significant differences in the magnitude of the response depending on forest biomes or between angiosperms and gymnosperms or evergreen and deciduous tree species. Functional traits explained some of the variation in drought responses between species (i.e. increased from 30 to 37% when wood density and specific leaf area were included). Tree species with denser wood and lower specific leaf area showed lower mortality responses. Our results illustrate the value of functional traits for understanding patterns of drought‐induced tree mortality and suggest that mortality could become increasingly widespread in the future.

Evaluating the accuracy of self-report for the diagnosis of HIV-associated neurocognitive disorder (HAND): defining “symptomatic” versus “asymptomatic” HAND - Lisa C. Obermeit; Jessica Beltran; Kaitlin B. Casaletto; Donald R. Franklin; Scott Letendre; Ronald Ellis; Christine Fennema-Notestine; Florin Vaida; Ann C. Collier; Christina M. Marra; David Clifford; Benjamin Gelman; et al. (Journal of NeuroVirology, 2017)

The invasive ant, Solenopsis invicta, reduces herpetofauna richness and abundance - C. R. Allen; H. E. Birge; J. Slater; E. Wiggers (Biological Invasions, 2017)

The scent of your enemy is my friend? The acquisition of large carnivore scent by a smaller carnivore - Maximilian L. Allen; Micaela S. Gunther; Christopher C. Wilmers (Journal of Ethology, 2017)

Range expansion by Passer montanus in North America - J. L. Burnett; C. P. Roberts; C. R. Allen; M. B. Brown; M. P. Moulton (Biological Invasions, 2017)

Survival probabilities and movements of harbor seals in central California - Suzanne C. Manugian; Denise Greig; Derek Lee; Benjamin H. Becker; Sarah Allen; Mark S. Lowry; James T. Harvey (Marine Mammal Science, 2017)
Harbor seal numbers and population trajectories differ by location in central California. Within San Francisco Bay ( SFB ) counts have been relatively stable since the 1972 Marine Mammal Protection Act, but in coastal areas like Tomales Bay ( TB ), counts increased before stabilizing in the 1990s. Emigration, poor survival, and environmental effects have been hypothesized as contributors to differences between trajectories; however, basic demographic data were not available to evaluate these hypotheses. We monitored 32 radio‐tagged adult females ( SFB n = 17, TB n = 15) for 20 mo (2011–2013), and estimated survival, resight, and movement probabilities using mark‐resight analyses and multistate mark‐resight models. Annual survival probability for both sites was 0.90 (95% CI = 0.18–0.99). Six seals were observed moving between locations resulting in an estimated probability of 0.042 (95% CI = 0.023–0.076) per month equal movement between sites. Resight probability was less in SFB relative to TB , likely due to differential haul‐out access, area surveyed, visibility, and resight effort. Because of wide confidence intervals and low precision of these first estimates of adult female harbor seal survival in California, this demographic must be further examined to dismiss its contribution to differing population trajectories. Using aerial survey data, we estimated 950 harbor seals in SFB (95% CI = 715–1,184) confirming numbers are still stable.

A Pilot Tsunami Inundation Forecast System for Australia - Stewart C. R. Allen; Diana J. M. Greenslade (Pure and Applied Geophysics, 2016)

Glacial lake outburst flood risk in Himachal Pradesh, India: an integrative and anticipatory approach considering current and future threats - S. K. Allen; A. Linsbauer; S. S. Randhawa; C. Huggel; P. Rana; A. Kumari (Natural Hazards, 2016)

Lake outburst and debris flow disaster at Kedarnath, June 2013: hydrometeorological triggering and topographic predisposition - S. K. Allen; P. Rastner; M. Arora; C. Huggel; M. Stoffel (Landslides, 2016)

Do Men Receive Information Required for Shared Decision Making About PSA Testing? Results from a National Survey - Bryan Leyva; Alexander Persoskie; Allison Ottenbacher; Jada G. Hamilton; Jennifer D. Allen; Sarah C. Kobrin; Stephen H. Taplin (Journal of Cancer Education, 2016)

Genetic evidence of peripheral isolation and low diversity in marginal populations of the Acropora hyacinthus complex - Go Suzuki; Shashank Keshavmurthy; Takeshi Hayashibara; Carden C. Wallace; Yoshihisa Shirayama; Chaolun Allen Chen; Hironobu Fukami (Coral Reefs, 2016)

Solutions for ecosystem‐level protection of ocean systems under climate change - Ana M. Queirós; Klaus B. Huebert; Friedemann Keyl; Jose A. Fernandes; Willem Stolte; Marie Maar; Susan Kay; Miranda C. Jones; Katell G. Hamon; Gerrit Hendriksen; Youen Vermard; Paul Marchal; et al. (Global Change Biology, 2016)
The Paris Conference of Parties ( COP 21) agreement renewed momentum for action against climate change, creating the space for solutions for conservation of the ocean addressing two of its largest threats: climate change and ocean acidification ( CCOA ). Recent arguments that ocean policies disregard a mature conservation research field and that protected areas cannot address climate change may be oversimplistic at this time when dynamic solutions for the management of changing oceans are needed. We propose a novel approach, based on spatial meta‐analysis of climate impact models, to improve the positioning of marine protected areas to limit CCOA impacts. We do this by estimating the vulnerability of ocean ecosystems to CCOA in a spatially explicit manner and then co‐mapping human activities such as the placement of renewable energy developments and the distribution of marine protected areas. We test this approach in the NE Atlantic considering also how CCOA impacts the base of the food web which supports protected species, an aspect often neglected in conservation studies. We found that, in this case, current regional conservation plans protect areas with low ecosystem‐level vulnerability to CCOA , but disregard how species may redistribute to new, suitable and productive habitats. Under current plans, these areas remain open to commercial extraction and other uses. Here, and worldwide, ocean conservation strategies under CCOA must recognize the long‐term importance of these habitat refuges, and studies such as this one are needed to identify them. Protecting these areas creates adaptive, climate‐ready and ecosystem‐level policy options for conservation, suitable for changing oceans.

Apolipoprotein E ε4 genotype status is not associated with neuroimaging outcomes in a large cohort of HIV+ individuals - Sarah A. Cooley; Robert H. Paul; Christine Fennema-Notestine; Erin E. Morgan; Florin Vaida; Qianqian Deng; Jie Ashley Chen; Scott Letendre; Ronald Ellis; David B. Clifford; Christina M. Marra; Ann C. Collier; et al. (Journal of NeuroVirology, 2016)

Difference in parenting in two species of burying beetle, Nicrophorus orbicollis and Nicrophorus vespilloides - Kyle M. Benowitz; Elizabeth C. McKinney; Allen J. Moore (Journal of Ethology, 2016)

Valve Interstitial Cells Act in a Pericyte Manner Promoting Angiogensis and Invasion by Valve Endothelial Cells - C. Alexander Arevalos; Jonathan M. Berg; Jacqueline M. V. Nguyen; Elizabeth L. Godfrey; Claudia Iriondo; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2016)

Male density influences mate searching speed and copulation duration in millipedes (Polydesmida: Gigantowales chisholmi) - G. I. Holwell; P. J. D. Allen; F. Goudie; P. E. Duckett; C. J. Painting (Behavioral Ecology and Sociobiology, 2016)

The importance of motivation, weapons, and foul odors in driving encounter competition in carnivores - Maximilian L. Allen; Christopher C. Wilmers; L. Mark Elbroch; Julie M. Golla; Heiko U. Wittmer (Ecology, 2016)
Encounter competition is interference competition in which animals directly contend for resources. Ecological theory predicts the trait that determines the resource holding potential ( RHP ), and hence the winner of encounter competition, is most often body size or mass. The difficulties of observing encounter competition in complex organisms in natural environments, however, has limited opportunities to test this theory across diverse species. We studied the outcome of encounter competition contests among mesocarnivores at deer carcasses in California to determine the most important variables for winning these contests. We found some support for current theory in that body mass is important in determining the winner of encounter competition, but we found that other factors including hunger and species‐specific traits were also important. In particular, our top models were “strength and hunger” and “size and hunger,” with models emphasizing the complexity of variables influencing outcomes of encounter competition. In addition, our wins above predicted ( WAP ) statistic suggests that an important aspect that determines the winner of encounter competition is species‐specific advantages that increase their RHP , as bobcats ( Lynx rufus ) and spotted skunks ( Spilogale gracilis ) won more often than predicted based on mass. In complex organisms, such as mesocarnivores, species‐specific adaptations, including strategic behaviors, aggressiveness, and weapons, contribute to competitive advantages and may allow certain species to take control or defend resources better than others. Our results help explain how interspecific competition shapes the occurrence patterns of species in ecological communities.

Expert consensus on an in vitro approach to assess pulmonary fibrogenic potential of aerosolized nanomaterials - Amy J. Clippinger; Arti Ahluwalia; David Allen; James C. Bonner; Warren Casey; Vincent Castranova; Raymond M. David; Sabina Halappanavar; Jon A. Hotchkiss; Annie M. Jarabek; Monika Maier; William Polk; et al. (Archives of Toxicology, 2016)

The impacts of increasing drought on forest dynamics, structure, and biodiversity in the United States - James S. Clark; Louis Iverson; Christopher W. Woodall; Craig D. Allen; David M. Bell; Don C. Bragg; Anthony W. D'Amato; Frank W. Davis; Michelle H. Hersh; Ines Ibanez; Stephen T. Jackson; Stephen Matthews; et al. (Global Change Biology, 2016)
We synthesize insights from current understanding of drought impacts at stand‐to‐biogeographic scales, including management options, and we identify challenges to be addressed with new research. Large stand‐level shifts underway in western forests already are showing the importance of interactions involving drought, insects, and fire. Diebacks, changes in composition and structure, and shifting range limits are widely observed. In the eastern US , the effects of increasing drought are becoming better understood at the level of individual trees, but this knowledge cannot yet be confidently translated to predictions of changing structure and diversity of forest stands. While eastern forests have not experienced the types of changes seen in western forests in recent decades, they too are vulnerable to drought and could experience significant changes with increased severity, frequency, or duration in drought. Throughout the continental United States, the combination of projected large climate‐induced shifts in suitable habitat from modeling studies and limited potential for the rapid migration of tree populations suggests that changing tree and forest biogeography could substantially lag habitat shifts already underway. Forest management practices can partially ameliorate drought impacts through reductions in stand density, selection of drought‐tolerant species and genotypes, artificial regeneration, and the development of multistructured stands. However, silvicultural treatments also could exacerbate drought impacts unless implemented with careful attention to site and stand characteristics. Gaps in our understanding should motivate new research on the effects of interactions involving climate and other species at the stand scale and how interactions and multiple responses are represented in models. This assessment indicates that, without a stronger empirical basis for drought impacts at the stand scale, more complex models may provide limited guidance.

Development of Dryland Oilseed Production Systems in Northwestern Region of the USA - D. S. Long; F. L. Young; W. F. Schillinger; C. L. Reardon; J. D. Williams; B. L. Allen; W. L. Pan; D. J. Wysocki (BioEnergy Research, 2016)

Advancing Product Quality: a Summary of the Second FDA/PQRI Conference - Lawrence X. Yu; Ilgaz Akseli; Barbara Allen; Gregory Amidon; Tara Gooen Bizjak; Ashley Boam; Margaret Caulk; David Doleski; Joseph Famulare; Adam C. Fisher; Scott Furness; Brian Hasselbalch; et al. (The AAPS Journal, 2016)

Erratum to: Low ambient oxygen prevents atherosclerosis - Ju-Gyeong Kang; Ho Joong Sung; Marcelo J. Amar; Milton Pryor; Alan T. Remaley; Michele D. Allen; Audrey C. Noguchi; Danielle A. Springer; Jaeyul Kwon; Jichun Chen; Ji-hoon Park; Ping-yuan Wang; et al. (Journal of Molecular Medicine, 2016)

Low ambient oxygen prevents atherosclerosis - Ju-Gyeong Kang; Ho Joong Sung; Marcelo J. Amar; Milton Pryor; Alan T. Remaley; Michele D. Allen; Audrey C. Noguchi; Danielle A. Springer; Jaeyul Kwon; Jichun Chen; Ji-hoon Park; Ping-yuan Wang; et al. (Journal of Molecular Medicine, 2016)

Reduction of Ethanol Yield from Switchgrass Infected with Rust Caused by Puccinia emaculata - Virginia R. Sykes; Fred L. Allen; Jonathan R. Mielenz; C. Neal Stewart; Mark T. Windham; Choo Y. Hamilton; Miguel Rodriguez; Kelsey L. Yee (BioEnergy Research, 2016)

Climate change impacts on endemic, high-elevation lichens in a biodiversity hotspot - Jessica L. Allen; James C. Lendemer (Biodiversity and Conservation, 2016)

Evaluating changes in season length, onset, and end dates across the United States (1948–2012) - Michael J. Allen; Scott C. Sheridan (International Journal of Climatology, 2016)
Discussed in a global context, the issue of scale is important to consider as it relates to climate change. As climatological studies utilize temporally and spatially static definitions of seasonal definitions, the understanding of seasonal change may be limited by the way in which seasons are defined. This research serves as a challenge to this perspective by examining the changes in seasons by incorporating variability into the way in which seasons are defined. Temporally and spatially variable seasons were defined based on thresholds of apparent temperature and upper‐level circulation patterns for the period 1948–2012. Using 60 US surface stations, two apparent air temperature metrics were used to define seasons that vary spatially and temporally. Stations represented major cities found in the contiguous United States. A large‐scale circulation approach utilized synoptic categorizations based on 250‐mb geopotential heights from the NCEP‐NCAR reanalysis ( NNR ) as a metric of seasonal delineation. In this method, seasons varied temporally but not spatially. Despite the different methodological approaches, consistent trends were found. Since 1948, late starts of autumn and winter have been observed while earlier onsets of spring and summer have taken place. For the individual stations, the largest shifts occurred along coasts and in larger, more urbanized environments. Individual locations also showed increased variability in start date, and significant changes were found for all four seasons in the circulation approach. Seasons have been shown to be important for a variety of processes including phenological responses and human adaptation to extreme temperature environments; therefore, the consideration of season variability may be appropriate for future climatological research.

Synthesis: comparing effects of resource and consumer fluxes into recipient food webs using meta‐analysis - Daniel C. Allen; Jeff S. Wesner (Ecology, 2016)
Here we synthesize empirical research using meta‐analysis to compare how consumer and resource fluxes affect recipient food webs. We tested the following hypotheses: (H 1 ) The direct effects of resource fluxes (bottom‐up) should be stronger than the direct effects of consumer fluxes (top‐down), because resource fluxes are permanent (do not return to the food web in which they were produced) but consumer fluxes may not be (consumers can leave). (H 2 ) Following H 1 , the indirect effects should attenuate (weaken) more quickly for consumer fluxes than for resource fluxes due to their direct effects being weaker. (H 3 ) The effects of resource fluxes should be stronger when recipient food webs are in different ecosystems than donor food webs due to differences in elevation that accompany cross‐ecosystem food web interfaces, often increasing flux quantity due to gravity, while the effects of consumer fluxes should be stronger when donor and recipient food webs are in the same ecosystem as they should more easily assimilate into the recipient food web. We found no differences in the magnitude of bottom‐up and top‐down direct effects for resource and consumer fluxes, but top‐down direct effects were 122% stronger than top‐down indirect effects. Indirect effects of prey and predator fluxes quickly attenuated while indirect effects of non‐prey resource and herbivore fluxes did not, as the overall direct effects of prey and predator fluxes were 123% and 163% stronger than their indirect effects, respectively. This result suggests that the magnitude of indirect effects decrease as the trophic level of resource and consumer fluxes increases, and also contrasts with results from studies showing in situ top‐down indirect effects are stronger than in situ bottom‐up indirect effects. We found that resource and consumer flux effect sizes were similar when they occurred between ecosystems, but when they occurred within ecosystems predator flux effects were 107% stronger than nutrient flux effects. Finally, we found that observational studies had higher effect sizes than manipulative studies. Future research should focus on how resource and consumer fluxes might interact and generate feedbacks in empirical studies of natural food webs, and what ecological factors might affect their relative strength.

Sex-Specific Patterns in Abundance, Temporary Emigration and Survival of Indo-Pacific Bottlenose Dolphins (Tursiops aduncus) in Coastal and Estuarine Waters - Kate R. Sprogis; Kenneth H. Pollock; Holly C. Raudino; Simon J. Allen; Anna M. Kopps; Oliver Manlik; Julian A. Tyne; Lars Bejder (Frontiers in Marine Science, 2016)

Plant biodiversity effects in reducing fluvial erosion are limited to low species richness - Daniel C. Allen; Bradley J. Cardinale; Theresa Wynn‐Thompson (Ecology, 2016)
It has been proposed that plant biodiversity may increase the erosion resistance of soils, yet direct evidence for any such relationship is lacking. We conducted a mesocosm experiment with eight species of riparian herbaceous plants, and found evidence that plant biodiversity significantly reduced fluvial erosion rates, with the eight‐species polyculture decreasing erosion by 23% relative to monocultures. Species richness effects were largest at low levels of species richness, with little increase between four and eight species. Our results suggest that plant biodiversity reduced erosion rates indirectly through positive effects on root length and number of root tips, and that interactions between legumes and non‐legumes were particularly important in producing biodiversity effects. Presumably, legumes increased root production of non‐legumes by increasing soil nitrogen availability due to their ability to fix atmospheric nitrogen. Our data suggest that a restoration project using species from different functional groups might provide the best insurance to maintain long‐term erosion resistance.

A seven-gene expression panel distinguishing clonal expansions of pre-leukemic and chronic lymphocytic leukemia B cells from normal B lymphocytes - Brian A. McCarthy; Sophia Yancopoulos; Mike Tipping; Xiao-jie Yan; Xue Ping Wang; Fiona Bennett; Wentian Li; Martin Lesser; Santanu Paul; Erin Boyle; Carolina Moreno; Rosa Catera; et al. (Immunologic Research, 2015)

Climate change, climate justice and the application of probabilistic event attribution to summer heat extremes in the California Central Valley - Roberto Mera; Neil Massey; David E. Rupp; Philip Mote; Myles Allen; Peter C. Frumhoff (Climatic Change, 2015)

Identification of specific corrinoids reveals corrinoid modification in dechlorinating microbial communities - Yujie Men; Erica C. Seth; Shan Yi; Terence S. Crofts; Robert H. Allen; Michiko E. Taga; Lisa Alvarez‐Cohen (Environmental Microbiology, 2015)
Summary Cobalamin and other corrinoids are essential cofactors for many organisms. The majority of microbes with corrinoid‐dependent enzymes do not produce corrinoids de novo , and instead must acquire corrinoids produced by other organisms in their environment. However, the profile of corrinoids produced in corrinoid‐dependent microbial communities, as well as the exchange and modification of corrinoids among community members have not been well studied. In this study, we applied a newly developed liquid chromatography tandem mass spectrometry‐based corrinoid detection method to examine relationships among corrinoids, their lower ligand bases and specific microbial groups in microbial communities containing D ehalococcoides mccartyi that has an obligate requirement for benzimidazole‐containing corrinoids for trichloroethene respiration. We found that p ‐cresolylcobamide ([ p‐Cre ] Cba ) and cobalamin were the most abundant corrinoids in the communities. It suggests that members of the family V eillonellaceae are associated with the production of [ p‐Cre ] Cba . The decrease of supernatant‐associated [ p‐Cre ] Cba and the increase of biomass‐associated cobalamin were correlated with the growth of D . mccartyi by dechlorination. This supports the hypothesis that D . mccartyi is capable of fulfilling its corrinoid requirements in a community through corrinoid remodelling, in this case, by importing extracellular [ p‐Cre ] Cba and 5,6‐dimethylbenzimidazole ( DMB ) (the lower ligand of cobalamin), to produce cobalamin as a cofactor for dechlorination. This study also highlights the role of DMB , the lower ligand produced in all of the studied communities, in corrinoid remodelling. These findings provide novel insights on roles played by different phylogenetic groups in corrinoid production and corrinoid exchange within microbial communities. This study may also have implications for optimizing chlorinated solvent bioremediation.

Bottom‐up regulation of malaria population dynamics in mice co‐infected with lung‐migratory nematodes - Emily C. Griffiths; Karen Fairlie‐Clarke; Judith E. Allen; C. Jessica E. Metcalf; Andrea L. Graham (Ecology Letters, 2015)
When and how populations are regulated by bottom up vs. top down processes, and how those processes are affected by co‐occurring species, are poorly characterised across much of ecology. We are especially interested in the community ecology of parasites that must share a host. Here, we quantify how resources and immunity affect parasite propagation in experiments in near‐replicate ‘mesocosms’’ – i.e. mice infected with malaria ( Plasmodium chabaudi ) and nematodes ( Nippostrongylus brasiliensis ). Nematodes suppressed immune responses against malaria, and yet malaria populations were smaller in co‐infected hosts. Further analyses of within‐host epidemiology revealed that nematode co‐infection altered malaria propagation by suppressing target cell availability. This is the first demonstration that bottom‐up resource regulation may have earlier and stronger effects than top‐down immune mechanisms on within‐host community dynamics. Our findings demonstrate the potential power of experimental ecology to disentangle mechanisms of population regulation in complex communities.

Defining multiple, distinct, and shared spatiotemporal patterns of DNA replication and endoreduplication from 3D image analysis of developing maize (Zea mays L.) root tip nuclei - Hank W. Bass; Gregg G. Hoffman; Tae-Jin Lee; Emily E. Wear; Stacey R. Joseph; George C. Allen; Linda Hanley-Bowdoin; William F. Thompson (Plant Molecular Biology, 2015)

The tectonic significance of lower Permian successions in the Texas Orocline (Eastern Australia) - M. Campbell; G. Rosenbaum; U. Shaanan; C. R. Fielding; C. Allen (Australian Journal of Earth Sciences, 2015)

CSF biomarkers of monocyte activation and chemotaxis correlate with magnetic resonance spectroscopy metabolites during chronic HIV disease - Albert M. Anderson; Christine Fennema-Notestine; Anya Umlauf; Michael J. Taylor; David B. Clifford; Christina M. Marra; Ann C. Collier; Benjamin B. Gelman; Justin C. McArthur; J. Allen McCutchan; David M. Simpson; Susan Morgello; et al. (Journal of NeuroVirology, 2015)

Changes in the Frequency and Intensity of Extreme Temperature Events and Human Health Concerns - Scott C. Sheridan; Michael J. Allen (Current Climate Change Reports, 2015)

Evaluating habitat suitability curves for predicting variation in macroinvertebrate biomass with weighted usable area in braided rivers in New Zealand - DJ Kelly; JW Hayes; C Allen; D West; H Hudson (New Zealand Journal of Marine and Freshwater Research, 2015)
We investigated changes in seasonal biomass of benthic macroinvertebrates over whole floodplain transects upstream and downstream of existing flow diversions in the Wilberforce and South Ashburton Rivers, Canterbury, New Zealand. We tested the predictive performance of a 1‐dimensional hydraulic‐habitat model informed with existing general habitat suitability curves (HSC), as well as river‐ and channel‐specific HSC developed from the studied rivers. Diversions resulted in significant declines in wetted width, habitat complexity, and resulting declines in benthic biomass, but community composition was unchanged. Weighted usable area (WUA) predictions based on general HSC were often poorly correlated with cross‐sectional macroinvertebrate biomass. River‐ and channel‐type‐specific HSC greatly improved the accuracy of predictions; however, all HSC generally under‐predicted the total proportional change in cross‐sectional macroinvertebrate biomass associated with flow change. We conclude that WUA was an insensitive indicator of flow‐related macroinvertebrate biomass change. We encourage development of HSC categorised by river hydrology, size and channel form.

Membrane Protein Structure, Function, and Dynamics: a Perspective from Experiments and Theory - Zoe Cournia; Toby W. Allen; Ioan Andricioaei; Bruno Antonny; Daniel Baum; Grace Brannigan; Nicolae-Viorel Buchete; Jason T. Deckman; Lucie Delemotte; Coral del Val; Ran Friedman; Paraskevi Gkeka; et al. (The Journal of Membrane Biology, 2015)

Massively parallel sequencing (MPS) assays for sequencing mitochondrial genomes: the phylogenomic implications for Acropora staghorn corals (Scleractinia; Acroporidae) - Shang-Yin Vanson Liu; Chia-Ling Carynn Chan; Hernyi Justin Hsieh; Silvia Fontana; Carden C. Wallace; Chaolun Allen Chen (Marine Biology, 2015)

Rethinking length‐based fisheries regulations: the value of protecting old and large fish with harvest slots - Daniel C Gwinn; Micheal S Allen; Fiona D Johnston; Paul Brown; Charles R Todd; Robert Arlinghaus (Fish and Fisheries, 2015)
Managing fisheries using length‐based harvest regulations is common, but such policies often create trade‐offs among conservation (e.g. maintaining natural age‐structure or spawning stock biomass) and fishery objectives (e.g. maximizing yield or harvest numbers). By focusing harvest on the larger (older) fish, minimum‐length limits are thought to maximize biomass yield, but at the potential cost of severe age and size truncation at high fishing mortality. Harvest‐slot‐length limits (harvest slots) restrict harvest to intermediate lengths (ages), which may contribute to maintaining high harvest numbers and a more natural age‐structure. However, an evaluation of minimum‐length limits vs. harvest slots for jointly meeting fisheries and conservation objectives across a range of fish life‐history strategies is currently lacking. We present a general age‐ and size‐structured population model calibrated to several recreationally important fish species. Harvest slots and minimum‐length limits were both effective at compromising between yield, numbers harvested and catch of trophy fish while conserving reproductive biomass. However, harvest slots consistently produced greater numbers of fish harvested and greater catches of trophy fish while conserving reproductive biomass and a more natural population age‐structure. Additionally, harvest slots resulted in less waste in the presence of hooking mortality. Our results held across a range of exploitation rates, life‐history strategies and fisheries objectives. Overall, we found harvest slots to represent a valuable option to meet both conservation and recreational fisheries objectives. Given the ubiquitous benefits of harvest slots across all life histories modelled, rethinking the widespread use of minimum‐length limits is warranted.

Discovery of a pupping site and nursery for critically endangered green sawfish Pristis zijsron - D. L. Morgan; M. G. Allen; B. C. Ebner; J. M. Whitty; S. J. Beatty (Journal of Fish Biology, 2015)
A pilot study targeting sawfishes in the southern Pilbara region of Western Australia, which is undergoing a major expansion in human activity, was conducted using gillnets during April and October 2011 in the Ashburton Estuary and adjacent mangrove creeks. Catch per unit effort was greatest in the Ashburton Estuary in October, due to an influx of green sawfish Pristis zijsron pups, and was orders of magnitude higher than previously reported for any Pristidae; the study sites contained P. zijsron up to almost 3 m total length. This study identified the first pupping site for P. zijsron in Western Australia, and the most southerly known nursery area for the species in Australian waters, and is potentially the most important globally.

Meta‐analysis: abundance, behavior, and hydraulic energy shape biotic effects on sediment transport in streams - L. K. Albertson; D. C. Allen (Ecology, 2015)
An increasing number of studies have emphasized the need to bridge the disciplines of ecology and geomorphology. A large number of case studies show that organisms can affect erosion, but a comprehensive understanding of biological impacts on sediment transport conditions is still lacking. We use meta‐analysis to synthesize published data to quantify the effects of the abundance, body size, and behavior of organisms on erosion in streams. We also explore the influence of current velocity, discharge, and sediment grain size on the strength of biotic effects on erosion. We found that species that both increase erosion (destabilizers) and decrease erosion (stabilizers) can alter incipient sediment motion, sediment suspension, and sediment deposition above control conditions in which the organisms were not present. When abundance was directly manipulated, these biotic effects were consistently stronger in the higher abundance treatment, increasing effect sizes by 66%. Per capita effect size and per capita biomass were also consistently positively correlated. Fish and crustaceans were the most studied organisms, but aquatic insects increased the effect size by 550× compared to other types of organisms after accounting for biomass. In streams with lower discharge and smaller grain sizes, we consistently found stronger biotic effects. Taken collectively, these findings provide synthetic evidence that biology can affect physical processes in streams, and these effects can be mediated by hydraulic energy. We suggest that future studies focus on understudied organisms, such as biofilms, conducting experiments under realistic field conditions, and developing hypotheses for the effect of biology on erosion and velocity currents in the context of restoration to better understand the forces that mediate physical disturbances in stream ecosystems.

Wide-ranging phylogeographic structure of invasive red lionfish in the Western Atlantic and Greater Caribbean - John S. S. Butterfield; Edgardo Díaz-Ferguson; Brian R. Silliman; Jonathan W. Saunders; Dayne Buddo; Antonio A. Mignucci-Giannoni; Linda Searle; Aarin C. Allen; Margaret E. Hunter (Marine Biology, 2015)

Rock avalanche on 14 July 2014 from Hillary Ridge, Aoraki/Mount Cook, New Zealand - S. C. Cox; M. J. McSaveney; J. Spencer; S. K. Allen; S. Ashraf; G. T. Hancox; P. Sirguey; J. Salichon; B. G. Ferris (Landslides, 2015)

Effects of flow regime on growth rate in freshwater drum, Aplodinotus grunniens - Stephen J. Jacquemin; Jason C. Doll; Mark Pyron; Michael Allen; Dustin A. S. Owen (Environmental Biology of Fishes, 2015)

BioEarth: Envisioning and developing a new regional earth system model to inform natural and agricultural resource management - Jennifer C. Adam; Jennie C. Stephens; Serena H. Chung; Michael P. Brady; R. David Evans; Chad E. Kruger; Brian K. Lamb; Mingliang Liu; Claudio O. Stöckle; Joseph K. Vaughan; Kirti Rajagopalan; John A. Harrison; et al. (Climatic Change, 2015)

Head Injury Potential and the Effectiveness of Headgear in Women’s Lacrosse - Kathleen Allen Rodowicz; Joseph E. Olberding; Andrew C. Rau (Annals of Biomedical Engineering, 2015)

An agenda for assessing and improving conservation impacts of sustainability standards in tropical agriculture - Jeffrey C. Milder; Margaret Arbuthnot; Allen Blackman; Sharon E. Brooks; Daniele Giovannucci; Lee Gross; Elizabeth T. Kennedy; Kristin Komives; Eric F. Lambin; Audrey Lee; Daniel Meyer; Peter Newton; et al. (Conservation Biology, 2015)
Sustainability standards and certification serve to differentiate and provide market recognition to goods produced in accordance with social and environmental good practices, typically including practices to protect biodiversity. Such standards have seen rapid growth, including in tropical agricultural commodities such as cocoa, coffee, palm oil, soybeans, and tea. Given the role of sustainability standards in influencing land use in hotspots of biodiversity, deforestation, and agricultural intensification, much could be gained from efforts to evaluate and increase the conservation payoff of these schemes. To this end, we devised a systematic approach for monitoring and evaluating the conservation impacts of agricultural sustainability standards and for using the resulting evidence to improve the effectiveness of such standards over time. The approach is oriented around a set of hypotheses and corresponding research questions about how sustainability standards are predicted to deliver conservation benefits. These questions are addressed through data from multiple sources, including basic common information from certification audits; field monitoring of environmental outcomes at a sample of certified sites; and rigorous impact assessment research based on experimental or quasi‐experimental methods. Integration of these sources can generate time‐series data that are comparable across sites and regions and provide detailed portraits of the effects of sustainability standards. To implement this approach, we propose new collaborations between the conservation research community and the sustainability standards community to develop common indicators and monitoring protocols, foster data sharing and synthesis, and link research and practice more effectively. As the role of sustainability standards in tropical land‐use governance continues to evolve, robust evidence on the factors contributing to effectiveness can help to ensure that such standards are designed and implemented to maximize benefits for biodiversity conservation.

Patterns in bobcat (Lynx rufus) scent marking and communication behaviors - Maximilian L. Allen; Cody F. Wallace; Christopher C. Wilmers (Journal of Ethology, 2015)

Deciphering life history transcriptomes in different environments - William J. Etges; Meredith V. Trotter; Cássia C. de Oliveira; Subhash Rajpurohit; Allen G. Gibbs; Shripad Tuljapurkar (Molecular Ecology, 2015)
We compared whole transcriptome variation in six pre‐adult stages and seven adult female ages in two populations of cactophilic Drosophila mojavensis reared on two host plants to understand how differences in gene expression influence standing life history variation. We used singular value decomposition ( SVD ) to identify dominant trajectories of life cycle gene expression variation, performed pairwise comparisons of stage and age differences in gene expression across the life cycle, identified when genes exhibited maximum levels of life cycle gene expression, and assessed population and host cactus effects on gene expression. Life cycle SVD analysis returned four significant components of transcriptional variation, revealing functional enrichment of genes responsible for growth, metabolic function, sensory perception, neural function, translation and ageing. Host cactus effects on female gene expression revealed population‐ and stage‐specific differences, including significant host plant effects on larval metabolism and development, as well as adult neurotransmitter binding and courtship behaviour gene expression levels. In 3‐ to 6‐day‐old virgin females, significant upregulation of genes associated with meiosis and oogenesis was accompanied by downregulation of genes associated with somatic maintenance, evidence for a life history trade‐off. The transcriptome of D. mojavensis reared in natural environments throughout its life cycle revealed core developmental transitions and genome‐wide influences on life history variation in natural populations.

Differential Aortic and Mitral Valve Interstitial Cell Mineralization and the Induction of Mineralization by Lysophosphatidylcholine In Vitro - Dena C. Wiltz; Richard I. Han; Reid L. Wilson; Aditya Kumar; Joel D. Morrisett; K. Jane Grande-Allen (Cardiovascular Engineering and Technology, 2014)

Workshop report: Identifying opportunities for global integration of toxicogenomics databases, 26–27 June 2013, Research Triangle Park, NC, USA - Diana M. Hendrickx; Rebecca R. Boyles; Jos C. S. Kleinjans; Allen Dearry (Archives of Toxicology, 2014)

Investigating high mortality during the cold season: mapping mean weather patterns of temperature and pressure - Michael J. Allen; Cameron C. Lee (Theoretical and Applied Climatology, 2014)

Application of statistical approaches to analyze geological, geotechnical and hydrogeological data at a fractured-rock mine site in Northern Canada - J. M. Mayer; D. M. Allen; H. D. Gibson; D. C. Mackie (Hydrogeology Journal, 2014)

Reproductive investment drives capture probability in fish: an interspecific comparison - D. A. H. Sutter; S. L. Shaw; M. S. Allen; D. P. Philipp; C. D. Suski (Fisheries Management and Ecology, 2014)

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

Panarchy: Theory and Application - Craig R. Allen; David G. Angeler; Ahjond S. Garmestani; Lance H. Gunderson; C. S. Holling (Ecosystems, 2014)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Hybrid poplar (Populus spp.) adaptation to a semi-arid region: results from Northwest New Mexico (2002–2011) - Michael K. O’Neill; Samuel C. Allen; Robert F. Heyduck; Kevin A. Lombard; Dan Smeal; Richard N. Arnold (Agroforestry Systems, 2014)

Electronic structure of the Mn-cofactor of modified bacterial reaction centers measured by electron paramagnetic resonance and electron spin echo envelope modulation spectroscopies - A. A. Tufts; M. Flores; T. L. Olson; J. C. Williams; J. P. Allen (Photosynthesis Research, 2014)

The three-dimensional structures of bacterial reaction centers - T. L. Olson; J. C. Williams; J. P. Allen (Photosynthesis Research, 2014)

Remote Antarctic feeding ground important for east Australian humpback whales - Rochelle Constantine; Debbie Steel; Judy Allen; Megan Anderson; Olive Andrews; C. Scott Baker; Peta Beeman; Daniel Burns; Jean-Benoît Charrassin; Simon Childerhouse; Michael Double; Paul Ensor; et al. (Marine Biology, 2014)

When should species richness be energy limited, and how would we know? - Allen H. Hurlbert; James C. Stegen (Ecology Letters, 2014)
Energetic constraints are fundamental to ecology and evolution, and empirical relationships between species richness and estimates of available energy (i.e. resources) have led some to suggest that richness is energetically constrained. However, the mechanism linking energy with richness is rarely specified and predictions of secondary patterns consistent with energy‐constrained richness are lacking. Here, we lay out the necessary and sufficient assumptions of a causal relationship linking energy gradients to richness gradients. We then describe an eco‐evolutionary simulation model that combines spatially explicit diversification with trait evolution, resource availability and assemblage‐level carrying capacities. Our model identified patterns in richness and phylogenetic structure expected when a spatial gradient in energy availability determines the number of individuals supported in a given area. A comparison to patterns under alternative scenarios, in which fundamental assumptions behind energetic explanations were violated, revealed patterns that are useful for evaluating the importance of energetic constraints in empirical systems. We use a data set on rockfish (genus Sebastes ) from the northeastern Pacific to show how empirical data can be coupled with model predictions to evaluate the role of energetic constraints in generating observed richness gradients.

High-mortality days during the winter season: comparing meteorological conditions across 5 US cities - Michael J. Allen; Scott C. Sheridan (International Journal of Biometeorology, 2014)

Contrast agents for MRI: 30+ years and where are we going? - Valérie C. Pierre; Matthew J. Allen; Peter Caravan (JBIC Journal of Biological Inorganic Chemistry, 2014)

Lipid nanoparticle delivery systems for siRNA-based therapeutics - C. Wan; T. M. Allen; P. R. Cullis (Drug Delivery and Translational Research, 2014)

Accumulation of Ergot Alkaloids During Conidiophore Development in Aspergillus fumigatus - Prashanthi Mulinti; Natalie A. Allen; Christine M. Coyle; Fabrice N. Gravelat; Donald C. Sheppard; Daniel G. Panaccione (Current Microbiology, 2014)

Xylem exudate composition and root-to-shoot nickel translocation in Alyssum species - Tiziana Centofanti; Zehra Sayers; Maria Isabel Cabello-Conejo; Petra Kidd; Naoko K. Nishizawa; Yusuke Kakei; Allen P. Davis; Richard C. Sicher; Rufus L. Chaney (Plant and Soil, 2013)

Overexpression of mannitol dehydrogenase in zonal geranium confers increased resistance to the mannitol secreting fungal pathogen Botrytis cinerea - John D. Williamson; Aparna Desai; Sergei F. Krasnyanski; Fei Ding; Wei-wen Guo; Thanh-Tuyen Nguyen; Heather A. Olson; John M. Dole; George C. Allen (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Watershed sediment source identification: tools, approaches, and case studies - Allen C. Gellis; Rajith Mukundan (Journal of Soils and Sediments, 2013)

Sediment source analysis in the Linganore Creek watershed, Maryland, USA, using the sediment fingerprinting approach: 2008 to 2010 - Allen C. Gellis; Gregory B. Noe (Journal of Soils and Sediments, 2013)

Biokinetically-Based In Vitro Cardiotoxicity of Residual Oil Fly Ash: Hazard Identification and Mechanisms of Injury - Travis L. Knuckles; Richard Jaskot; Judy H. Richards; C. Andrew Miller; Allen Ledbetter; John McGee; William P. Linak; Kevin L. Dreher (Cardiovascular Toxicology, 2013)

A Tale of Two Rivers: Implications of Water Management Practices for Mussel Biodiversity Outcomes During Droughts - Daniel C. Allen; Heather S. Galbraith; Caryn C. Vaughn; Daniel E. Spooner (Ambio, 2013)

Source water, phenology and growth of two tropical dry forest tree species growing on shallow karst soils - Héctor Estrada-Medina; Louis S. Santiago; Robert C. Graham; Michael F. Allen; Juan José Jiménez-Osornio (Trees, 2013)

The largest Au deposits in the St Ives Goldfield (Yilgarn Craton, Western Australia) may be located in a major Neoarchean volcano-sedimentary depo-centre - K. L. McGoldrick; R. J. Squire; R. A. F. Cas; M. Briggs; J. Tunjic; C. M. Allen; I. H. Campbell; P. C. Hayman (Mineralium Deposita, 2013)

Indices for the Objective Assessment of Tsunami Forecast Models - Stewart C. R. Allen; Diana J. M. Greenslade (Pure and Applied Geophysics, 2013)

Diverse Perceptions of Stakeholder Engagement within an Environmental Modeling Research Team - Elizabeth Allen; Chad Kruger; Fok-Yan Leung; Jennie C. Stephens (Journal of Environmental Studies and Sciences, 2013)

Sharing Best Practices in Teaching Biomedical Engineering Design - R. H. Allen; S. Acharya; C. Jancuk; A. A. Shoukas (Annals of Biomedical Engineering, 2013)

Increases in brain white matter abnormalities and subcortical gray matter are linked to CD4 recovery in HIV infection - Christine Fennema-Notestine; Ronald J. Ellis; Sarah L. Archibald; Terry L. Jernigan; Scott L. Letendre; Randy J. Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; David J. Croteau; Tanya Wolfson; Robert K. Heaton; et al. (Journal of NeuroVirology, 2013)

Blind to morphology: genetics identifies several widespread ecologically common species and few endemics among Indo‐Pacific cauliflower corals ( Pocillopora , Scleractinia) - Jorge H. Pinzón; Eugenia Sampayo; Evelyn Cox; Leonard J. Chauka; Chaolun Allen Chen; Christian R. Voolstra; Todd C. LaJeunesse (Journal of Biogeography, 2013)
Aim Using high‐resolution genetic markers on samples gathered from across their wide distributional range, we endeavoured to delimit species diversity in reef‐building Pocillopora corals. They are common, ecologically important, and widespread throughout the Indo‐Pacific, but their phenotypic plasticity in response to environmental conditions and their nearly featureless microskeletal structures confound taxonomic assignments and limit an understanding of their ecology and evolution. Location Indo‐Pacific, Red Sea, Arabian/Persian Gulf. Methods Sequence analysis of nuclear ribosomal (internal transcribed spacer 2, ITS 2) and mitochondrial (open reading frame) loci were combined with population genetic data (seven microsatellite loci) for Pocillopora samples collected throughout the Indo‐Pacific, Red Sea and Arabian Gulf, in order to assess the evolutionary divergence, reproductive isolation, frequency of hybridization and geographical distributions of the genus. Results Between five and eight genetically distinct lineages comparable to species were identified with minimal or no hybridization between them. Colony morphology was generally incongruent with genetics across the full range of sampling, and the total number of species is apparently consistent with lower estimates from competing morphologically based hypotheses (about seven or eight taxa). The most commonly occurring genetic lineages were widely distributed and exhibited high dispersal and gene flow, factors that have probably minimized allopatric speciation. Uniquely among scleractinian genera, this genus contains a monophyletic group of broadcast spawners that evolved recently from an ancestral brooder. Main conclusions The delineation of species diversity guided by genetics fundamentally advances our understanding of Pocillopora geographical distributions, ecology and evolution. Because traditional diagnostic features of colony and branch morphology are proving to be of limited utility, the identification of Pocillopora species for future ecological and experimental work should rely on genetic characters that will improve research and aid in conservation strategies for these and other reef‐building corals, including the detection of real and mistaken endemic populations.

Initial epidemic area is strongly associated with the yearly extent of soybean rust spread in North America - Christopher C. Mundt; LaRae D. Wallace; Tom W. Allen; Clayton A. Hollier; Robert C. Kemerait; Edward J. Sikora (Biological Invasions, 2013)

Pollen analyses of tarnished plant bugs - G. D. Jones; K. C. Allen (Palynology, 2013)

Functional genomic and phenotypic responses to desiccation in natural populations of a desert drosophilid - Subhash Rajpurohit; Cássia C. Oliveira; William J. Etges; Allen G. Gibbs (Molecular Ecology, 2013)
We used whole‐transcriptome microarrays to assess changes in gene expression and monitored mortality rates and epicuticular hydrocarbons ( CHC s) in response to desiccation stress in four natural populations of D rosophila mojavensis from B aja C alifornia and mainland M exico. Desiccation had the greatest effect on gene expression, followed by biogeographical variation at regional and population levels. Genes involved in environmental sensing and cuticular structure were up‐regulated in dry conditions, while genes involved in transcription itself were down‐regulated. Flies from B aja C alifornia had higher expression of reproductive and mitochondrial genes, suggesting that these populations have greater fecundity and higher metabolic rates. Host plant differences had a surprisingly minor effect on the transcriptome. In most cases, desiccation‐caused mortality was greater in flies reared on fermenting cactus tissues than that on laboratory media. Water content of adult females and males was significantly different and was lower in B aja C alifornia males. Different groups of CHC s simultaneously increased and decreased in amounts due to desiccation exposure of 9 and 18 h and were population‐specific and dependent on larval rearing substrates. Overall, we observed that changes in gene expression involved a coordinated response of behavioural, cuticular and metabolic genes. Together with differential expression of cuticular hydrocarbons, this study revealed some of the mechanisms that have allowed D . mojavensis to exploit its harsh desert conditions. Certainly, for D . mojavensis that uses different host plants, population‐level understanding of responses to stressors associated with future climate change in desert regions must be evaluated across geographical and local ecological scales.

Agricultural adaptation to climate change: observations from the Mid-Hills of Nepal - E. M. Biggs; E. L. Tompkins; J. Allen; C. Moon; R. Allen (Climate and Development, 2013)

Influence of human immune cells on cancer: studies at the University of Colorado - Tullia C. Bruno; Jena D. French; Kimberly R. Jordan; Oscar Ramirez; Trisha R. Sippel; Virginia F. Borges; Bryan R. Haugen; Martin D. McCarter; Allen Waziri; Jill E. Slansky (Immunologic Research, 2013)

Erratum to: Gentamicin Reduces Calcific Nodule Formation by Aortic Valve Interstitial Cells In Vitro - Aditya Kumar; Dena C. Wiltz; K. Jane Grande-Allen (Cardiovascular Engineering and Technology, 2013)

Gentamicin Reduces Calcific Nodule Formation by Aortic Valve Interstitial Cells In Vitro - Aditya Kumar; Dena C. Wiltz; K. Jane Grande-Allen (Cardiovascular Engineering and Technology, 2013)

Species distribution models indicate contrasting late‐Quaternary histories for Southern and Northern Hemisphere bird species - Brian Huntley; Judy R. M. Allen; Phoebe Barnard; Yvonne C. Collingham; Phyllida R. Holliday (Global Ecology and Biogeography, 2013)
Aim To test the following hypotheses: that Fynbos species had more extensive distributions at the Last Glacial Maximum (LGM), extending onto the exposed ‘Agulhas Plain’; that genetically distinct British taxa could have persisted through the LGM on adjacent areas of exposed shelf. Location Southern Africa; Europe. Methods Climatic response surfaces were fitted for 14 Fynbos and two European birds. These models were used to hindcast species distributions for palaeoclimates simulated using a fully coupled atmosphere–ocean general circulation model. LGM annual net primary productivity (ANPP) of two plant functional types upon which the European birds depend were simulated using a dynamic vegetation model and compared with potential LGM bird distributions. Results Fynbos birds' potential LGM distributions mostly extended southwards onto the exposed Agulhas Plain and were consistently more extensive than at present. This contrasts with conventional expectations for temperate species based upon Northern Hemisphere evidence. North‐west European taxa potentially had LGM ranges on exposed shelf and ice‐free areas to the west and south‐west of the British Isles ice sheet. This is consistent with available genetic evidence, supporting the long‐standing hypothesis that these taxa persisted through the LGM in this region. In both regions, results allow the generation of new testable hypotheses about species evolution and palaeobiogeography. Main conclusions Bird species found today in the Fynbos probably had more extensive ranges under glacial conditions, with the potential ranges of many species extending onto the Agulhas Plain. Bird taxa restricted today to the British Isles probably survived the LGM with limited distributions on exposed shelf and ice‐free areas south‐west of the British Isles ice sheet. Areas of shelf exposed under glacial conditions are likely to have been important components of glacial distributions of species in both the Northern and Southern Hemisphere. The contrasting history of Northern and Southern Hemisphere species has important conservation implications, especially in relation to conserving intra‐specific genetic diversity.

Comparing Scales of Environmental Effects from Gasoline and Ethanol Production - Esther S. Parish; Keith L. Kline; Virginia H. Dale; Rebecca A. Efroymson; Allen C. McBride; Timothy L. Johnson; Michael R. Hilliard; Jeffrey M. Bielicki (Environmental Management, 2013)

Environmental Indicators of Biofuel Sustainability: What About Context? - Rebecca A. Efroymson; Virginia H. Dale; Keith L. Kline; Allen C. McBride; Jeffrey M. Bielicki; Raymond L. Smith; Esther S. Parish; Peter E. Schweizer; Denice M. Shaw (Environmental Management, 2013)

Stochastic and deterministic drivers of spatial and temporal turnover in breeding bird communities - James C. Stegen; Amy L. Freestone; Thomas O. Crist; Marti J. Anderson; Jonathan M. Chase; Liza S. Comita; Howard V. Cornell; Kendi F. Davies; Susan P. Harrison; Allen H. Hurlbert; Brian D. Inouye; Nathan J. B. Kraft; et al. (Global Ecology and Biogeography, 2013)
Aim A long‐standing challenge in ecology is to identify the suite of factors that lead to turnover in species composition in both space and time. These factors might be stochastic (e.g. sampling and priority effects) or deterministic (e.g. competition and environmental filtering). While numerous studies have examined the relationship between turnover and individual drivers of interest (e.g. primary productivity, habitat heterogeneity, or regional – ‘gamma’ – diversity), few studies have disentangled the simultaneous influences of multiple stochastic and deterministic processes on both temporal and spatial turnover. If turnover is governed primarily by stochastic sampling processes, removing the sampling effects of gamma diversity should result in non‐significant relationships between turnover and environmental variables. Conversely, if deterministic processes govern turnover patterns, removing sampling effects will have little influence on turnover gradients. Here, we test these predictions. Location The United States. Methods Continental‐scale, multidecadal data were used to quantify spatial and temporal turnover in avian community composition within 295 survey routes. A series of regression and structural equation models were coupled with a null model to construct statistical models describing turnover patterns. Results Examining explanatory variables alone or in combination showed that spatial and temporal turnover increased together, decreased with primary productivity and increased with habitat heterogeneity. The relationships between turnover and all variables became weaker when sampling effects were removed, but relationships with primary productivity and habitat heterogeneity remained relatively strong. In addition, spatial turnover increased strongly with spatial gamma diversity after sampling effects were removed. Main conclusions Our results show that spatial and temporal turnover are related to each other through a stochastic sampling process, but that each type of turnover is further influenced by deterministic processes. The relative influence of deterministic processes appears, however, to decrease with primary productivity and increase with habitat heterogeneity across an east–west longitudinal gradient in North America.

The importance of limestone bedrock and dissolution karst features on tree root distribution in northern Yucatán, México - Héctor Estrada-Medina; Robert C. Graham; Michael F. Allen; Juan José Jiménez-Osornio; Said Robles-Casolco (Plant and Soil, 2013)

Assessing risk associated with sea-level rise and storm surge—Redux - Christine C. Shepard; Vera N. Agostini; Ben Gilmer; Tashya Allen; Jeff Stone; William Brooks; Michael W. Beck (Natural Hazards, 2013)

Using Amaranthus palmeri pollen to mark captured tarnished plant bugs - G. D. Jones; K. C. Allen (Palynology, 2012)

Mitochondrial DNA variation and HIV-associated sensory neuropathy in CHARTER - Emily R. Holzinger; Todd Hulgan; Ronald J. Ellis; David C. Samuels; Marylyn D. Ritchie; David W. Haas; Asha R. Kallianpur; Cinnamon S. Bloss; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; et al. (Journal of NeuroVirology, 2012)

Crop coefficients and actual evapotranspiration of a drip-irrigated Merlot vineyard using multispectral satellite images - M. Carrasco-Benavides; S. Ortega-Farías; L. O. Lagos; J. Kleissl; L. Morales; C. Poblete-Echeverría; R. G. Allen (Irrigation Science, 2012)

Serum vitamins A and E as modifiers of lipid trait genetics in the National Health and Nutrition Examination Surveys as part of the Population Architecture using Genomics and Epidemiology (PAGE) study - Logan Dumitrescu; Robert Goodloe; Kristin Brown-Gentry; Ping Mayo; Melissa Allen; Hailing Jin; Niloufar B. Gillani; Nathalie Schnetz-Boutaud; Holli H. Dilks; Dana C. Crawford (Human Genetics, 2012)

Future heat vulnerability in California, Part II: projecting future heat-related mortality - Scott C. Sheridan; Michael J. Allen; Cameron C. Lee; Laurence S. Kalkstein (Climatic Change, 2012)

Future heat vulnerability in California, Part I: projecting future weather types and heat events - Scott C. Sheridan; Cameron C. Lee; Michael J. Allen; Laurence S. Kalkstein (Climatic Change, 2012)

Bottom‐up biodiversity effects increase resource subsidy flux between ecosystems - Daniel C. Allen; Caryn C. Vaughn; Jeffrey F. Kelly; Joshua T. Cooper; Michael H. Engel (Ecology, 2012)
Although biodiversity can increase ecosystem productivity and adjacent ecosystems are often linked by resource flows between them, the relationship between biodiversity and resource subsidies is not well understood. Here we test the influence of biodiversity on resource subsidy flux by manipulating freshwater mussel species richness and documenting the effects on a trophic cascade from aquatic to terrestrial ecosystems. In a mesocosm experiment, mussel effects on algae were linked through stable isotope analyses to mussel‐derived nitrogen subsidies, but mussel biodiversity effects on algal accumulation were not significant. In contrast, mussel biodiversity significantly increased aquatic insect emergence rates, because aquatic insects were responding to mussel‐induced changes in algal community structure instead of algal accumulation. In turn, mussel biodiversity also significantly increased terrestrial spider abundance as spiders tracked increases in aquatic insect prey after a reproduction event. In a comparative field study, we found that sites with greater mussel species richness had higher aquatic insect emergence rates. These results show that, because food webs in adjacent ecosystems are often linked, biodiversity effects in one ecosystem can influence adjacent ecosystems as well.

Removal of Uranium(VI), Lead(II) at the Surface of TiO2 Nanotubes Studied by X-Ray Photoelectron Spectroscopy - M. Bonato; K. V. Ragnarsdottir; G. C. Allen (Water, Air, & Soil Pollution, 2012)

Aerodynamic Parameterization of the Satellite-Based Energy Balance (METRIC) Model for ET Estimation in Rainfed Olive Orchards of Andalusia, Spain - C. Santos; I. J. Lorite; R. G. Allen; M. Tasumi (Water Resources Management, 2012)

Evaluating alternative future sea-level rise scenarios - Christine C. Shepard; Vera N. Agostini; Ben Gilmer; Tashya Allen; Jeff Stone; William Brooks; Michael W. Beck (Natural Hazards, 2012)

Functional ecology of feeding in elasmobranchs - Cheryl A. D. Wilga; Ashley A. Stoehr; Danielle C. Duquette; Rebecca M. Allen (Environmental Biology of Fishes, 2012)

Stable isotopic assessment of site fidelity of mummichogs, Fundulus heteroclitus, exposed to multiple anthropogenic inputs - Marc A. Skinner; Simon C. Courtenay; W. Roy Parker; R. Allen Curry (Environmental Biology of Fishes, 2012)

Intensity attenuation for active crustal regions - Trevor I. Allen; David J. Wald; C. Bruce Worden (Journal of Seismology, 2012)

Prediagnostic concentrations of plasma genistein and prostate cancer risk in 1,605 men with prostate cancer and 1,697 matched control participants in EPIC - Ruth C. Travis; Naomi E. Allen; Paul N. Appleby; Alison Price; Rudolf Kaaks; Jenny Chang-Claude; Heiner Boeing; Krasimira Aleksandrova; Anne Tjønneland; Nina Føns Johnsen; Kim Overvad; J. Ramón Quirós; et al. (Cancer Causes & Control, 2012)

The Control of an Invasive Bivalve, Corbicula fluminea, Using Gas Impermeable Benthic Barriers in a Large Natural Lake - Marion E. Wittmann; Sudeep Chandra; John E. Reuter; S. Geoffrey Schladow; Brant C. Allen; Katie J. Webb (Environmental Management, 2012)

Diversity of Brazilian biovar 2 strains of Ralstonia solanacearum - Bárbara G. Santana; Carlos A. Lopes; Elba Alvarez; Cristine C. Barreto; Caitilyn Allen; Betania F. Quirino (Journal of General Plant Pathology, 2012)

Development of sustainability evaluation model for implementing product service systems - H. Allen Hu; S. H. Chen; C. W. Hsu; C. Wang; C. L. Wu (International Journal of Environmental Science and Technology, 2012)

Genetic features of cerebrospinal fluid-derived subtype B HIV-1 tat - Jun Yong Choi; George K. Hightower; Joseph K. Wong; Robert Heaton; Steven Woods; Igor Grant; Thomas D. Marcotte; Ronald J. Ellis; Scott L. Letendre; Ann C. Collier; Christina M. Marra; David B. Clifford; et al. (Journal of NeuroVirology, 2012)

Advancing the use of minirhizotrons in wetlands - C. M. Iversen; M. T. Murphy; M. F. Allen; J. Childs; D. M. Eissenstat; E. A. Lilleskov; T. M. Sarjala; V. L. Sloan; P. F. Sullivan (Plant and Soil, 2012)

Temporal turnover in the composition of tropical tree communities: functional determinism and phylogenetic stochasticity - Nathan G. Swenson; James C. Stegen; Stuart J. Davies; David L. Erickson; Jimena Forero-Montaña; Allen H. Hurlbert; W. John Kress; Jill Thompson; María Uriarte; S. Joseph Wright; Jess K. Zimmerman (Ecology, 2012)
The degree to which turnover in biological communities is structured by deterministic or stochastic factors and the identities of influential deterministic factors are fundamental, yet unresolved, questions in ecology. Answers to these questions are particularly important for projecting the fate of forests with diverse disturbance histories worldwide. To uncover the processes governing turnover we use species‐level molecular phylogenies and functional trait data sets for two long‐term tropical forest plots with contrasting disturbance histories: one forest is older‐growth, and one was recently disturbed. Having both phylogenetic and functional information further allows us to parse out the deterministic influences of different ecological filters. With the use of null models we find that compositional turnover was random with respect to phylogeny on average, but highly nonrandom with respect to measured functional traits. Furthermore, as predicted by a deterministic assembly process, the older‐growth and disturbed forests were characterized by less than and greater than expected functional turnover, respectively. These results suggest that the abiotic environment, which changes due to succession in the disturbed forest, strongly governs the temporal dynamics of disturbed and undisturbed tropical forests. Predicting future changes in the composition of disturbed and undisturbed forests may therefore be tractable when using a functional‐trait‐based approach.

Assessing future risk: quantifying the effects of sea level rise on storm surge risk for the southern shores of Long Island, New York - Christine C. Shepard; Vera N. Agostini; Ben Gilmer; Tashya Allen; Jeff Stone; William Brooks; Michael W. Beck (Natural Hazards, 2012)

High-resolution array CGH defines critical regions and candidate genes for microcephaly, abnormalities of the corpus callosum, and seizure phenotypes in patients with microdeletions of 1q43q44 - Blake C. Ballif; Jill A. Rosenfeld; Ryan Traylor; Aaron Theisen; Patricia I. Bader; Roger L. Ladda; Susan L. Sell; Michelle Steinraths; Urvashi Surti; Marianne McGuire; Shelley Williams; Sandra A. Farrell; et al. (Human Genetics, 2012)

Using Multitemporal Remote Sensing Imagery and Inundation Measures to Improve Land Change Estimates in Coastal Wetlands - Yvonne C. Allen; Brady R. Couvillion; John A. Barras (Estuaries and Coasts, 2012)

Effects of biotic disturbances on forest carbon cycling in the U nited S tates and C anada - Jeffrey A. Hicke; Craig D. Allen; Ankur R. Desai; Michael C. Dietze; Ronald J. Hall; Edward H. (Ted) Hogg; Daniel M. Kashian; David Moore; Kenneth F. Raffa; Rona N. Sturrock; James Vogelmann (Global Change Biology, 2012)
Forest insects and pathogens are major disturbance agents that have affected millions of hectares in N orth A merica in recent decades, implying significant impacts to the carbon ( C ) cycle. Here, we review and synthesize published studies of the effects of biotic disturbances on forest C cycling in the U nited S tates and C anada. Primary productivity in stands was reduced, sometimes considerably, immediately following insect or pathogen attack. After repeated growth reductions caused by some insects or pathogens or a single infestation by some bark beetle species, tree mortality occurred, altering productivity and decomposition. In the years following disturbance, primary productivity in some cases increased rapidly as a result of enhanced growth by surviving vegetation, and in other cases increased slowly because of lower forest regrowth. In the decades following tree mortality, decomposition increased as a result of the large amount of dead organic matter. Net ecosystem productivity decreased immediately following attack, with some studies reporting a switch to a C source to the atmosphere, and increased afterward as the forest regrew and dead organic matter decomposed. Large variability in C cycle responses arose from several factors, including type of insect or pathogen, time since disturbance, number of trees affected, and capacity of remaining vegetation to increase growth rates following outbreak. We identified significant knowledge gaps, including limited understanding of carbon cycle impacts among different biotic disturbance types (particularly pathogens), their impacts at landscape and regional scales, and limited capacity to predict disturbance events and their consequences for carbon cycling. We conclude that biotic disturbances can have major impacts on forest C stocks and fluxes and can be large enough to affect regional C cycling. However, additional research is needed to reduce the uncertainties associated with quantifying biotic disturbance effects on the N orth A merican C budget.

Evaluation of population decline and fishing sustainability of the endangered Australian freshwater fish Macquaria australasica - T. L. HUNT; J. W. DOUGLAS; M. S. ALLEN; D. C. GWINN; Z. TONKIN; J. LYON; A. PICKWORTH (Fisheries Management and Ecology, 2011)
Macquarie perch, Macquaria australasica Cuvier, is an endangered Australian freshwater fish that has historically supported popular recreational fisheries, but since the 1980s, it has experienced a decline in both distribution and abundance. This study investigated whether a marked decline in the population size of Macquarie perch has occurred at Lake Dartmouth between the mid‐1980s and 2000 and the likelihood of the current legal minimum length (LML) of 350 mm TL protecting the population from recruitment overfishing. Recreational angler survey data showed strong evidence for a temporal population decline. Sampling of the population and construction of a simulation model indicated that the current LML would protect the population from recruitment overfishing. This study highlights the value of specifically investigating suspected threats to endangered fish populations to allow the instigation of effective fisheries management.

Global to city scale urban anthropogenic heat flux: model and variability - L. Allen; F. Lindberg; C. S. B. Grimmond (International Journal of Climatology, 2011)
The large scale urban consumption of energy (LUCY) model simulates all components of anthropogenic heat flux ( Q F ) from the global to individual city scale at 2.5 × 2.5 arc‐minute resolution. This includes a database of different working patterns and public holidays, vehicle use and energy consumption in each country. The databases can be edited to include specific diurnal and seasonal vehicle and energy consumption patterns, local holidays and flows of people within a city. If better information about individual cities is available within this (open‐source) database, then the accuracy of this model can only improve, to provide the community data from global‐scale climate modelling or the individual city scale in the future. The results show that Q F varied widely through the year, through the day, between countries and urban areas. An assessment of the heat emissions estimated revealed that they are reasonably close to those produced by a global model and a number of small‐scale city models, so results from LUCY can be used with a degree of confidence. From LUCY, the global mean urban Q F has a diurnal range of 0.7–3.6 W m −2 , and is greater on weekdays than weekends. The heat release from building is the largest contributor (89–96%), to heat emissions globally. Differences between months are greatest in the middle of the day (up to 1 W m −2 at 1 pm). December to February, the coldest months in the Northern Hemisphere, have the highest heat emissions. July and August are at the higher end. The least Q F is emitted in May. The highest individual grid cell heat fluxes in urban areas were located in New York (577), Paris (261.5), Tokyo (178), San Francisco (173.6), Vancouver (119) and London (106.7). Copyright © 2010 Royal Meteorological Society

Genetic analysis of iron-deficiency effects on the mouse spleen - Jennifer N. Gibson; Leslie C. Jellen; Erica L. Unger; Grant Morahan; Munish Mehta; Christopher J. Earley; Richard P. Allen; Lu Lu; Byron C. Jones (Mammalian Genome, 2011)

Candida middelhoveniana sp. nov., a new yeast species found on the rhizoplane of organically cultivated sugarcane - José R. de A. Ribeiro; Patrícia M. B. de Carvalho; Anderson de S. Cabral; Andrew Macrae; Leda C. S. Mendonça-Hagler; Ricardo L. L. Berbara; Allen N. Hagler (Antonie van Leeuwenhoek, 2011)

Integrated catchment management—interweaving social process and science knowledge - A Fenemor; C Phillips; W Allen; RG Young; G Harmsworth; B Bowden; L Basher; PA Gillespie; M Kilvington; R Davies‐Colley; J Dymond; A Cole; et al. (New Zealand Journal of Marine and Freshwater Research, 2011)
This paper provides an overview of the Motueka integrated catchment management (ICM) research programme. This research was based on the thesis that achieving ecosystem resilience at a catchment scale requires active measures to develop community resilience. We define a generic adaptive planning and action process, with associated knowledge management and stakeholder involvement processes, and illustrate those processes with observations from five research themes: (1) water allocation; (2) land use effects on water; (3) land and freshwater impacts on the coast; (4) integrative tools and processes for managing cumulative effects; and (5) building human capital and facilitating community action. Our research clearly illustrates the benefits for effective decision‐making of carrying out catchment scale science and management within collaborative processes which patiently develop trusting relationships. We conclude that coastal catchments should be managed as a holistic continuum from ridge tops to the sea and that some processes like floods or loss of community resilience have decadal consequences, which support the need for long‐term monitoring and investment.

Building collaboration and learning in integrated catchment management: the importance of social process and multiple engagement approaches - W Allen; A Fenemor; M Kilvington; G Harmsworth; RG Young; N Deans; C Horn; C Phillips; O Montes de Oca; J Ataria; R Smith (New Zealand Journal of Marine and Freshwater Research, 2011)
Success at integrated catchment management (ICM) requires the ongoing participation of different stakeholders in an adaptive and learning‐based management process. However, this can be difficult to achieve in practice because many initiatives fail to address the underlying social process aspects required. We review emerging lessons around how to engage stakeholders in ways that support social learning. We focus on the experience of an ICM research programme based in the Motueka catchment in New Zealand and provide a simple framework for distinguishing a range of conversations across different communities of practice. We highlight the need to use multiple engagement approaches to address different constituent needs and opportunities, and to encourage the informal conversations that spring up around these. We then illustrate the range of platforms for dialogue and learning that were used in the programme during 10 years of ICM research. Finally, a number of lessons are described from across the programme to guide research leaders and managers seeking to improve collaboration in other integrated science, management and policy initiatives.

Integrated catchment management—a decade of research in the Motueka River catchment - A Fenemor; RG Young; B Bowden; C Phillips; W Allen (New Zealand Journal of Marine and Freshwater Research, 2011)

Near real-time Feed On Offer (FOO) from MODIS for early season grazing management of Mediterranean annual pastures - Richard C. G. Smith; Matthew Adams; Stewart Gittins; Steve Gherardi; Duncan Wood; Stefan Maier; Richard Stovold; Graham Donald; Sarfraz Khohkar; Adrian Allen (International Journal of Remote Sensing, 2011)

Plasma matrix metalloproteinase-9 response to eccentric exercise of the elbow flexors - Molly C. Madden; William C. Byrnes; Jacob A. Lebin; Matthew E. Batliner; David L. Allen (European Journal of Applied Physiology, 2011)

Menopausal hormone therapy and risk of ovarian cancer in the European prospective investigation into cancer and nutrition - Konstantinos K. Tsilidis; Naomi E. Allen; Timothy J. Key; Laure Dossus; Rudolf Kaaks; Kjersti Bakken; Eiliv Lund; Agnès Fournier; Christina C. Dahm; Kim Overvad; Louise Hansen; Anne Tjønneland; et al. (Cancer Causes & Control, 2011)

Seabed foraging by Antarctic krill: Implications for stock assessment, bentho‐pelagic coupling, and the vertical transfer of iron - Katrin Schmidt; Angus Atkinson; Sebastian Steigenberger; Sophie Fielding; Margaret C. M. Lindsay; David W. Pond; Geraint A. Tarling; Thor A. Klevjer; Claire S. Allen; Stephen Nicol; Eric P. Achterberg (Limnology and Oceanography, 2011)
A compilation of more than 30 studies shows that adult Antarctic krill ( Euphausia superba ) may frequent benthic habitats year‐round, in shelf as well as oceanic waters and throughout their circumpolar range. Net and acoustic data from the Scotia Sea show that in summer 2‐20% of the population reside at depths between 200 and 2000 m, and that large aggregations can form above the seabed. Local differences in the vertical distribution of krill indicate that reduced feeding success in surface waters, either due to predator encounter or food shortage, might initiate such deep migrations and results in benthic feeding. Fatty acid and microscopic analyses of stomach content confirm two different foraging habitats for Antarctic krill: the upper ocean, where fresh phytoplankton is the main food source, and deeper water or the seabed, where detritus and copepods are consumed. Krill caught in upper waters retain signals of benthic feeding, suggesting frequent and dynamic exchange between surface and seabed. Krill contained up to 260 nmol iron per stomach when returning from seabed feeding. About 5% of this iron is labile, i.e., potentially available to phytoplankton. Due to their large biomass, frequent benthic feeding, and acidic digestion of particulate iron, krill might facilitate an input of new iron to Southern Ocean surface waters. Deep migrations and foraging at the seabed are significant parts of krill ecology, and the vertical fluxes involved in this behavior are important for the coupling of benthic and pelagic food webs and their elemental repositories.

An Evaluation of Tsunami Forecasts from the T2 Scenario Database - Diana J. M. Greenslade; Stewart C. R. Allen; M. Arthur Simanjuntak (Pure and Applied Geophysics, 2011)

Archaean fluid-assisted crustal cannibalism recorded by low δ18O and negative εHf(T) isotopic signatures of West Greenland granite zircon - Joe Hiess; Vickie C. Bennett; Allen P. Nutman; Ian S. Williams (Contributions to Mineralogy and Petrology, 2011)

Consumption of meat and fish and risk of lung cancer: results from the European Prospective Investigation into Cancer and Nutrition - Jakob Linseisen; Sabine Rohrmann; Bas Bueno-de-Mesquita; Frederike L. Büchner; Hendriek C. Boshuizen; Antonio Agudo; Inger Torhild Gram; Christina C. Dahm; Kim Overvad; Rikke Egeberg; Anne Tjønneland; Heiner Boeing; et al. (Cancer Causes & Control, 2011)

Clinical factors related to brain structure in HIV: the CHARTER study - Terry L. Jernigan; Sarah L. Archibald; Christine Fennema-Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; Randy J. Notestine; Tanya Wolfson; Scott L. Letendre; Ronald J. Ellis; Robert K. Heaton; Anthony C. Gamst; et al. (Journal of NeuroVirology, 2011)

The impact of natural versus anthropogenic aerosols on atmospheric circulation in the Community Atmosphere Model - Robert J. Allen; Steven C. Sherwood (Climate Dynamics, 2011)

Variation in Physiological Stress between Bridge‐ and Cave‐Roosting Brazilian Free‐Tailed Bats - LOUISE C. ALLEN; AMY S. TURMELLE; ERIC P. WIDMAIER; NICKOLAY I. HRISTOV; GARY F. MCCRACKEN; THOMAS H. KUNZ (Conservation Biology, 2011)
Since the late 1980s, Brazilian free‐tailed bats ( Tadarida brasiliensis ) have increasingly used bridges as roosts in the southern United States. We examined differences in blood cortisol levels, body condition, and parasite load, as measures of physiological stress in bats roosting in bridges and bats roosting in caves. We collected data during three periods, coinciding with female phases of reproduction. For all measures, bats were captured during the nightly emergence from the roost and immediately sampled. Cortisol levels were significantly higher during pregnancy and lactation and in individuals with lower body‐condition scores (length of forearm to mass ratio) and significantly higher in bats roosting in caves than in those roosting in bridges. Thus, we concluded that individuals of this species that roost in bridges are not chronically stressed and seem to be unaffected by human activities present at bridges. This is a rare documented instance where a human‐dominated environment does not appear to be adversely affecting the physiological health of a free‐ranging animal .

Utilization of Dairy Byproduct Proteins, Surfactants, and Enzymes in Frozen Dough - Ali Asghar; Faqir Muhammad Anjum; Jonathan C. Allen (Critical Reviews in Food Science and Nutrition, 2011)

Age estimation and lead–radium dating of Antarctic toothfish (Dissostichus mawsoni) in the Ross Sea - Cassandra M. Brooks; Allen H. Andrews; Julian R. Ashford; Nakul Ramanna; Christopher D. Jones; Craig C. Lundstrom; Gregor M. Cailliet (Polar Biology, 2011)

Rock avalanches and other landslides in the central Southern Alps of New Zealand: a regional study considering possible climate change impacts - Simon K. Allen; Simon C. Cox; Ian F. Owens (Landslides, 2011)

Investigation of 15 of the top candidate genes for late-onset Alzheimer’s disease - Olivia Belbin; Minerva M. Carrasquillo; Michael Crump; Oliver J. Culley; Talisha A. Hunter; Li Ma; Gina Bisceglio; Fanggeng Zou; Mariet Allen; Dennis W. Dickson; Neill R. Graff-Radford; Ronald C. Petersen; et al. (Human Genetics, 2011)

Tissue procurement strategies affect the protein biochemistry of human heart samples - Lori A. Walker; Allen M. Medway; John S. Walker; Joseph C. Cleveland; Peter M. Buttrick (Journal of Muscle Research and Cell Motility, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

The evolutionary pathway from anoxygenic to oxygenic photosynthesis examined by comparison of the properties of photosystem II and bacterial reaction centers - J. P. Allen; J. C. Williams (Photosynthesis Research, 2011)

Effects of Central Airway Shunting on the Mechanical Impedance of the Mouse Lung - Benjamin L. Schwartz; Ron C. Anafi; Minara Aliyeva; John A. Thompson-Figueroa; Gilman B. Allen; Lennart K. A. Lundblad; Jason H. T. Bates (Annals of Biomedical Engineering, 2011)

Pathogenesis of Pulmonary Cryptococcus gattii Infection: A Rat Model - Mark B. Krockenberger; Richard Malik; Popchai Ngamskulrungroj; Luciana Trilles; Patricia Escandon; Susan Dowd; Chris Allen; Uwe Himmelreich; Paul J. Canfield; Tania C. Sorrell; Wieland Meyer (Mycopathologia, 2010)

Genetic Diversity of Aedes vexans (Diptera, Culicidae) from New Orleans: Pre- and Post-Katrina - Cesar D. Solorzano; Allen L. Szalanski; Carrie B. Owens; C. Dayton Steelman (Biochemical Genetics, 2010)

The Correlation of 3D DT-MRI Fiber Disruption with Structural and Mechanical Degeneration in Porcine Myocardium - Song Zhang; J. Allen Crow; Xiaoyong Yang; Joseph Chen; Ali Borazjani; Katie B. Mullins; Wei Chen; Robert C. Cooper; Ronald M. McLaughlin; Jun Liao (Annals of Biomedical Engineering, 2010)

Suspended particles in the Canada Basin from optical and bottle data, 2003–2008 - J. M. Jackson; S. E. Allen; E. C. Carmack; F. A. McLaughlin (Ocean Science, 2010)
It is expected that coastal erosion, upwelling, and increased river runoff from Arctic warming will increase the concentration of suspended particles in the Arctic Ocean. Here we analyze in situ transmissometer and fluorometer data from the summers of 2003 through 2008 and bottle-derived particulate organic carbon (POC) and total suspended solids (TSS) measurements sampled in the summers of 2006 and 2007 from the Canada Basin and surrounding shelves. We divided our study area into five regions to account for the significant spatial variability and found that the highest attenuation, POC and TSS values were observed along the Beaufort shelf and the lowest values were located along the eastern shelf of the Canada Basin. We then explored the correlation of POC and TSS with beam attenuation coefficients to assess the viability of estimating POC concentrations from archived transmissometer data. POC (but not TSS) and attenuation were well-correlated over the Northwind Ridge, in the Canada Basin interior, and along the eastern shelf of the Canada Basin. Neither TSS nor POC were well-correlated with attenuation along the entire Beaufort shelf. An interannual comparison of the attenuation and fluorescence data was done. We found no evidence of increasing attenuation from the summers of 2003 through 2008 and, although not statistically significant, it even appeared that attenuation decreased over time in the upper 25 m of the Northwind Ridge and in the 25–100 m layer (that includes the chlorophyll maximum) of the eastern Beaufort shelf and within the Canada Basin. In the Canada Basin interior, the subsurface chlorophyll maximum deepened at a rate of 3.2 m per year from an average of 45 m in 2003 to 61 m in 2008, an example of how changes to the Arctic climate are impacting its ecology.

Performance assessment of an irrigation scheme using indicators determined with remote sensing techniques - C. Santos; Ignacio J. Lorite; M. Tasumi; R. G. Allen; E. Fereres (Irrigation Science, 2010)

Integrating Environmental and Socio-Economic Indicators of a Linked Catchment–Coastal System Using Variable Environmental Intensity - John R. Dymond; Tim J. A. Davie; Andrew D. Fenemor; Jagath C. Ekanayake; Ben R. Knight; Anthony O. Cole; Oscar Montes de Oca Munguia; Will J. Allen; Roger G. Young; Les R. Basher; Marc Dresser; Chris J. Batstone (Environmental Management, 2010)

Erratum to: Interaction between groundwater, the hyporheic zone and a Chalk stream: a case study from the River Lambourn, UK - David J. Allen; W. George Darling; Daren C. Gooddy; Daniel J. Lapworth; Andrew J. Newell; Ann T. Williams; Debbie Allen; Corinna Abesser (Hydrogeology Journal, 2010)

Interaction between groundwater, the hyporheic zone and a Chalk stream: a case study from the River Lambourn, UK - David J. Allen; W. George Darling; Daren C. Gooddy; Daniel J. Lapworth; Andrew J. Newell; Ann T. Williams; Debbie Allen; Corinna Abesser (Hydrogeology Journal, 2010)

Spatial and Temporal Hypoxia Dynamics in Dense Emergent Macrophytes in a Florida Lake - Aaron J. Bunch; Micheal S. Allen; Daniel C. Gwinn (Wetlands, 2010)

A phylogenetic investigation of Carthamus combining sequence and microsatellite data - Victoria G. Bowles; Reinhold Mayerhofer; Corey Davis; Allen G. Good; Jocelyn C. Hall (Plant Systematics and Evolution, 2010)

Analyzing complex traits with congenic strains - Haifeng Shao; David S. Sinasac; Lindsay C. Burrage; Craig A. Hodges; Pamela J. Supelak; Mark R. Palmert; Carol Moreno; Allen W. Cowley; Howard J. Jacob; Joseph H. Nadeau (Mammalian Genome, 2010)

Assembly history dictates ecosystem functioning: evidence from wood decomposer communities - Tadashi Fukami; Ian A. Dickie; J. Paula Wilkie; Barbara C. Paulus; Duckchul Park; Andrea Roberts; Peter K. Buchanan; Robert B. Allen (Ecology Letters, 2010)
Ecology Letters (2010) 13: 675–684 Abstract Community assembly history is increasingly recognized as a fundamental determinant of community structure. However, little is known as to how assembly history may affect ecosystem functioning via its effect on community structure. Using wood‐decaying fungi as a model system, we provide experimental evidence that large differences in ecosystem functioning can be caused by small differences in species immigration history during community assembly. Direct manipulation of early immigration history resulted in three‐fold differences in fungal species richness and composition and, as a consequence, differences of the same magnitude in the rate of decomposition and carbon release from wood. These effects – which were attributable to the history‐dependent outcome of competitive and facilitative interactions – were significant across a range of nitrogen availabilities observed in natural forests. Our results highlight the importance of considering assembly history in explaining ecosystem functioning.

Hybridization and polyploidy as drivers of continuing evolution and speciation in Sorbus - ASHLEY ROBERTSON; TIMOTHY C. G. RICH; ALEXANDRA M. ALLEN; LIBBY HOUSTON; CAT ROBERTS; JON R. BRIDLE; STEPHEN A. HARRIS; SIMON J. HISCOCK (Molecular Ecology, 2010)

Ploidy levels of Dioscorea alata L. germplasm determined by flow cytometry - J. Obidiegwu; E. Rodriguez; E. Ene-Obong; J. Loureiro; C. Muoneke; C. Santos; M. Kolesnikova-Allen; R. Asiedu (Genetic Resources and Crop Evolution, 2010)

Myogenic regulatory factor response to resistance exercise volume in skeletal muscle - Micah J. Drummond; Robert K. Conlee; Gary W. Mack; Sterling Sudweeks; G. Bruce Schaalje; Allen C. Parcell (European Journal of Applied Physiology, 2010)

Top‐down control of microbial activity and biomass in an Arctic soil ecosystem - Bethany Allen; Dana Willner; Walter C. Oechel; David Lipson (Environmental Microbiology, 2010)
Summary Globally, soil microbes preside over vast carbon stores, and both microbial biomass and activity are known to be regulated by bottom‐up controls, that is, limitation by nutrients and energy. However, there is evidence that grazing by protozoans exerts top‐down controls on biomass. Here, we investigate top‐down control by phage on soil microbes using an experimental site near Barrow, Alaska (71°N, 157°W) during the 2007 growing season. Soil measurements were taken from sites that covered a range of microtopographical features within a drained and thawed lake basin including high‐ and low‐centred ice‐wedge polygons to estimate the availability of carbon and nitrogen for microbes. Using both field and laboratory experiments, we successfully increased both microbial biomass and respiration by decreasing phage populations. The addition of carbon and nutrients to soils had no significant effects on biomass or respiration, indicating a lack of bottom‐up controls. Additionally, we present the first use of tea extracts as a potent anti‐phage agent in soils. Our results suggest that top‐down controls, such as phage predation, are critical to regulation of microbial activities in Arctic soils.

Surface Elevation Change and Susceptibility of Different Mangrove Zones to Sea-Level Rise on Pacific High Islands of Micronesia - Ken W. Krauss; Donald R. Cahoon; James A. Allen; Katherine C. Ewel; James C. Lynch; Nicole Cormier (Ecosystems, 2010)

Structures of proteins and cofactors: X-ray crystallography - J. P. Allen; C. Seng; C. Larson (Photosynthesis Research, 2009)

Latitudinal patterns of magnitude and interannual variability in net ecosystem exchange regulated by biological and environmental variables - WENPING YUAN; YIQI LUO; ANDREW D. RICHARDSON; RAM OREN; SEBASTIAAN LUYSSAERT; IVAN A. JANSSENS; REINHART CEULEMANS; XUHUI ZHOU; THOMAS GRÜNWALD; MARC AUBINET; CHRISTIAN BERHOFER; DENNIS D. BALDOCCHI; et al. (Global Change Biology, 2009)
Over the last two and half decades, strong evidence showed that the terrestrial ecosystems are acting as a net sink for atmospheric carbon. However the spatial and temporal patterns of variation in the sink are not well known. In this study, we examined latitudinal patterns of interannual variability (IAV) in net ecosystem exchange (NEE) of CO 2 based on 163 site‐years of eddy covariance data, from 39 northern‐hemisphere research sites located at latitudes ranging from ∼29°N to ∼64°N. We computed the standard deviation of annual NEE integrals at individual sites to represent absolute interannual variability (AIAV), and the corresponding coefficient of variation as a measure of relative interannual variability (RIAV). Our results showed decreased trends of annual NEE with increasing latitude for both deciduous broadleaf forests and evergreen needleleaf forests. Gross primary production (GPP) explained a significant proportion of the spatial variation of NEE across evergreen needleleaf forests, whereas, across deciduous broadleaf forests, it is ecosystem respiration (Re). In addition, AIAV in GPP and Re increased significantly with latitude in deciduous broadleaf forests, but AIAV in GPP decreased significantly with latitude in evergreen needleleaf forests. Furthermore, RIAV in NEE, GPP, and Re appeared to increase significantly with latitude in deciduous broadleaf forests, but not in evergreen needleleaf forests. Correlation analyses showed air temperature was the primary environmental factor that determined RIAV of NEE in deciduous broadleaf forest across the North American sites, and none of the chosen climatic factors could explain RIAV of NEE in evergreen needleleaf forests. Mean annual NEE significantly increased with latitude in grasslands. Precipitation was dominant environmental factor for the spatial variation of magnitude and IAV in GPP and Re in grasslands.

A Biogeochemical View of Estuarine Eutrophication: Seasonal and Spatial Trends and Correlations in the Delaware Estuary - Jonathan H. Sharp; Kohei Yoshiyama; Alexander E. Parker; Matthew C. Schwartz; Susan E. Curless; Allison Y. Beauregard; Justin E. Ossolinski; Allen R. Davis (Estuaries and Coasts, 2009)

Genetic diversity assessment of sub-samples of cacao, Theobroma cacao L. collections in West Africa using simple sequence repeats marker - Peter O. Aikpokpodion; Juan C. Motamayor; Victor O. Adetimirin; Yaw Adu-Ampomah; Ivan Ingelbrecht; Albertus B. Eskes; Raymond J. Schnell; Maria Kolesnikova-Allen (Tree Genetics & Genomes, 2009)

Ploidy level studies on the Dioscorea cayenensis/Dioscorea rotundata complex core set - J. Obidiegwu; J. Loureiro; E. Ene-Obong; E. Rodriguez; M. Kolesnikova-Allen; C. Santos; C. Muoneke; R. Asiedu (Euphytica, 2009)

WUS and STM-based reporter genes for studying meristem development in poplar - Y. Bao; P. Dharmawardhana; R. Arias; M. B. Allen; C. Ma; Steven H. Strauss (Plant Cell Reports, 2009)

Vampire rock avalanches of January 2008 and 2003, Southern Alps, New Zealand - S. C. Cox; S. K. Allen (Landslides, 2009)

Effects of sibutramine and rimonabant in rats trained to discriminate between 22- and 2-h food deprivation - David C. Jewett; Thomas W. Hahn; Travis R. Smith; Britta L. Fiksdal; Jason M. Wiebelhaus; Andrew R. Dunbar; Catherine R. Filtz; Noah L. Novinska; Allen S. Levine (Psychopharmacology, 2009)

Roosting ecology and variation in adaptive and innate immune system function in the Brazilian free-tailed bat (Tadarida brasiliensis) - Louise C. Allen; Amy S. Turmelle; Mary T. Mendonça; Kristen J. Navara; Thomas H. Kunz; Gary F. McCracken (Journal of Comparative Physiology B, 2009)

An integrated approach to assess broad-scale condition of coastal wetlands—the Gulf of Mexico Coastal Wetlands pilot survey - Janet A. Nestlerode; Virginia D. Engle; Pete Bourgeois; Paul T. Heitmuller; John M. Macauley; Yvonne C. Allen (Environmental Monitoring and Assessment, 2009)

The readthrough domain of pea enation mosaic virus coat protein is not essential for virus stability in the hemolymph of the pea aphid - Sijun Liu; S. Sivakumar; Zhaohui Wang; Bryony C. Bonning; W. Allen Miller (Archives of Virology, 2009)

Comparative Analyses of Coding and Noncoding DNA Regions Indicate that Acropora (Anthozoa: Scleractina) Possesses a Similar Evolutionary Tempo of Nuclear vs. Mitochondrial Genomes as in Plants - I.-Ping Chen; Chung-Yu Tang; Chih-Yung Chiou; Jia-Ho Hsu; Nuwei Vivian Wei; Carden C. Wallace; Paul Muir; Henry Wu; Chaolun Allen Chen (Marine Biotechnology, 2009)

Global population structure of the tope ( Galeorhinus galeus ) inferred by mitochondrial control region sequence data - C. L. CHABOT; L. G. ALLEN (Molecular Ecology, 2009)
In order to properly manage and conserve exploited shark species, detailed analyses of their population structure is needed. Global populations of Galeorhinus galeus are in decline due to the exploitation of the fishery over the past 80 years. Currently, the genetic structure of eastern Pacific populations of G. galeus is not known and recent observations in the northeastern Pacific suggest an increase in numbers. To evaluate gene flow among populations of G. galeus , 116 samples were collected and analysed from six geographically dispersed locations: Australia, North America, South Africa, South America (Argentina and Peru), and the UK. Analysis of 968 to 1006 bp of the 1068‐bp mitochondrial control region revealed 38 unique haplotypes that were largely restricted to their collecting locality. Significant genetic structure was detected among populations (Φ ST = 0.84; P Nm = 0.05–0.97). Due to an apparent lack of migration, populations of G. galeus appear to be isolated from each other with little to no gene flow occurring among them. As a consequence of this isolation, increasing numbers of G. galeus in the northeastern Pacific can be best explained by local recruitment and not by input from geographically distant populations.

EPR, ENDOR, and Special TRIPLE measurements of P•+ in wild type and modified reaction centers from Rb. sphaeroides - J. P. Allen; J. M. Cordova; C. C. Jolley; T. A. Murray; J. W. Schneider; N. W. Woodbury; J. C. Williams; J. Niklas; G. Klihm; M. Reus; W. Lubitz (Photosynthesis Research, 2009)

Sugar Maple Decline after Defoliation by Forest Tent Caterpillar - Dustin M. Wood; Ruth D. Yanai; Douglas C. Allen; Sandra H. Wilmot (Journal of Forestry, 2009)
Defoliation is a significant stressor of forest stands that may incite decline disease of sugar maple ( Acer saccharum: Marsh). The recent outbreak (2002-2007) of forest tent caterpillar (FTC; Malacosoma disstria: Hübner) in the northeastern United States offered the opportunity to assess the effects of defoliation and site conditions on sugar maple health. We measured 51 North American Maple Project stands in New York and Vermont in the summer of 2007. Dieback (P = 0.07) and mortality (P = 0.04) were both worse in stands defoliated by FTC. Low growing-season soil moisture during the outbreak, indicated by Palmer's Z-index; cool mean temperature during the outbreak; and concave microrelief were also important predictors of forest damage. We present the results of our multiple regression equations for stand dieback (R2 = 0.71) and mortality (R2 = 0.64) in tables that can be used by forest managers to evaluate the vulnerability of their sugar maple stands to decline after defoliation by FTC.

Cohesive social behaviour shortens the stress response: the effects of conspecifics on the stress response in lake sturgeon Acipenser fulvescens - P. J. Allen; C. C. BARTH; S. J. Peake; M. V. Abrahams; W. G. Anderson (Journal of Fish Biology, 2009)
An examination was made of whether social interactions can have a beneficial effect through the attenuation of the stress response in a social species. In the first experiment, one larger (mean ± s . e . 194·0 ± 12·5 g) and seven smaller (32·0 ± 2·6 g) juvenile lake sturgeon Acipenser fulvescens were placed in tanks to determine whether a classic dominance effect would be established based on body size ( n = 6). Large fish did not establish a territory or aggressively interact with smaller fish, as there were no significant differences in nearest‐neighbour distances and an absence of aggressive behaviour (biting, chasing and pushing). In the second experiment, it was hypothesized that the presence of conspecifics would have a beneficial effect through an attenuation of the stress response. Fish in groups or isolation were stressed by a brief aerial exposure (30 s), and blood plasma was measured at regular time intervals (0, 20, 40, 60, 120 and 240 min) following the stressor via an implanted cannula ( n = 9–11). The presence of conspecifics did not affect the peak cortisol response, however, the overall cortisol response was shorter in duration compared to fish in isolation. Furthermore, secondary stress variables (plasma ions and glucose) showed differences between fish in groups and isolation. The results of these experiments suggest that social interaction plays an important and beneficial role in regulating the stress response in cohesive social species such as A. fulvescens .

Genetic diversity and structure of farm and GenBank accessions of cacao (Theobroma cacao L.) in Cameroon revealed by microsatellite markers - Ives Bruno M. Efombagn; Juan C. Motamayor; Olivier Sounigo; Albertus B. Eskes; Salomon Nyassé; Christian Cilas; Ray Schnell; Maria J. Manzanares-Dauleux; Maria Kolesnikova-Allen (Tree Genetics & Genomes, 2008)

Comparison of bacterial reaction centers and photosystem II - László Kálmán; JoAnn C. Williams; James P. Allen (Photosynthesis Research, 2008)

Magnitude and biophysical regulators of methane emission and consumption in the Australian agricultural, forest, and submerged landscapes: a review - R. C. Dalal; D. E. Allen; S. J. Livesley; G. Richards (Plant and Soil, 2008)

Developing tsunami warnings from numerical model output - S. C. R. Allen; D. J. M. Greenslade (Natural Hazards, 2008)

MAG Gene Variation and Cortical Gray Matter Volume in First Episode Schizophrenia - Aristotle N. Voineskos; Donna J. Lang; Gwyneth Zai; Natalie Bulgin; Sajid Shaikh; Wayne Su; Lili C. Kopala; G. William MacEwan; Allen E. Thornton; Geoffrey N. Smith; Jehannine C. Austin; William G. Honer; et al. (Brain Imaging and Behavior, 2008)

The ‘oriental’ component of the Balkan flora: evidence of presence on the Thracian Plain during the Weichselian late‐glacial - E. K. Magyari; J. C. Chapman; B. Gaydarska; E. Marinova; T. Deli; J. P. Huntley; J. R. M. Allen; B. Huntley (Journal of Biogeography, 2008)
Aim To obtain palaeobotanical evidence enabling evaluation of the viability of the hypothesis that the ‘oriental’ element of the Balkan flora reached south‐east Europe from Turkey prior to the Holocene, probably via the Thracian Plain during a late Quaternary glacial stage but no later than the late Weichselian. Location Ezero wetland, northern Thracian Plain, Bulgaria. Methods We undertook analyses of pollen and microspores, plant macrofossils, wood fragments and molluscs recovered from sediments deposited in the Ezero wetland during the late Weichselian and Weichselian late‐glacial. Sediment chronology was determined using radiocarbon age estimates. Results Six metres of sediments were recovered from the basin, of which the lower 3 m, extending from c . 15,450 cal yr bp to the early Allerød, was analysed. A major hiatus occurred after c . 13,900 cal yr bp , the overlying sediments being of late Holocene age. Palaeobotanical evidence indicates predominantly open vegetation during the Weichselian late‐glacial, although macrofossil remains of woody taxa demonstrate the local presence of patches of wooded steppe and gallery forest. Changes in the composition of the steppe vegetation, and in the nature of the sediments deposited in the basin, indicate changes in climatic conditions, especially in the hydrological regime and in the moisture available to vegetation. After an initially relatively moister phase, the final centuries of the late Weichselian were drier, as was a short interval that may correlate with the Older Dryas. Moister conditions characterize intervals corresponding to the Bølling and Allerød sub‐units of the Weichselian late‐glacial interstadial. Although the pollen evidence is thus consistent with that from previous studies of this period in south‐east Europe and south‐west Asia, indicating predominantly open steppe vegetation, the macrofossil evidence indicates the persistent local presence of woody taxa. The woody taxa recorded include Celtis tournefortii ‐type and Juniperus cf. J. excelsa , two taxa today characteristic of the wooded steppes of Anatolia and members of the ‘oriental’ element of the southern Balkan flora, as well as Rosaceae Subfams. Maloideae and Prunoideae, Alnus and Fraxinus . Main conclusions The late Weichselian vegetation of the northern Thracian Plain included patches of wooded steppe that supported members of the ‘oriental’ element of the modern Balkan flora. The presence of such taxa renders viable the hypothesis that they could have reached south‐east Europe from Turkey via the Thracian Plain during glacial times. Such hypotheses in historical biogeography can be evaluated critically using the evidence obtained from plant macrofossil analyses in combination with that from pollen analysis.

Analysis of Acropora muricata Calmodulin (CaM) Indicates That Scleractinian Corals Possess the Ancestral Exon/Intron Organization of the Eumetazoan CaM Gene - Chih-Yung Chiou; I-Ping Chen; Chienhsun Chen; Henry Ju-Lin Wu; Nuwei Vivian Wei; Carden C. Wallace; Chaolun Allen Chen (Journal of Molecular Evolution, 2008)

An RNA:DNA‐based growth model for young‐of‐the‐year winter flounder Pseudopleuronectes americanus (Walbaum) - R. Mercaldo‐Allen; C. Kuropat; E. M. Caldarone (Journal of Fish Biology, 2008)
A laboratory calibration experiment was conducted to determine the relationship between nucleic acid‐based variables and growth rate in young‐of‐the‐year winter flounder Pseudopleuronectes americanus . Three temperatures and three feeding levels were used to produce a variety of growth rates. Nucleic acid analyses were conducted on white muscle tissue using an ultraviolet absorption assay. RNA concentration (μg mg −1 wet tissue mass) and the ratio of RNA:DNA ( R RD ) were positively correlated with a mass‐based instantaneous growth coefficient ( G M ) ( r = 0·42 and 0·72, respectively). Fifty‐one per cent of the variability in growth rate was explained by the simple linear regression G M =−0·02615 + 0·00848 R RD ( P

Fish abundance and community composition in native and non‐native plants following hydrilla colonisation at Lake Izabal, Guatemala - C. A. BARRIENTOS; M. S. ALLEN (Fisheries Management and Ecology, 2008)
Fish community composition was assessed among six macrophyte habitats, including hydrilla, Hydrilla verticillata (L.F.) Royle, common native species (bulrush, Scirpus spp., muskgrass, Chara spp., eelgrass, Vallisneria americana Michx. and Illinois pondweed, Potamogeton illinoensis Morong) and no‐plants, to assess potential impacts of recent hydrilla colonisation on the littoral fish community at Lake Izabal, Guatemala. Fish biomass was significantly different among habitats, with hydrilla supporting the highest fish biomass. Fish density did not differ significantly among habitats. Total fish species richness was similar (12‐15 species) among habitats, but community composition changed with macrophyte presence. Biomass of mojarra, Cichlasoma maculicauda Regan, which supported the most important subsistence fishery at the lake, was significantly different among habitats and had the greatest biomass in the hydrilla habitat. Although hydrilla may adversely affect native plants, lake access and other uses, it provided useful fish habitat and likely was not detrimental to the Lake Izabal fish community composition.

Multimillion year thermal history of a porphyry copper deposit: application of U–Pb, 40Ar/39Ar and (U–Th)/He chronometers, Bajo de la Alumbrera copper–gold deposit, Argentina - Anthony C. Harris; W. James Dunlap; Peter W. Reiners; Charlotte M. Allen; David R. Cooke; Noel C. White; Ian H. Campbell; Suzanne D. Golding (Mineralium Deposita, 2008)

Integrating satellite-based evapotranspiration with simulation models for irrigation management at the scheme level - C. Santos; I. J. Lorite; M. Tasumi; R. G. Allen; E. Fereres (Irrigation Science, 2008)

Defensin Susceptibility and Colonization in the Mouse Model of AJ100, a Polymyxin B-Resistant, Brucella abortus RB51 Isolate - Shirley M. Halling; Allen E. Jensen; Steven C. Olsen (Current Microbiology, 2008)

Metabolic versatility of the Riftia pachyptila endosymbiont revealed through metagenomics - Julie C. Robidart; Shellie R. Bench; Robert A. Feldman; Alexey Novoradovsky; Sheila B. Podell; Terry Gaasterland; Eric E. Allen; Horst Felbeck (Environmental Microbiology, 2008)
Summary The facultative symbiont of Riftia pachyptila , named here Candidatus Endoriftia persephone , has evaded culture to date, but much has been learned regarding this symbiosis over the past three decades since its discovery. The symbiont population metagenome was sequenced in order to gain insight into its physiology. The population genome indicates that the symbionts use a partial Calvin–Benson Cycle for carbon fixation and the reverse TCA cycle (an alternative pathway for carbon fixation) that contains an unusual ATP citrate lyase. The presence of all genes necessary for heterotrophic metabolism, a phosphotransferase system, and dicarboxylate and ABC transporters indicate that the symbiont can live mixotrophically. The metagenome has a large suite of signal transduction, defence (both biological and environmental) and chemotaxis mechanisms. The physiology of Candidatus Endoriftia persephone is explored with respect to functionality while associated with a eukaryotic host, versus free‐living in the hydrothermal environment.

Structure and metal binding properties of ZnuA, a periplasmic zinc transporter from Escherichia coli - Liliya A. Yatsunyk; J. Allen Easton; Lydia R. Kim; Stacy A. Sugarbaker; Brian Bennett; Robert M. Breece; Ivan I. Vorontsov; David L. Tierney; Michael W. Crowder; Amy C. Rosenzweig (JBIC Journal of Biological Inorganic Chemistry, 2008)

Towards constraining climate sensitivity by linear analysis of feedback patterns in thousands of perturbed-physics GCM simulations - Benjamin M. Sanderson; C. Piani; W. J. Ingram; D. A. Stone; M. R. Allen (Climate Dynamics, 2008)

Changes in yellow perch length frequencies and sex ratios following closure of the commercial fishery and reduction in sport bag limits in southern Lake Michigan - T. E. LAUER; J. C. DOLL; P. J. ALLEN; B. BREIDERT; J. PALLA (Fisheries Management and Ecology, 2008)
The closure of the Indiana commercial fishery in Lake Michigan in 1997 provided the opportunity to examine the effects of commercial exploitation on the yellow perch, Perca flavescens (Mitchill), population. Data from annual gillnet and trawl sampling, recreational angler creel surveys and commercial fishing harvest were used to determine whether changes in length–frequency distributions and sex ratios were altered following closure. The proportions of large, adult yellow perch were significantly greater after the closure of the commercial fishery. Overexploitation of fish >200 mm by commercial harvest likely truncated the size distribution, but recreational harvest was comparatively small and did not appear to be a factor influencing size distributions. This post‐closure period also had a greater proportion of females in trawl catches, and the mean length of harvested fish increased in the recreational fishery. These findings suggest commercial exploitation influenced yellow perch population dynamics in far southern Lake Michigan.

How do elevated [CO2], warming, and reduced precipitation interact to affect soil moisture and LAI in an old field ecosystem? - Orla Dermody; Jake F. Weltzin; Elizabeth C. Engel; Philip Allen; Richard J. Norby (Plant and Soil, 2007)

Molecular identity of olfactory bulb interneurons: transcriptional codes of periglomerular neuron subtypes - Zegary J Allen; Ronald R. Waclaw; Melissa C. Colbert; Kenneth Campbell (Journal of Molecular Histology, 2007)

New alternative phosphorylation sites on the cyclin dependent kinase 1/cyclin a complex in p53-deficient human cells treated with etoposide: possible association with etoposide-induced apoptosis - Karen Higginbottom; Ulrike Jahnke; Adrian C. Newland; Finbarr E. Cotter; Paul David Allen (Apoptosis, 2007)

∼3,850 Ma tonalites in the Nuuk region, Greenland: geochemistry and their reworking within an Eoarchaean gneiss complex - Allen P. Nutman; Vickie C. Bennett; Clark R. L. Friend; Kenji Horie; Hiroshi Hidaka (Contributions to Mineralogy and Petrology, 2007)

Water Soluble Metallo-Phthalocyanines: The Role of the Functional Groups on the Spectral and Photophysical Properties - Vera T. Verdree; Serhii Pakhomov; Guifa Su; Michael W. Allen; Amber C. Countryman; Robert P. Hammer; Steven A. Soper (Journal of Fluorescence, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Effects of Injection Systems and Plastic Mulches on Distribution and Emissions of Cis- and Trans-1,3-Dichloropropene and Chloropicrin - Li-Tse Ou; John E. Thomas; L. Hartwell Allen; Joseph C. Vu; Donald W. Dickson (Archives of Environmental Contamination and Toxicology, 2007)

DRASTIC-Fm: a modified vulnerability mapping method for structurally controlled aquifers in the southern Gulf Islands, British Columbia, Canada - S. C. Denny; D. M. Allen; J. M. Journeay (Hydrogeology Journal, 2007)

Condition‐dependent reproductive tactics by large and small anadromous male sockeye salmon Oncorhynchus nerka - C. S. Allen; H. B. Rich; T. P. Quinn (Journal of Fish Biology, 2007)
Reproductive tactics, aggression and courtship by large and small (jack) male sockeye salmon Oncorhynchus nerka with ripe females in temporary enclosures depended on the size and behaviour of the competitor, not the size of the focal male. When paired with other jacks or with large but less aggressive males, jacks fought for access to ripe females rather than sneaking, but used sneaking tactics when paired with large, aggressive males. Dominant males of both size groups courted actively and females spawned readily with all combinations of males.

Use of microarrays to assess viral diversity: from genotype to phenotype - Michael J. Allen; Joaquin Martinez‐Martinez; Declan C. Schroeder; Paul J. Somerfield; William H. Wilson (Environmental Microbiology, 2007)
Summary The diversity among the coccolithovirus strains held in the Plymouth Virus Collection (PVC) was assessed using three complementary techniques: phylogeny based on DNA polymerase and major capsid protein gene sequence; host range; and a new, microarray‐based genome‐wide approach. The PVC is composed of three groups of strains that are geographically and temporally distinct. Virus strains clustered according to these groups in all three diversity assessments. Furthermore, the microarray approach based on genomic content showed that two strains, previously considered as identical to others in the PVC, are actually distinct. These results show the importance of genome‐wide surveys for assessing strain diversity. Not only has the microarray provided an alternative to the phylogeny‐derived pattern for virus evolution, it has also begun to provide some clues to the genes that may be responsible for the different phenotypes displayed by these viruses.

How useful is DNA extracted from the legs of archived insects for microsatellite-based population genetic analyses? - Phillip C. Watts; David J. Thompson; Katherine A. Allen; Stephen J. Kemp (Journal of Insect Conservation, 2007)

The Role of Cohort Studies in Drug Development: Clinical Evidence of Antiviral Activity of Serotonin Reuptake Inhibitors and HMG-CoA Reductase Inhibitors in the Central Nervous System - Scott L. Letendre; Jennifer Marquie-Beck; Ronald J. Ellis; Steven Paul Woods; Brookie Best; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina Marra; Justin C. McArthur; J. Allen McCutchan; Susan Morgello; et al. (Journal of Neuroimmune Pharmacology, 2007)

Awareness of gynecologic surveillance in women from hereditary non-polyposis colorectal cancer families - Kathleen Yang; Brian Allen; Peggy Conrad; C. Bethan Powell; Jonathan Terdiman; Lee-may Chen (Familial Cancer, 2006)

Quantifying anthropogenic influence on recent near-surface temperature change - M. R. Allen; N. P. Gillett; J. A. Kettleborough; G. Hegerl; R. Schnur; P. A. Stott; G. Boer; C. Covey; T. L. Delworth; G. S. Jones; J. F. B. Mitchell; T. P. Barnett (Surveys in Geophysics, 2006)

Relationship of alcohol intake and sex steroid concentrations in blood in pre- and post-menopausal women: the European Prospective Investigation into Cancer and Nutrition - S. Rinaldi; P. H. M. Peeters; I. D. Bezemer; L. Dossus; C. Biessy; C. Sacerdote; F. Berrino; S. Panico; D. Palli; R. Tumino; K. T. Khaw; S. Bingham; et al. (Cancer Causes & Control, 2006)

“Stout Guardian of the Door” - Douglas C. Allen (Journal of Forestry, 2006)

A Valuable Reference for the Forester’s Library - Douglas C. Allen (Journal of Forestry, 2006)

What Are the Best Loblolly Pine Genotypes Worth to Landowners? - Steven E. McKeand; Robert C. Abt; H. Lee Allen; Bailian Li; Glenn P. Catts (Journal of Forestry, 2006)
Forest landowners in the South can realize large financial benefits from planting the best loblolly pine (Pinus taeda L.) genotypes. Most of the productivity increases from genetics can be considered as increases in site index. We estimate that landowners can realize net present values of $50 to over $300/ac across a range of productivity and silvicultural management regimes simply by planting the best genotypes that are currently available from commercial and state forest nurseries. Landowners could pay more for the best genotypes, and the best seedlings would be well worth the additional costs.

Influence of Dissolved Organic Matter on Acute Toxicity of Zinc to Larval Fathead Minnows (Pimephales promelas) - Robert B. Bringolf; Brady A. Morris; Connie J. Boese; Robert C. Santore; Herbert E. Allen; Joseph S. Meyer (Archives of Environmental Contamination and Toxicology, 2006)

Effects of Application Methods of Metam Sodium and Plastic Covers on Horizontal and Vertical Distributions of Methyl Isothiocyanate in Bedded Field Plots - Li-Tse Ou; John E. Thomas; L. Hartwell Allen; Joseph C. Vu; Donald W. Dickson (Archives of Environmental Contamination and Toxicology, 2006)

The Clactonian elephant butchery site at Southfleet Road, Ebbsfleet, UK - F. F. Wenban‐Smith; P. Allen; M. R. Bates; S. A. Parfitt; R. C. Preece; J. R. Stewart; C. Turner; J. E. Whittaker (Journal of Quaternary Science, 2006)
Archaeological excavations at Southfleet Road, Ebbsfleet, Kent, have revealed a complex sequence of fossiliferous Middle Pleistocene sediments containing lithic artefacts. An incomplete skeleton of straight‐tusked elephant Palaeoloxodon antiquus was found in lacustrine sediments in close association with a cluster of mint condition cores, flakes and notched flake‐tools, some with evidence of use‐damage. These finds appear to reflect in situ tool production and butchery of the elephant carcass. A far larger concentration of similar artefacts, again in mint condition, occurred nearby in the same horizon. These finds were overlain by a fluvial gravel containing abundant handaxes, some also in mint condition. A range of fossils, including pollen, molluscs and small vertebrates, indicates temperate conditions with local woodland coeval with the elephant butchery. The sediments appear to have formed during the early part of an interglacial, almost certainly MIS 11. As well as providing rare undisturbed evidence of human behaviour, the site supports the existence of a distinctive non‐handaxe Clactonian core/flake‐tool industry in southeast England at this period. Copyright © 2006 John Wiley & Sons, Ltd.

Rapid phase-shift reversal on a Jamaican coral reef - Joshua A. Idjadi; Sarah C. Lee; John F. Bruno; William F. Precht; Laurie Allen-Requa; Peter J. Edmunds (Coral Reefs, 2006)

Patterns in body mass distributions: sifting among alternative hypotheses - C. R. Allen; A. S. Garmestani; T. D. Havlicek; P. A. Marquet; G. D. Peterson; C. Restrepo; C. A. Stow; B. E. Weeks (Ecology Letters, 2006)
Understanding how animals interact with their environment is critical for evaluating, mitigating and coping with anthropogenic alteration of Earth's biosphere. Researchers have attempted to understand some aspects of these interactions by examining patterns in animal body mass distributions. Energetic, phylogenetic, biogeographical, textural discontinuity and community interaction hypotheses have been advanced to explain observed patterns. Energetic and textural discontinuity hypotheses focus upon the allometry of resource use. The community interaction hypothesis contends that biotic interactions within assemblages of species are of primary importance. Biogeographical and phylogenetic hypotheses focus on the role of constraints on the organization of communities. This paper examines and organizes these various propositions about species body mass distributions and discusses the multiple competing hypotheses, how their predictions vary, and possible methods by which the hypotheses can be distinguished and tested. Each of the hypotheses is partial, and explains some elements of pattern in body mass distributions. The scale of appropriate application, relevance and interpretation varies among the hypotheses, and the mechanisms underlying observed patterns are likely to be multicausal and vary with scale.

Separate neurochemical classes of sympathetic postganglionic neurons project to the left ventricle of the rat heart - R. J. Richardson; I. Grkovic; A. M. Allen; C. R. Anderson (Cell and Tissue Research, 2006)

Fecundity, egg size and early hatchery survival for wild Atlantic salmon, from the River Bush - I. J. J. MOFFETT; M. ALLEN; C. FLANAGAN; W. W. CROZIER; G. J. A. KENNEDY (Fisheries Management and Ecology, 2006)
A total of 118 wild Atlantic salmon, Salmo salar L., females were stripped at the River Bush Salmon Station. The total number of eggs (fecundity) and egg diameters were compared for three age groups of adults. Adult length explained the majority of the variation in fecundity whilst freshwater age explained the majority of the variation in egg diameter. Parallel regression analysis for the total number of eggs on fish length relation for 3 years (2000–2002) showed significant temporal variation among years. Larger eggs from 2.1+ adults produced longer and heavier swim‐up fry than smaller eggs from 1.1+ adults. There was also the suggestion that the survival of eggs from 1.1+ adults was lower than eggs from 2.1+ adults to the swim‐up stage.

Preliminary characterisation of repeat families in the genome of EhV-86, a giant algal virus that infects the marine microalga Emiliania huxleyi - M. J. Allen; D. C. Schroeder; W. H. Wilson (Archives of Virology, 2006)

Mutational analysis in UK patients with a clinical diagnosis of familial hypercholesterolaemia: relationship with plasma lipid traits, heart disease risk and utility in relative tracing - Steve E. Humphries; Treena Cranston; Marcus Allen; Helen Middleton-Price; Maryam C. Fernandez; Victoria Senior; Emma Hawe; Andrew Iversen; Richard Wray; Martin A. Crook; Anthony S. Wierzbicki (Journal of Molecular Medicine, 2006)

Incursion and excursion of Antarctic biota: past, present and future - D. K. A. Barnes; D. A. Hodgson; P. Convey; C. S. Allen; A. Clarke (Global Ecology and Biogeography, 2006)
Aim To investigate the major paradigms of intense isolation and little anthropogenic influence around Antarctica and to examine the timings and scales of the modification of the southern polar biota. Location Antarctica and surrounding regions. Methods First, mechanisms of and evidence for long‐term isolation are reviewed. These include continental drift, the development of a surrounding deep‐water channel and the Antarctic Circumpolar Current (ACC). They also include levels of endemism, richness and distinctiveness of assemblages. Secondly, evidence for past and modern opportunities for species transport are investigated. Comparative levels of alien establishments are also examined around the Southern Ocean. Discussion On a Cenozoic time‐scale, it is clear that Gondwana's fragmentation led to increasing geographical isolation of Antarctica and the initiation of the ACC, which restricted biota exchange to low levels while still permitting some movement of biota. On a shorter Quaternary time‐scale, the continental ice‐sheet, influenced by solar (Milankovitch) cycles, has expanded and contracted periodically, covering and exposing terrestrial and continental shelf habitats. There were probably refugia for organisms during each glacial maxima. It is also likely that new taxa were introduced into Antarctica during cycles of ice sheet and oceanic front movement. The current situation (a glacial minimum) is not ‘normal’; full interglacials represent only 10% of the last 430 ka. On short (ecological) time‐scales, many natural dispersal processes (airborne, oceanic eddy, rafting and hitch‐hiking on migrants) enable the passage of biota to and from Antarctica. In recent years, humans have become influential both directly by transporting organisms and indirectly by increasing survival and establishment prospects via climate change. Main conclusions Patterns of endemism and alien establishment are very different across taxa, land and sea, and north vs. south of the Polar Frontal Zone. Establishment conditions, as much as transport, are important in limiting alien establishment. Three time‐scales emerge as important in the modification of Antarctica's biota. The natural ‘interglacial’ process of reinvasion of Antarctica is being influenced strongly by humans.

Use of marine sanctuaries by far‐ranging predators: commuting flights to the California Current System by breeding Hawaiian albatrosses - K. D. HYRENBACH; C. KEIPER; S. G. ALLEN; D. G. AINLEY; D. J. ANDERSON (Fisheries Oceanography, 2006)
Quantifying the dispersion and habitats of far‐ranging seabirds, turtles, and cetaceans is essential to assess whether zoning strategies can help protect upper‐trophic marine predators. In this paper, we focus on Black‐footed Albatross ( Phoebastria nigripes ) use of three US national marine sanctuaries off central California: Cordell Bank, Gulf of the Farallones, and Monterey Bay. We assessed the significance of these protected areas to albatrosses by: (i) documenting commuting flights between Hawaiian breeding sites and the California Current System (CCS); (ii) quantifying albatross dispersion patterns on the central California continental shelf and slope, and (iii) characterizing albatross habitats within sanctuary waters using concurrent satellite‐tracking data and vessel‐based sightings. Chick‐rearing albatrosses commuted from their colony on Tern Island, Hawaii (23.878°N, 166.288°W), to the CCS (34–48°N) and two of the eight satellite‐tracked birds entered the marine sanctuaries. Among the telemetry locations within sanctuary waters, two‐thirds (24 of 36) straddled the shelf break and slope (201–2000‐m depth), a pattern underscored by a concurrent vessel‐based survey in which 144 Black‐footed Albatrosses were sighted. This study illustrates the value of coordinated satellite telemetry and vessel‐based surveys to assess the distributions of protected species within existing marine protected areas. More specifically, our results underscore the importance of three central California marine sanctuaries to Hawaiian albatrosses breeding in subtropical waters, approximately 4500 km away.

Structural analysis of a designed inhibitor complexed with the hemagglutinin-neuraminidase of Newcastle disease virus - Charlotte Ryan; Viateslav Zaitsev; David J. Tindal; Jeffrey C. Dyason; Robin J. Thomson; Irina Alymova; Allen Portner; Mark von Itzstein; Garry Taylor (Glycoconjugate Journal, 2006)

Helicotylenchus dihystera in Australian cotton roots - O. G. G. Knox; C. M. T. Anderson; S. J. Allen; D. B. Nehl (Australasian Plant Pathology, 2006)

A Tropical Freshwater Wetland: I. Structure, Growth, and Regeneration - James A. Allen; Ken W. Krauss; Katherine C. Ewel; Bobby D. Keeland; Erick E. Waguk (Wetlands Ecology and Management, 2005)

Agroforestry Today: An Analysis of the 750 Presentations to the 1st World Congress of Agroforestry, 2004 - P.K. Ramachandran Nair; Samuel C. Allen; Michael E. Bannister (Journal of Forestry, 2005)
The developmental stage of a discipline can be gauged by the nature of its publications. Major themes of the 750 presentations at the 1st World Congress of Agroforestry, Orlando, Florida, 2004, were biological and ecological (28%); communication and knowledge integration (24%); and economics, marketing, and social issues (23%). The presentations related mostly (88% of total) to the tropics. About 55% of the authors came from educational institutions, 21% represented governments, and 13% represented nongovernmental organizations. The presentations showed that sustainability continued to be a major conceptual foundation of agroforestry, but there was considerable tropical-temperate contrast in efforts to attain sustainability. Although issues such as poverty alleviation, food security, and attainment of the Millennium Development Goals dominate the research and development agenda in the tropics, the focus in the temperate region is on environmental services such as carbon sequestration, water quality enhancement, and biodiversity conservation. The nature, diversity, and distribution of presentations as well as the current trends in agroforestry research suggest that agroforestry is maturing as a robust discipline.

Mitogenomic analysis of Montipora cactus and Anacropora matthai (cnidaria; scleractinia; acroporidae) indicates an unequal rate of mitochondrial evolution among Acroporidae corals - Ching-Chih Tseng; Carden C. Wallace; Chaolun Allen Chen (Coral Reefs, 2005)

Pre-clinical Study of 213Bi Labeled PAI2 for the Control of Micrometastatic Pancreatic Cancer - Chang F. Qu; Emma Y. Song; Yong Li; Syed M. A. Rizvi; Chand Raja; Ross Smith; Alfred Morgenstern; C. Apostolidis; Barry J. Allen (Clinical & Experimental Metastasis, 2005)

MUC1, MUC2, MUC4, MUC5AC and MUC6 Expression in the Progression of Prostate Cancer - Paul J. Cozzi; Jian Wang; Warick Delprado; Alan C. Perkins; Barry J. Allen; Pamela J. Russell; Yong Li (Clinical & Experimental Metastasis, 2005)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Sex differences in the contribution of nicotine and nonpharmacological stimuli to nicotine self-administration in rats - Nadia Chaudhri; Anthony R. Caggiula; Eric C. Donny; Sheri Booth; Maysa A. Gharib; Laure A. Craven; Shannon S. Allen; Alan F. Sved; Kenneth A. Perkins (Psychopharmacology, 2005)

C-peptide, IGF-I, sex-steroid hormones and adiposity: a cross-sectional study in healthy women within the European Prospective Investigation into Cancer and Nutrition (EPIC) - Irene D. Bezemer; Sabina Rinaldi; Laure Dossus; Carla H. van. Gils; Petra H. M. Peeters; Paulus A. H. van. Noord; H. Bas Bueno-de-Mesquita; Soren Paaske Johnsen; Kim Overvad; Anja Olsen; Anne Tjønneland; Heiner Boeing; et al. (Cancer Causes & Control, 2005)

Immature Diptera (excluding Culicidae) inhabiting phytotelmata in the Auckland and Wellington regions - José G. B. Derraik; Allen C. G. Heath (New Zealand Journal of Marine and Freshwater Research, 2005)
This study records the Diptera fauna (excluding Culicidae) breeding in phytotelmata in the Auckland and Wellington regions of New Zealand, particularly in native forest habitats. Diptera larvae were relatively abundant in the leaf axils of the native epiphyte Collospermum hastatum, and in the fallen leaves of the native nikau palm Rhypalostylis sapida. Chironomidae and Tipulidae were the most common families collected, but larvae of Anisopodidae, Ceratopogonidae, Empididae, Psychodidae, and Syrphidae were also present.

Clostridium clostridioforme: a mixture of three clinically important species - S. M. Finegold; Y. Song; C. Liu; D. W. Hecht; P. Summanen; E. Könönen; S. D. Allen (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Nitrogen mineralization in a pecan (Carya illinoensis K. Koch)?cotton (Gossypium hirsutum L.) alley cropping system in the southern United States - Samuel C. Allen; Shibu Jose; P. K. R. Nair; Barry J. Brecke; Vimala D. Nair; Donald A. Graetz; Craig L. Ramsey (Biology and Fertility of Soils, 2005)

Brain mitochondrial injury in human immunodeficiency virus–seropositive (HIV+) individuals taking nucleoside reverse transcriptase inhibitors - Brian C Schweinsburg; Michael J Taylor; Omar M Alhassoon; Raul Gonzalez; Gregory G Brown; Ronald J Ellis; Scott Letendre; John S Videen; J Allen McCutchan; Thomas L Patterson; Igor Grant; the HNRC Group (Journal of NeuroVirology, 2005)

Polymerase chain reaction-based suppression of repetitive sequences in whole chromosome painting probes for FISH - Lawrence C. Dugan; Melissa S. Pattee; Jennifer Williams; Mike y; Karen Sorensen; Joel S. Bedford; Allen T. Christian (Chromosome Research, 2005)

Homozygous loss of menin is well tolerated in liver, a tissue not affected in MEN1 - Peter C. Scacheri; Judy S. Crabtree; Alyssa L. Kennedy; Gary P. Swain; Jerrold M. Ward; Stephen J. Marx; Allen M. Spiegel; Francis S. Collins (Mammalian Genome, 2004)

Cytokine gene polymorphisms in ischaemic heart disease: investigation using family-based tests of association - Paul G. McGlinchey; Mark S. Spence; Chris C. Patterson; Adrian R. Allen; Gillian Murphy; David A. Savage; A. Peter Maxwell; Pascal P. McKeown (Journal of Molecular Medicine, 2004)

Analysis and glycosyl composition of the exopolysaccharide isolated from the floc‐forming wastewater bacterium Thauera sp. MZ1T - Michael S. Allen; Karen T. Welch; Benjamin S. Prebyl; David C. Baker; Arthur J. Meyers; Gary S. Sayler (Environmental Microbiology, 2004)
Summary Conditions were developed for the reproducible production, isolation and characterization of a novel microbial extracellular polysaccharide believed to be involved in transient viscous bulking at an industrial wastewater treatment plant. The exopolysaccharide was extracted from cell‐free culture supernatants of Thauera sp. strain MZ1T grown on a minimal medium with succinate. The purified polymer was found to be approximately 260 kDa in size by gel‐permeation chromatography. The GC–MS analysis of the alditol acetate and per‐ O ‐trimethylsilyl methyl glycoside derivatives revealed that the exopolysaccharide was composed of four monosaccharides including: rhamnose, galacturonic acid, N ‐acetylglucosamine and N ‐acetylfucosamine. Glucose, which also appeared at low levels, is most likely from a co‐eluting glucan. The FTIR and NMR spectroscopic analyses further revealed the presence of esterified component groups on the polymer. These results represent the first published description of a polysaccharide from a member of the genus Thauera , and lay the foundation for a deeper understanding of the factors potentially involved in zoogloeal cluster formation and viscous bulking.

X-ray photoelectron study of oxygen bonding in crystalline C?S?H phases - L. Black; K. Garbev; P. Stemmermann; K. R. Hallam; G. C. Allen (Physics and Chemistry of Minerals, 2004)

Competition for 15N-labeled fertilizer in a pecan (Carya illinoensis K. Koch)-cotton (Gossypium hirsutum L.) alley cropping system in the southern United States - Samuel C. Allen; Shibu Jose; P.K.R. Nair; Barry J. Brecke; Craig L. Ramsey (Plant and Soil, 2004)

An Atomic Force Microscopy Study of the Effect of Nanoscale Contact Geometry and Surface Chemistry on the Adhesion of Pharmaceutical Particles - Jennifer C. Hooton; Caroline S. German; Stephanie Allen; Martyn C. Davies; Clive J. Roberts; Saul J. B. Tendler; Philip M. Williams (Pharmaceutical Research, 2004)

The South Africa Stress and Health Study: Rationale and Design - David R. Williams; Allen Herman; Ronald C. Kessler; John Sonnega; Soraya Seedat; Dan J. Stein; Hashim Moomal; Colwick M. Wilson (Metabolic Brain Disease, 2004)

15 N uptake by mycorrhizal native and invasive plants from a N-eutrophied shrubland: a greenhouse experiment - Lidia C. Yoshida; Edith B. Allen (Biology and Fertility of Soils, 2004)

Species-specific measurements of ectomycorrhizal turnover under N-fertilization: combining isotopic and genetic approaches - Kathleen K. Treseder; C. A. Masiello; J. L. Lansing; M. F. Allen (Oecologia, 2004)

ELA-ICP-MS U?Pb zircon geochronology of regional volcanism hosting the Bajo de la Alumbrera Cu?Au deposit: implications for porphyry-related mineralization - Charlotte M. Allen; Scott E. Bryan; Ian H. Campbell; Rodney J. Holcombe; Anthony C. Harris; J. Michael Palin (Mineralium Deposita, 2004)

Alteration of Soil Carbon Pools and Communities of Mycorrhizal Fungi in Chaparral Exposed to Elevated Carbon Dioxide - Kathleen K. Treseder; Louise M. Egerton-Warburton; Michael F. Allen; Yufu Cheng; Walter C. Oechel (Ecosystems, 2003)

Size-Resolved Characterisation of Soluble Ions in the Particles in the Tropospheric Plume of Masaya Volcano, Nicaragua: Origins and Plume Processing - T. A. Mather; A. G. Allen; C. Oppenheimer; D. M. Pyle; A. J. S. McGonigle (Journal of Atmospheric Chemistry, 2003)

Nitrogen Starvation-Induced Changes in Amino Acid and Free Ammonium Pools in Schizophyllum commune Colonies - Jennifer N. Hanks; Jamie M. Hearnes; Allen C. Gathman; Walt W. Lilly (Current Microbiology, 2003)

Females prefer carotenoid colored males as mates in the pentamorphic livebearing fish, Poecilia parae - Godfrey R. Bourne; Felix Breden; Teresa C. Allen (The Science of Nature, 2003)

Central and peripheral haemodynamic effects of l-NAME infusion in healthy volunteers - D. R. Morgan; B. Silke; L. J. Dixon; P. B. Allen; C. G. Hanratty; G. E. McVeigh (European Journal of Clinical Pharmacology, 2003)

Analysis of Trans-Silencing Interactions Using Transcriptional Silencers of Varying Strength and Targets With and Without Flanking Nuclear Matrix Attachment Regions - Robert Ascenzi; Bekir Ülker; Joselyn J. Todd; Dolores A. Sowinski; Carolyn R. Schimeneck; George C. Allen; Arthur K. Weissinger; William F. Thompson (Transgenic Research, 2003)

Spatial variation in regional CO 2 exchange for the Kuparuk River Basin, Alaska over the summer growing season - GEORGE L. VOURLITIS; JOSEPH VERFAILLIE; WALTER C. OECHEL; ALLEN HOPE; DOUGLAS STOW; RYAN ENGSTROM (Global Change Biology, 2003)
The spatial and temporal patterns in CO 2 flux for the Kuparuk River Basin, a 9200‐km 2 watershed located in NE Alaska were estimated using the Regional Arctic CO 2 Exchange Simulator (RACES) for the 1994–1995 growing seasons. RACES uses non‐linear models and a Geographical Information System database (GIS) consisting of the normalized difference vegetation index (NDVI) and dynamic temperature and radiation maps. The spatial and temporal patterns in the NDVI during both growing seasons suggest that ecosystem development occurred 2–4 weeks earlier and was relatively more rapid in the southern portion of the Kuparuk River Basin. Rates of gross primary production (GPP) and whole‐ecosystem respiration (R) were 2–4 fold higher in the southern basin than along the arctic coastal plain depending on time of year. The higher rate of GPP estimated for the southern basin was primarily due to higher NDVI values, while the higher R estimated for the southern basin was due in part to higher temperature and the NDVI. While GPP and R showed strong latitudinal trends, spatial and temporal trends in net ecosystem CO 2 exchange (NEE) were much more variable. Thus, while spatial trends in carbon gain (GPP) and loss (R) were highly correlated, small spatial and temporal differences in these large fluxes (GPP and/or R) lead to corresponding large spatial variations in the NEE.

Restoring Arthropod Communities in Coastal Sage Scrub - J. C. Burger; R. A. Redak; E. B. Allen; J. T. Rotenberry; M. F. Allen (Conservation Biology, 2003)
Coastal sage scrub in California and northern Baja California has been severely affected by urban expansion and is, in places, badly in need of restoration. We measured arthropod abundance and diversity on one of its primary components, the native shrub Artemisia californica ( Asteraceae; California sage ), to evaluate whether arthropod communities had become reestablished after a restoration attempt. Arthropods were collected from shrubs on planted and undisturbed sites 6 years after a restoration attempt. Fifty‐seven families and 146 adult morphospecies were found. Family and species richness were greater on planted shrubs, but arthropod diversity, once differences in species' abundances were corrected for, was greater on naturally established plants. Common arthropods occurred at similar densities regardless of planting history. The proportion of single occurrences of a species, in contrast, was significantly greater on naturally established shrubs. Planted shrubs supported more predators relative to herbivores than did naturally established shrubs. Planted shrubs were still distinguishable from naturally established ones in that they were both more isolated from neighboring shrubs and surrounded by more invasive weeds. We suggest that small‐scale restoration attempts can be successful at restoring basic elements of surrounding biodiversity. They do create a different community, however, both taxonomically and functionally, and are at least initially less able to support rare species.

Characterization of Particle-Interactions by Atomic Force Microscopy: Effect of Contact Area - Jennifer C. Hooton; Caroline S. German; Stephanie Allen; Martyn C. Davies; Clive J. Roberts; Saul J. B. Tendler; Philip M. Williams (Pharmaceutical Research, 2003)

Elevation of Transgene Expression Level by Flanking Matrix Attachment Regions (MAR) is Promoter Dependent: A Study of the Interactions of Six Promoters with the RB7 3′ MAR - S. Luke Mankin; George C. Allen; Thomas Phelan; Steven Spiker; William F. Thompson (Transgenic Research, 2003)

Alterations in protein kinase C isoenzyme expression and autophosphorylation during the progression of pressure overload-induced left ventricular hypertrophy - Allison L. Bayer; Maria C. Heidkamp; Nehu Patel; Michael Porter; Steve Engman; Allen M. Samarel (Molecular and Cellular Biochemistry, 2003)

Assessment of genetic diversity within and between pearl millet landraces - Ranjana Bhattacharjee; P. Bramel; C. Hash; M. Kolesnikova-Allen; I. Khairwal (Theoretical and Applied Genetics, 2002)

Antinociceptive effects of the selective delta opioid agonist SNC80 alone and in combination with mu opioids in the squirrel monkey titration procedure - Linda Dykstra; Arthur L. Granger; Richard M. Allen; Xiaoyan Zhang; Kenner C. Rice (Psychopharmacology, 2002)

The structure of the heterodimer reaction center from Rhodobacter sphaeroides at 2.55 å resolution - A. Camara-Artigas; C. Magee; A. Goetsch; J.P. Allen (Photosynthesis Research, 2002)

High-throughput transgene copy number estimation by competitive PCR - Anton S. Callaway; Rita Abranches; Jeffery Scroggs; George C. Allen; William F. Thompson (Plant Molecular Biology Reporter, 2002)

Control of Ixodes scapularis and Amblyomma americanum Through use of the ‘4-poster’ Treatment Device on Deer in Maryland - John F. Carroll; Patricia C. Allen; Dolores E. Hill; J. Mathews Pound; J. Allen Miller; John E. George (Experimental and Applied Acarology, 2002)

Nitrogen fertilization alters the functioning of arbuscular mycorrhizas at two semiarid grasslands - Lea Corkidi; Diane L. Rowland; Nancy C. Johnson; Edith B. Allen (Plant and Soil, 2002)

The role of mtDNA background in disease expression: a new primary LHON mutation associated with Western Eurasian haplogroup J - Michael D. Brown; Elena Starikovskaya; Olga Derbeneva; Seyed Hosseini; Jon C. Allen; Irina E. Mikhailovskaya; Rem I. Sukernik; Douglas C. Wallace (Human Genetics, 2002)

Influence of Transport over a Mountain Ridge on the Chemical Composition of Marine Aerosols during the ACE-2 Hillcloud Experiment - A. G. Allen; B. M. Davison; J. D. James; L. Robertson; R. M. Harrison; C. N. Hewitt (Journal of Atmospheric Chemistry, 2002)

Constraining climate model properties using optimal fingerprint detection methods - C. E. Forest; M. R. Allen; A. P. Sokolov; P. H. Stone (Climate Dynamics, 2001)

Ecosystem controls of juvenile pink salmon ( Onchorynchus gorbuscha ) and Pacific herring ( Clupea pallasi ) populations in Prince William Sound, Alaska - Robert T. Cooney; J. R. Allen; M. A. Bishop; D. L. Eslinger; T. Kline; B. L. Norcross; C. P. Mcroy; J. Milton; J. Olsen; V. Patrick; A. J. Paul; D. Salmon; et al. (Fisheries Oceanography, 2001)
Five years of field, laboratory, and numerical modelling studies demonstrated ecosystem‐level mechanisms influencing the mortality of juvenile pink salmon and Pacific herring. Both species are prey for other fishes, seabirds, and marine mammals in Prince William Sound. We identified critical time‐space linkages between the juvenile stages of pink salmon and herring rearing in shallow‐water nursery areas and seasonally varying ocean state, the availability of appropriate zooplankton forage, and the kinds and numbers of predators. These relationships defined unique habitat dependencies for juveniles whose survivals were strongly linked to growth rates, energy reserves, and seasonal trophic sheltering from predators. We found that juvenile herring were subject to substantial starvation losses during a winter period of plankton diminishment, and that predation on juvenile pink salmon was closely linked to the availability of alternative prey for fish and bird predators. Our collaborative study further revealed that juvenile pink salmon and age‐0 herring exploit very different portions of the annual production cycle. Juvenile pink salmon targeted the cool‐water, early spring plankton bloom dominated by diatoms and large calanoid copepods, whereas young‐of‐the‐year juvenile herring were dependent on warmer conditions occurring later in the postbloom summer and fall when zooplankton was composed of smaller calanoids and a diversity of other taxa. The synopsis of our studies presented in this volume speaks to contemporary issues facing investigators of fish ecosystems, including juvenile fishes, and offers new insight into problems of bottom‐up and top‐down control. In aggregate, our results point to the importance of seeking mechanistic rather than correlative understandings of complex natural systems.

Plankton dynamics: observed and modelled responses to physical conditions in Prince William Sound, Alaska - David L. Eslinger; R. Ted Cooney; C. Peter Mcroy; Alison Ward; Thomas C. Kline; E. Paul Simpson; Jia Wang; Jennifer R. Allen (Fisheries Oceanography, 2001)
Plankton populations in Prince William Sound, Alaska, exhibited pronounced seasonal, annual and longer‐period variability in composition and standing stock in response to physically influenced differences in nutrient availability, and possibly currents that modify local biomass by exchanges with water from the bordering Gulf of Alaska. During springs in which early, strong physical stratification developed, intense, short‐lived phytoplankton blooms occurred. These blooms had relatively short residence times in the water column. In contrast, during springs in which slower, weaker stratification developed, phytoplankton blooms were prolonged and took longer to peak. These slower blooms prolonged the period of phytoplankton production, prolonged interaction with the springtime grazing community and led to the incorporation of more organic matter into pelagic food webs. A coupled biological‐physical simulation of plankton production was used to examine the implications of seasonally varying air and mixed‐layer temperatures, surface winds and incident light on the timing, duration, annual production and standing stock of plankton. Our modelling results reproduced the observed characteristics of the springtime production cycle, and the magnitude of zooplankton stocks for the period 1992–97 but not for 1981–91. These results suggest that for most of the 1990s, bottom‐up influences on nutrient supplies controlled levels of primary consumers, whereas for the 11 years before that, other unknown factors dominated this process. We present the results of a comprehensive, multiyear study of relationships between plankton and physical limitations, and a retrospective analysis of earlier conditions to explore the possible causes for these differences.

Novel mtDNA mutations and oxidative phosphorylation dysfunction in Russian LHON families - Michael D. Brown; Sergei Zhadanov; Jon C. Allen; Seyed Hosseini; Nancy J. Newman; Vasily V. Atamonov; Irina E. Mikhailovskaya; Rem I. Sukernik; Douglas C. Wallace (Human Genetics, 2001)

Patterns of natural and anthropogenic disturbance of the mangroves on the Pacific Island of Kosrae - James A. Allen; Katherine C. Ewel; Jason Jack (Wetlands Ecology and Management, 2001)

Meeting Global Policy Commitments: Carbon Sequestration and Southern Pine Forests - K.H. Johnsen; D. Wear; R. Oren; R.O. Teskey; F. Sanchez; R. Will; J. Butnor; D. Markewitz; D. Richter; T. Rials; H.L. Allen; J. Seiler; et al. (Journal of Forestry, 2001)
In managed forests, the amount of carbon further sequestered will be determined by (1) the increased amount of carbon in standing biomass (resulting from land-use changes and increased productivity); (2) the amount of recalcitrant carbon remaining below ground at the end of rotations; and (3) the amount of carbon sequestered in products created from harvested wood. Because of the region's high productivity and industrial infrastructure, carbon sequestration via southern pine forests could be increased, and this may benefit the nation in terms of global policy commitments.

Poster Session - J. van S. Graver; H. J. Banks; A. K. Sharp; A. Contessi; N. Baldassari; M. Maggioli; Sabine Prozell; Ch. Reichmuth; Maria Otília Carvalho; Ana Paula Pereira; A. Mexia; Sylvia Allen; et al. (Phytoparasitica, 2001)

Physical and chemical processes in the application of CA and/or fumigation - Cecilia V. De Dios; Maria Finesa A. Cosico; Ma. Elvira M. Martinez; D. D. Julian; I. V. Dator; R. L. Tiongson; J. van S. Graver; S. Pratt; C. Reed; Sylvia Allen; G. N. Mbata; T. W. Phillips; et al. (Phytoparasitica, 2001)

A scaling approach for quantifying the net CO 2 flux of the Kuparuk River Basin, Alaska - Walter C. Oechel; George L. Vourlitis; Joseph Verfaillie; Tim Crawford; Steve Brooks; Edward Dumas; Allen Hope; Douglas Stow; Bill Boynton; Viktor Nosov; Rommel Zulueta (Global Change Biology, 2000)
Summary Net CO 2 flux measurements conducted during the summer and winter of 1994–96 were scaled in space and time to provide estimates of net CO 2 exchange during the 1995–96 (9 May 1995–8 May 1996) annual cycle for the Kuparuk River Basin, a 9200 km 2 watershed located in NE Alaska. Net CO 2 flux was measured using dynamic chambers and eddy covariance in moist‐acidic, nonacidic, wet‐sedge, and shrub tundra, which comprise 95% of the terrestrial landscape of the Kuparuk Basin. CO 2 flux data were used as input to multivariate models that calculated instantaneous and daily rates of gross primary production (GPP) and whole‐ecosystem respiration ( R ) as a function of meteorology and ecosystem development. Net CO 2 flux was scaled up to the Kuparuk Basin using a geographical information system (GIS) consisting of a vegetation map, digital terrain map, dynamic temperature and radiation fields, and the models of GPP and R . Basin‐wide estimates of net CO 2 exchange for the summer growing season (9 May−5 September 1995) indicate that nonacidic tundra was a net sink of −31.7 ± 21.3 GgC (1 Gg = 10 9 g), while shrub tundra lost 32.5 ± 6.3 GgC to the atmosphere (negative values denote net ecosystem CO 2 uptake). Acidic and wet sedge tundra were in balance, and when integrated for the entire Kuparuk River Basin (including aquatic surfaces), whole basin summer net CO 2 exchange was estimated to be in balance (−0.9 ± 50.3 GgC). Autumn to winter (6 September 1995–8 May 1996) estimates of net CO 2 flux indicate that acidic, nonacidic, and shrub tundra landforms were all large sources of CO 2 to the atmosphere (75.5 ± 8.3, 96.4 ± 11.4, and 43.3 ± 4.7 GgC for acidic, nonacidic, and shrub tundra, respectively). CO 2 loss from wet sedge surfaces was not substantially different from zero, but the large losses from the other terrestrial landforms resulted in a whole basin net CO 2 loss of 217.2 ± 24.1 GgC during the 1995–96 cold season. When integrated for the 1995–96 annual cycle, acidic (66.4 + 25.25 GgC), nonacidic (64.7 ± 29.2 GgC), and shrub tundra (75.8 ± 8.4 GgC) were substantial net sources of CO 2 to the atmosphere, while wet sedge tundra was in balance (0.4 + 0.8 GgC). The Kuparuk River Basin as a whole was estimated to be a net CO 2 source of 218.1 ± 60.6 GgC over the 1995–96 annual cycle. Compared to direct measurements of regional net CO 2 flux obtained from aircraft‐based eddy covariance, the scaling procedure provided realistic estimates of CO 2 exchange during the summer growing season. Although winter estimates could not be assessed directly using aircraft measurements of net CO 2 exchange, the estimates reported here are comparable to measured values reported in the literature. Thus, we have high confidence in the summer estimates of net CO 2 exchange and reasonable confidence in the winter net CO 2 flux estimates for terrestrial landforms of the Kuparuk river basin. Although there is larger uncertainty in the aquatic estimates, the small surface area of aquatic surfaces in the Kuparuk river basin (≈ 5%) presumably reduces the potential for this uncertainty to result in large errors in basin‐wide CO 2 flux estimates.

Strategies for Amplification by Polymerase Chain Reaction of the Complete Sequence of the Gene Encoding Nuclear Large Subunit Ribosomal RNA in Corals - Chaolun Allen Chen; Carden C. Wallace; Jr-Kai Yu; Nuwei Vivian Wei (Marine Biotechnology, 2000)

Optimal detection and attribution of climate change: sensitivity of results to climate model differences - G. C. Hegerl; P. A. Stott; M. R. Allen; J. F. B. Mitchell; S. F. B. Tett; U. Cubasch (Climate Dynamics, 2000)

HABITAT SELECTION OF FORAGING BOTTLENOSE DOLPHINS IN RELATION TO BOAT DENSITY NEAR CLEARWATER, FLORIDA - Mark C. Allen; Andrew J. Read (Marine Mammal Science, 2000)

Venesection needle coring increases positive results with RT-PCR for detection of circulating cells expressing CEA mRNA - R.Q. Wharton; H. Patel; S.K. Jonas; C. Glover; M. Weston; T.G. Allen-Mersh (Clinical & Experimental Metastasis, 2000)

Use of matrix attachment regions (MARs) to minimize transgene silencing - George C. Allen; Steven Spiker; William F. Thompson (Plant Molecular Biology, 2000)

Isolation, characterization, expression and functional analysis of the zebrafish ortholog of MEN1 - Pachiappan Manickam; Andreas M. Vogel; Sunita K. Agarwal; Takaya Oda; Allen M. Spiegel; Stephen J. Marx; Francis S. Collins; Brant M. Weinstein; Settara C. Chandrasekharappa (Mammalian Genome, 2000)

Modeling observed chaotic oscillations in bursting neurons: the role of calcium dynamics and IP 3 - Martin Falcke; Ramó n Huerta; Mikhail I. Rabinovich; Henry D. I. Abarbanel; Robert C. Elson; Allen I. Selverston (Biological Cybernetics, 2000)

Downed wood in Micronesian mangrove forests - James A. Allen; Katherine C. Ewel; Bobby D. Keeland; Tara Tara; Thomas J. Smith (Wetlands, 2000)

Meta-igneous (non-gneissic) tonalites and quartz-diorites from an extensive ca. 3800 Ma terrain south of the Isua supracrustal belt, southern West Greenland: constraints on early crust formation - Allen P. Nutman; Vickie C. Bennett; Clark R. L. Friend; Marc D. Norman (Contributions to Mineralogy and Petrology, 1999)

Colonoscopy aided by magnetic 3D imaging: is the technique sufficiently sensitive to detect differences between men and women? - R. S. Rowland; G. D. Bell; S. Dogramadzi; C. Allen (Medical & Biological Engineering & Computing, 1999)

Colonoscopy aided by magnetic 3D imaging: assessing the routine use of a stiffening sigmoid overtube to speed up the procedure - G. D. Bell; R. S. Rowland; M. Rutter; M. Abu-Sada; S. Dogramadzi; C. Allen (Medical & Biological Engineering & Computing, 1999)

Soil biota responses to long-term atmospheric CO 2 enrichment in two California annual grasslands - Matthias C. Rillig; Christopher B. Field; Michael F. Allen (Oecologia, 1999)

What is the role of arbuscular mycorrhizal fungi in plant-to-ecosystem responses to Elevated atmospheric CO 2 ? - M. C. Rillig; Michael F. Allen (Mycorrhiza, 1999)

Fertile Solanum tuberosum+S. commersonii somatic hybrids as sources of resistance to bacterial wilt caused by Ralstonia solanacearum - L. T. Laferriere; J. P. Helgeson; C. Allen (Theoretical and Applied Genetics, 1999)

Isolation, genomic organization, and expression analysis of Men1, the murine homolog of the MEN1 gene - Siradanahalli C. Guru; Judy S. Crabtree; Kevin D. Brown; Karen J. Dunn; Pachiappan Manickam; Nijaguna B. Prasad; Danny Wangsa; A. Lee Burns; Allen M. Spiegel; Stephen J. Marx; William J. Pavan; Francis S. Collins; et al. (Mammalian Genome, 1999)

Fungal root colonization responses in natural grasslands after long‐term exposure to elevated atmospheric CO 2 - Matthias C. Rillig; Christopher B. Field; Michael F. Allen (Global Change Biology, 1999)
Summary Arbuscular mycorrhizae, ubiquitous mutualistic symbioses between plant roots and fungi in the order Glomales , are believed to be important controllers of plant responses to global change, in particular to elevated atmospheric CO 2 . In order to test if any effects on the symbiosis can persist after long‐term treatment, we examined root colonization by arbuscular mycorrhizal (AM) and other fungi of several plant species from two grassland communities after continuous exposure to elevated atmospheric CO 2 for six growing seasons in the field. For plant species from both a sandstone and a serpentine annual grassland there was evidence for changes in fungal root colonization, with changes occurring as a function of plant host species. We documented decreases in percentage nonmycorrhizal fungal root colonization in elevated CO 2 for several plant species. Total AM root colonization (%) only increased significantly for one out of the five plant species in each grassland. However, when dividing AM fungal hyphae into two groups of hyphae (fine endophyte and coarse endophyte), we could document significant responses of AM fungi that were hidden when only total percentage colonization was measured. We also documented changes in elevated CO 2 in the percentage of root colonized by both AM hyphal types simultaneously. Our results demonstrate that changes in fungal root colonization can occur after long‐term CO 2 enrichment, and that the level of resolution of the study of AM fungal responses may have to be increased to uncover significant changes to the CO 2 treatment. This study is also one of the first to document compositional changes in the AM fungi colonizing roots of plants grown in elevated CO 2 . Although it is difficult to relate the structural data directly to functional changes, possible implications of the observed changes for plant communities are discussed.

Phototoxicity of fluoranthene to two freshwater crustaceans, Hyalella azteca and Daphnia magna: measures of feeding inhibition as a toxicological endpoint - Audrey C. Hatch; G. Allen Burton (Hydrobiologia, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Body Mass Patterns Predict Invasions and Extinctions in Transforming Landscapes - Craig R. Allen; Elizabeth A. Forys; C. S. Holling (Ecosystems, 1999)

SPRINKMOD - pressure and discharge simulation model for pressurized irrigation systems. 2. Case study - C. de L. T. de Andrade; R. D. Wells; R. G. Allen (Irrigation Science, 1999)

SPRINKMOD - pressure and discharge simulation model for pressurized irrigation systems. 3. Sensitivity to lateral hydraulic parameters and leakage - C. de L. T. de Andrade; R. G. Allen; R. D. Wells (Irrigation Science, 1999)

SPRINKMOD - pressure and discharge simulation model for pressurized irrigation systems. 1. Model development and description - C. de L. T. de Andrade; R. G. Allen (Irrigation Science, 1999)

The influence of relative plant density and floral morphological complexity on the behaviour of bumblebees - Jane C. Stout; John A. Allen; Dave Goulson (Oecologia, 1998)

α-lactalbumin as a modulator of mammary cellular activity - Brenda Alston-Mills; Christopher D. Hepler; Lisa Sternhagen; Jonathan C. Allen; K. Alan Meshaw (In Vitro Cellular & Developmental Biology - Animal, 1998)

A synthetic complement C1q-like peptide selectively interacts with immune complexes - Err-Cheng Chan; Mai-Zon Pan; C. Allen Chang; Tzong-Zeng Wu; Yong-Bing Kuo (Biotechnology Letters, 1998)

Effects of recombinant lysostaphin on cytotoxicity and interleukin-8 level in normal human epidermal keratinocytes cell line - Err-Cheng Chan; C. Allen Chang; Tzong-Zeng Wu; Yuh-Ling Lin (Biotechnology Letters, 1998)

Repellent scent-marking of flowers by a guild of foraging bumblebees ( Bombus spp.) - Jane C. Stout; Dave Goulson; John A. Allen (Behavioral Ecology and Sociobiology, 1998)

Incomplete Removal of the Pesticide Captan from Skin by Standard Handwash Exposure Assessment Procedures - R. A. Fenske; C. Schulter; C. Lu; E. H. Allen (Bulletin of Environmental Contamination and Toxicology, 1998)

KRC transcripts: identification of an unusual alternative splicing event - Chi-Ho Mak; Ziling Li; Carl Eugene Allen; Yiling Liu; L.-C. Wu (Immunogenetics, 1998)

Nonstructural carbohydrates of soybean plants grown in subambient and superambient levels of CO2 - Leon H. Allen; Evelin C. Bisbal; Kenneth J. Boote (Photosynthesis Research, 1998)

Free energy dependence of the direct charge recombination from the primary and secondary quinones in reaction centers from Rhodobacter sphaeroides - J. P. Allen; J. C. Williams; M. S. Graige; M. L. Paddock; A. Labahn; G. Feher; M. Y. Okamura (Photosynthesis Research, 1998)

Effect of oral creatine ingestion on parameters of the work rate-time relationship and time to exhaustion in high-intensity cycling - Jimmy C. Smith; Daniel P. Stephens; Emily L. Hall; Allen W. Jackson; Conrad P. Earnest (European Journal of Applied Physiology, 1998)

Two internal pools of soluble polyphosphate in the cyanobacterium Synechocystis sp. strain PCC 6308: an in vivo 31P NMR spectroscopic study - B. A. Lawrence; C. Suarez; A. DePina; Eleanor Click; Nancy H. Kolodny; M. M. Allen (Archives of Microbiology, 1998)

Vitamin D 3 enhances mood in healthy subjects during winter - Allen T. G. Lansdowne; S. C. Provost (Psychopharmacology, 1998)

Floral display size in comfrey, Symphytum officinale L. (Boraginaceae): relationships with visitation by three bumblebee species and subsequent seed set - Dave Goulson; Jane C. Stout; Sadie A. Hawson; John A. Allen (Oecologia, 1998)

CDP840 - M. J. Perry; J. O’Connell; C. Walker; T. Crabbe; D. Baldock; A. Russell; S. Lumb; Z. Huang; D. Howat; R. Allen; M. Merriman; J. Walls; et al. (Cell Biochemistry and Biophysics, 1998)

Plant species-specific changes in root-inhabiting fungi in a California annual grassland: responses to elevated CO 2 and nutrients - Matthias C. Rillig; Michael F. Allen; John N. Klironomos; Nona R. Chiariello; Christopher B. Field (Oecologia, 1998)

Original Articles: Ecological Resilience, Biodiversity, and Scale - Garry Peterson; Craig R. Allen; C. S. Holling (Ecosystems, 1998)

Muscle satellite cells from dystrophic (mdx) mice have elevated levels of heparan sulphate proteoglycan receptors for fibroblast growth factor - NANCY J. Crisona; KAREN D. Allen; RICHARD C. Strohman (Journal of Muscle Research and Cell Motility, 1998)

Effect of contraction strength on responses in biceps brachii and adductor pollicis to transcranial magnetic stimulation - J. L. Taylor; Gabrielle M. Allen; Jane E. Butler; S. C. Gandevia (Experimental Brain Research, 1997)

Phenol Concentrations in Air and Rain Water Samples Collected near a Wood Preserving Facility - S. K. Allen; C. W. Allen (Bulletin of Environmental Contamination and Toxicology, 1997)

Organochlorine Pesticides and Polychlorinated Biphenyls (PCBs) in Sediments and Biota from Four US Arctic Lakes - S. M. Allen-Gil; C. P. Gubala; R. Wilson, D. H. Landers; T. L. Wade; J. L. Sericano; L. R. Curtis (Archives of Environmental Contamination and Toxicology, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Eighteen new polymorphic markers in the multiple endocrine neoplasia type 1 (MEN1) region - Pachiappan Manickam; Siradanahalli C. Guru; Larisa V. Debelenko; Sunita K. Agarwal; Shodimu-Emmanuel Olufemi; Jane M. Weisemann; Mark S. Boguski; Judy S. Crabtree; Yingping Wang; Bruce A. Roe; Irina A. Lubensky; Zhengping Zhuang; et al. (Human Genetics, 1997)

Does prey dispersion affect frequency-dependent predation by wild birds? - Stuart C. Church; Michael Jowers; John A. Allen (Oecologia, 1997)

Planted conifer seedling growth under two soil thermal regimes in high-elevation forest openings in interior British Columbia - Allen C. Balisky; Philip Burton (New Forests, 1997)

Introduction of a plant intron into the luciferase gene ofPhotinus pyralis - S. Luke Mankin; George C. Allen; William F. Thompson (Plant Molecular Biology Reporter, 1997)

Changes in the mechanical properties of human and amphibian muscle after eccentric exercise - C. Jones; T. Allen; J. Talbot; D. L. Morgan; U. Proske (European Journal of Applied Physiology, 1997)

Free zinc concentration in bovine milk measured by analytical affinity chromatography with immobilized metallothionein - Peifang Zhang; Jonathan C. Allen (Biological Trace Element Research, 1995)

The effect of elevated intracranial pressure on the vibrational response of the ovine head - Milan Stevanovic; George R. Wodicka; Joe D. Bourland; George P. Graber; Kirk S. Foster; Gary C. Lantz; Willis A. Tacker; Allen Cymerman (Annals of Biomedical Engineering, 1995)

Yeast communities of the cactusPilosocereus arrabidae as resources for larval and adult stages ofDrosophila serido - Paula B. Morais; Carlos A. Rosa; Allen N. Hagler; Leda C. Mendonca-Hagler (Antonie van Leeuwenhoek, 1994)

Yeast communities of the cactusPilosocereus arrabidae and associated insects in the Sandy Coastal Plains of Southeastern Brazil - Carlos A. Rosa; Paula B. Morais; Allen N. Hagler; Leda C. Mendona-Hagler; Ricardo F. Monteiro (Antonie van Leeuwenhoek, 1994)

Glucocorticoid and polyamine involvement in zinc uptake by COMMA-1D mammary epithelial cells - Jonathan C. Allen; Sharon J. Vaillancourt; Lisa Haedrich (Biological Trace Element Research, 1993)

Detection of potato leafroll virus by visual inspection, direct tissue blotting and ELISA techniques - J. L. Whitworth; R. G. Samson; T. C. Allen; A. R. Mosley (American Journal of Potato Research, 1993)

Effect of cadmium accumulation on serum vitellogenin levels and hepatosomatic and gonadosomatic indices of winter flounder (Pleuronectes americanus) - J. J. Pereira; R. Mercaldo-Allen; C. Kuropat; D. Luedke; G. Sennefelder (Archives of Environmental Contamination and Toxicology, 1993)

Evaluation of direct tissue blotting to detect potato viruses - Richard G. Samson; Thomas C. Allen; Jonathan L. Whitworth (American Journal of Potato Research, 1993)

The relative contribution of individual polychlorinated biphenyls (PCBs), polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzo-p-furans (PCDFs) to toxic equivalent values derived for bulked human adipose tissue samples from Wales, United Kingdom - Raquel Duarte-Davidson; Stuart J. Harrad; Susan Allen; Andrew S. Sewart; Kevin C. Jones (Archives of Environmental Contamination and Toxicology, 1993)

Baroreceptor responses derived from a fundamental concept - Mona F. Taher; Albert B. P. Cecchini; Mark A. Allen; Sherif R. Gobran; Robert C. Gorman; Brian L. Guthrie; Kyle A. Lingenfelter; Sina Y. Rabbany; Philip M. Rolchigo; Julius Melbin; Abraham Noordergraaf (Annals of Biomedical Engineering, 1988)

Food consumption, food utilization, and metabolic rates ofGeocoris punctipes [Het.: Lygaeidae] fedHeliothis virescens [Lep.: Noctuidae] eggs - Allen C. Cohen (BioControl, 1984)

Relationships of defined PVX infection levels to verticillium wilt, yield, and quality of the Russet Burbank potato - J. R. Davis; T. C. Allen (American Journal of Potato Research, 1984)

Maintenance, symptoms and distribution of potato viruses X, S, Y, A, M and leafroll in potato tissue culture plantlets - Jeffrey P. McMorran; Thomas C. Allen (American Journal of Potato Research, 1983)

Evaluation of Boehringer Mannheim ELISA kits for the detection of potato viruses - T. C. Allen; J. P. McMorran (American Journal of Potato Research, 1983)

Distribution of tobacco rattle virus and potato virus X in leaves, roots, and fruits and/or seeds of naturally-infected weeds - T. C. Allen; J. R. Davis (American Journal of Potato Research, 1982)

Biological and biochemical investigations on five European isolates ofMamestra brassicae nuclear polyhedrosis virus - D. A. Brown; H. F. Evans; C. J. Allen; D. C. Kelly (Archives of Virology, 1981)

Diagnosis of tobacco rattle virus (TRV) and other viruses in weed and rotation crops in potato fields - E. A. Locatelli; T. C. Allen; P. A. Koepsell; A. P. Appleby (American Journal of Potato Research, 1978)

Dislodgeable residues of ethion in Florida citrus and relationships to weather variables - H. N. Nigg; J. C. Allen; R. F. Brooks; G. J. Edwards; N. P. Thompson; Roy W. King; A. H. Blagg (Archives of Environmental Contamination and Toxicology, 1977)

s 59th annual meeting Potato Association of America - D. E. Hudson; M. D. Volz; B. B. DePhillips; Gene A. Mathia; Frank Haynes; N. A. Wynn; Allen E. Abrahams; Lewis A. Schaper; Paul H. Orr; Earl C. Yaeger; Combs Joseph; Robert L. Mercer; et al. (American Journal of Potato Research, 1975)

Weed hosts of the tobacco rattle virus in Idaho - J. R. Davis; T. C. Allen (American Journal of Potato Research, 1975)

Factors affecting the relationship between tuber size and dry-matter content - O. P. Ifenkwe; E. J. Allen; D. C. E. Wurr (American Journal of Potato Research, 1974)

Tissue modifications in monkeys as related to absorption, distribution, and excretion of polychlorinated biphenyls - J. R. Allen; D. H. Norback; I. C. Hsu (Archives of Environmental Contamination and Toxicology, 1974)

Systems analysis of arterial pressure regulation and hypertension - Arthur C. Guyton; Thomas G. Coleman; Allen W. Cowley; Jean-Francois Liard; Roger A. Norman; R. Davis Manning (Annals of Biomedical Engineering, 1972)

Computer data collection and editing for hemodynamic studies - Allen M. Scher; Winfried W. Ohm; Theodore H. Kehl; Allan C. Young (Annals of Biomedical Engineering, 1972)

Intersyngenic variations in the esterases of bacterized Paramecium aurelia - Sally Lyman Allen; Bruce C. Byrne; Donald L. Cronkite (Biochemical Genetics, 1971)

Specificity patterns of Agrobacterium tumefaciens phages - R. J. Boyd; A. C. Hildebrandt; O. N. Allen (Archives of Microbiology, 1970)

Electron microscopy of phages for Agrobacterium tumefaciens - R. J. Boyd; A. C. Hildebrandt; O. N. Allen (Archives of Microbiology, 1970)

Multiple forms of lactate dehydrogenase in the cod, Gadus morhua L. - P. H. Odense; T. C. Leung; T. M. Allen; E. Parker (Biochemical Genetics, 1969)

Concerning ?long wave length? pigments in algae - M. B. Allen; S. A. Bendix; J. C. Murchio (Archives of Microbiology, 1962)

The influence of variety on the specific gravity-mealiness relationship of potatoes - Allen E. Schark; C. E. Peterson; Frances Carlin (American Journal of Potato Research, 1956)

Sectional notes - Frank E. Garrett; David N. Wright; Cecil W. Frutchey; W. B. Ward; Allen Purdy; John C. Campbell; H. J. Evans; C. A. Henderson; W. C. Barnes; John Noonan; Edwin W. Cake; Claude R. Kemper; et al. (American Journal of Potato Research, 1948)

Sectional notes - Frank Garrett; W. B. Ward; Allen Purdy; J. C. Campbell; H. J. Evans; E. B. Tussing; E. R. Jackman; O. D. Burke; John Noonan; J. W. Scannell (American Journal of Potato Research, 1947)

Three years of potato spraying in southeastern Wisconsin - O. G Whipple; T. C. Allen (American Journal of Potato Research, 1941)

Influence of planting date on potato leafhopper population and hopperburn development - T. C. Allen; G. H. Rieman; J. S. McFarlane (American Journal of Potato Research, 1940)

Occurrence of hopperburn resistance and susceptibility in the potato - T. C. Allen; G. H. Rieman (American Journal of Potato Research, 1939)

Potato notes - C. Tice; W. C. Edmundson; W. Stuart; Seymour Bridge; Glen Carter; A. G. Allen; Daniel Dean; H. H. Zimmerly; J. O. Milward (American Journal of Potato Research, 1924)